Method for manufacturing a honeycomb body having an inorganic filtration deposit - Patents.com
By controlling the load on the honeycomb filter body and conducting water resistance tests, the problems of water resistance and filtering efficiency of the filter body in the prior art are solved, and efficient filtration performance in the water environment is achieved.
Patent Information
- Application Number
- JP2021511638
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-09-03
- Filing Date
- 2019-08-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2039-08-30
AI Technical Summary
In the prior art, when producing artificial honeycomb filter bodies with high filter efficiency and water resistance, there is a problem of excessive load or reduced filter efficiency.
A honeycomb filter body with 20 g or less load is used to ensure that the filtering efficiency is at or exceeds 70% by performing water absorption, immersion or spray water water resistance testing thereon.
The stability of filtering efficiency after water resistance test is achieved, ensuring the efficient performance of the filter body in a water environment.
Smart Images

Figure 0007660500000019 
Figure 0007660500000020 
Figure 0007660500000021
Abstract
Description
Related Applications
[0001] This application claims the benefit of priority under 35 U.S.C. §119 to U.S. Provisional Application No. 62 / 726,192, filed August 31, 2018, and to International Application No. PCT / CN2018 / 103807, filed September 3, 2018, the entire contents of which are incorporated herein by reference. [Technical field]
[0002] SUMMARY OF THE DISCLOSURE The present disclosure relates to a method for making a porous body, such as a porous ceramic honeycomb body, having an inorganic deposit of an inorganic filtration material. [Background technology]
[0003] Wall-flow filters are used to remove particulates from fluid exhaust streams, such as combustion engine exhaust. Examples include diesel particulate filters, which are used to remove particulates from diesel engine exhaust gases, and gasoline particulate filters (GPFs), which are used to remove particulates from gasoline engine exhaust gases. Exhaust gas to be filtered enters the inlet cells, passes through the cell walls, and exits the filter via the outlet channels. As the gas passes through and then exits the filter, particulates become trapped on or within the inlet cell walls. Summary of the Invention
[0004] Aspects of the present disclosure relate to porous bodies and methods for their production and use.
[0005] In one embodiment, a filtration article has a honeycomb filter body, inorganic deposits disposed within the honeycomb filter body at a loading of inorganic deposits of 20 grams or less per liter of honeycomb filter body, and a clean filtration efficiency of 70% or greater before being exposed to a water resistance test as measured by a clean filtration efficiency test, wherein the clean filtration efficiency of the filtration article after being exposed to the water resistance test is 80% or greater than the clean filtration efficiency of the filtration article before the water resistance test, and the water resistance test is selected from the group consisting of a water absorption test, a water immersion test, or a water spray test.
[0006] In one embodiment, a filtration article has a honeycomb filter body comprising a plurality of porous walls made of a first ceramic composition, the honeycomb filter body exhibiting a honeycomb filter body filtration efficiency when measured by a Clean Filtration Efficiency Test, an inorganic deposit made of a second ceramic composition having an inorganic deposit loading of 20 g or less per liter of honeycomb filter body, and a clean filtration efficiency when measured by a Clean Filtration Efficiency Test, the clean filtration efficiency being 110% or more of the honeycomb filter body filtration efficiency, and the clean filtration efficiency of the filtration article after exposure to a water resistance test being 90% or more of the clean filtration efficiency of the filtration article before the water resistance test, the water resistance test being selected from the group consisting of a water absorption test, a water immersion test, or a water spray test.
[0007] In one aspect, a filtration article includes a honeycomb filter body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending longitudinally from an inlet end to an outlet end, the plurality of channels comprising inlet channels open at the inlet end and sealed at a location spaced longitudinally from the inlet end and outlet channels open at the outlet end and sealed at a location spaced longitudinally from the outlet end; an inorganic deposit disposed on, or in, or both on and in at least some of the walls; and a silicon-containing precursor binder, the inorganic deposits being bonded to one another, to the walls, or both by the silicon-containing precursor binder.
[0008] In one embodiment, a filtration article includes a honeycomb filter body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending longitudinally from an inlet end to an outlet end, the plurality of channels comprising inlet channels open at the inlet end and sealed at a location spaced longitudinally from the inlet end and outlet channels open at the outlet end and sealed at a location spaced longitudinally from the outlet end; and inorganic deposits disposed on, or within, or both on, or within at least some of the walls, the inorganic deposits being bonded to each other, to the walls, or both, and at least a portion of the inorganic deposits form a porous inorganic network across portions of the walls, and the filtration article has a clean filtration efficiency of 70% or greater as measured by a Clean Filtration Efficiency Test.
[0009] In one embodiment, a filtration article has a honeycomb body comprised of a plurality of intersecting porous walls whose surfaces define a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel that is sealed at a location spaced from the inlet end and an outlet channel that is sealed at a location spaced from the outlet end, and an inorganic deposit disposed on, or in, or both on, or in, at least some of the walls defining the inlet channels, wherein the filtration article has a clean filtration efficiency of 70% or greater as measured by a Clean Filtration Efficiency Test, and the filtration article is moisture resistant such that the clean filtration efficiency of the article does not change by more than 5% after exposure to a Water Absorption Test, a Water Immersion Test, a Water Spray Test, or a combination thereof.
[0010] In one embodiment, a filtration article has a honeycomb body comprised of a plurality of intersecting porous walls comprised of surfaces defining a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel sealed at a location spaced from the inlet end and an outlet channel sealed at a location spaced from the outlet end, and an inorganic deposit disposed on, or in, or both on, or in, at least some of the walls defining the inlet channels, the inorganic deposit comprised of refractory inorganic nanoparticles bound by a high temperature binder comprising one or more inorganic components, the filtration article has a clean filtration efficiency of 70% or greater as measured by a Clean Filtration Efficiency Test, and the filtration article is moisture resistant such that the clean filtration efficiency of the article does not change by more than 5% after exposure to a water absorption test, a water immersion test, a water spray test, or a combination thereof.
[0011] In one embodiment, a filtration article has a honeycomb body comprised of a plurality of intersecting porous walls whose surfaces define a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel that is sealed at a location spaced from the inlet end and an outlet channel that is sealed at a location spaced from the outlet end, and an inorganic material disposed on, or within, or both on, or within at least some of the walls defining the inlet channels, wherein the filtration article has a clean filtration efficiency of 70% or greater as measured by a Clean Filtration Efficiency Test, and the filtration article is moisture resistant such that the clean filtration efficiency of the article does not change by more than 5% after exposure to a Water Absorption Test, a Water Immersion Test, a Water Spray Test, or a combination thereof.
[0012] In one embodiment, a filtration article comprises a honeycomb body comprised of a plurality of intersecting porous walls of surfaces defining a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel sealed at a location spaced from the inlet end and an outlet channel sealed at a location spaced from the outlet end, and a porous inorganic network of refractory metal oxide nanoparticles disposed on, or within, or both on, or within at least some of the walls defining the inlet channels, the refractory metal oxide nanoparticles being bound by a high temperature binder comprising one or more inorganic components, the filtration article having a clean filtration efficiency of 70% or greater as measured by a Clean Filtration Efficiency Test, and the filtration article is moisture resistant such that the clean filtration efficiency of the article does not change by more than 5% after exposure to a Water Absorption Test, a Water Immersion Test, a Water Spray Test, or a combination thereof.
[0013] In one aspect, a filtration article includes a honeycomb filter body having porous walls with pores, and an inorganic deposit disposed within the honeycomb filter body, the inorganic deposit including inorganic material nanoparticles and a binder, the inorganic deposit including a network of cohesive agglomerates of the inorganic material nanoparticles and the binder, and the binder including an alcohol-soluble binder.
[0014] Additional features and advantages are set forth in the following detailed description, and in part will be readily apparent to those skilled in the art from that description, or may be learned by practicing the embodiments described herein, including the following detailed description, the claims, and the accompanying drawings.
[0015] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated into and constitute a part of this specification. The drawings illustrate the various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. [Brief description of the drawings]
[0016] [Figure 1] 1 is a flow chart illustrating an exemplary embodiment of a process for manufacturing a material according to embodiments disclosed herein. [Diagram 2] FIG. 1 is a schematic diagram illustrating an apparatus for depositing inorganic materials according to embodiments disclosed herein. [Diagram 3] FIG. 1 is a schematic diagram illustrating an apparatus for depositing inorganic materials according to embodiments disclosed herein. [Figure 4] FIG. 1 is a schematic diagram illustrating an apparatus for depositing inorganic materials according to embodiments disclosed herein. [Diagram 5] FIG. 1 is a schematic diagram illustrating an apparatus for depositing inorganic materials according to embodiments disclosed herein. [Figure 6] FIG. 1 is a schematic diagram illustrating an apparatus for depositing inorganic materials according to embodiments disclosed herein. [Figure 7] FIG. 2 is a schematic diagram showing an unplugged honeycomb body. [Figure 8] FIG. 1 is a schematic diagram illustrating a wall-flow particulate filter according to an embodiment disclosed and described herein. [Figure 9] FIG. 9 is a longitudinal sectional view of the particulate filter shown in FIG. 8. [Figure 10] FIG. 2 is a schematic diagram showing a wall of a honeycomb body with a particulate load. [Figure 11] 1 is a flow chart illustrating an exemplary embodiment of an aqueous-based process for producing materials according to embodiments disclosed herein. [Figure 12] 1 is a graph showing filtration efficiency before and after curing for various samples prepared according to embodiments disclosed herein. [Figure 13] 1 is a graph showing pressure drop before and after cure for various samples prepared according to embodiments disclosed herein. [Figure 14A] 1 is a SEM photograph showing alumina agglomerates produced from an ethanol-based suspension (DK-2405-5%). [Figure 14B] 1 is a SEM photograph showing alumina agglomerates produced from an aqueous-based suspension (Allied-880-20%). [Figure 14C] 1 is a SEM photograph showing alumina agglomerates produced from an aqueous-based suspension (DK-880-20%). [Figure 14D] 1 is a SEM photograph showing alumina agglomerates produced from an aqueous-based suspension (DK-880-50%). [Figure 14E] FIG. 1 is a SEM photograph showing alumina agglomerates produced from an aqueous-based suspension (DK-9950-50%). [Figure 14F] 1 is a SEM photograph showing alumina agglomerates produced from an aqueous-based suspension (DK-2404-20%). [Figure 15A] 1 is a graph showing aqueous and ethanol-based processes in terms of FE / dP performance for various samples prepared according to embodiments disclosed herein. [Figure 15B] FIG. 1 is a graph showing aqueous and ethanol-based processes in terms of FE versus sediment loading for various samples prepared according to embodiments disclosed herein. [Figure 16A] 1 is a SEM photograph showing alumina agglomerates produced from an ethanol-based suspension. [Figure 16B] 1 is a SEM photograph showing alumina agglomerates produced from an aqueous-based suspension and deposited onto a porous ceramic wall. [Figure 16C] 1 is a graph showing agglomerate particle size for agglomerates produced by an ethanol-based process and an aqueous-based process. [Figure 16D] 1 is a graph showing the agglomerate cumulative size distribution produced by an ethanol-based process and an aqueous-based process. [Figure 17A] 1 is a graph showing the effect of different heat treatment temperatures on the durability of filtration efficiency with respect to water resistance for samples prepared according to embodiments disclosed herein. [Figure 17B]1 is a graph showing the effect of different heat treatment temperatures on pressure drop with respect to water resistance for samples prepared according to embodiments disclosed herein. [Figure 18A] 1 is a graph showing the effect of heat treatment on filtration efficiency at different heat treatment temperatures in relation to water resistance for samples prepared according to embodiments disclosed herein. [Figure 18B] 1 is a graph showing the effect of heat treatment on pressure drop at different heat treatment temperatures for samples prepared according to embodiments disclosed herein. [Figure 19] 1 is a graph showing filtration efficiency after various durability tests including a high flow test, a low temperature vibration test, a vehicle test, and a two-stage water resistance test. [Figure 20] 1 is a SEM photograph of a top view of the inlet region of an inlet channel of a plugged honeycomb body prepared according to embodiments disclosed herein. [Figure 21] 1 is a SEM photograph of a cut-away side view of an inlet region of an inlet channel of a plugged honeycomb body prepared according to embodiments disclosed herein. [Figure 22] 1 is a SEM photograph of a top view of the middle region of an inlet channel of a plugged honeycomb body prepared according to embodiments disclosed herein. [Diagram 23] 1 is a SEM photograph of a cut-away side view of the mid-region of an inlet channel of a plugged honeycomb body prepared according to embodiments disclosed herein. [Figure 24] 1 is a SEM photograph of a top view of the outlet area of an inlet channel of a plugged honeycomb body prepared according to an embodiment disclosed herein. [Diagram 25] 1 is a SEM photograph of a cut-away side view of an outlet area of an inlet channel of a plugged honeycomb body prepared according to embodiments disclosed herein. [Figure 26] 1 is a SEM photograph of a close-up cut-away side view of the outlet area of an inlet channel of a plugged honeycomb body prepared according to embodiments disclosed herein. [Figure 27] 27 is the SEM photograph of FIG. 26 with the colors inverted. [Figure 28] 28 is a portion of the SEM photograph of FIG. 27 with aggregate 1500 surrounded by a dashed line. [Figure 29] FIG. 29 is a schematic diagram of agglomerates 1502 forming the agglomerate 1500 region outlined by dashed lines in FIG. [Diagram 30] 1 is a flowchart illustrating an exemplary process flow in accordance with certain embodiments. [Figure 31A] FIG. 1 is a schematic diagram illustrating an apparatus for depositing filtration material according to embodiments disclosed herein. [Figure 31B] FIG. 1 is a schematic diagram illustrating an apparatus for depositing filtration material according to embodiments disclosed herein. [Figure 31C] FIG. 1 is a schematic diagram illustrating an apparatus for depositing filtration material according to embodiments disclosed herein. [Figure 31D] FIG. 1 is a schematic diagram illustrating an apparatus for depositing filtration material according to embodiments disclosed herein. [Diagram 32] 1 is a close-up SEM photograph of Al2O3 aggregates or agglomerates according to embodiments disclosed and described herein. [Figure 33A] 1 is a SEM photograph of a top view of a wall of a honeycomb body with discrete areas of filtration material deposits formed on the wall 10% axial distance from the inlet end of the honeycomb body. [Figure 33B] 1 is a SEM photograph of a top view of a wall of a honeycomb body with discrete areas of filtration material deposits formed on the wall 50% axial distance from the inlet end of the honeycomb body. [Figure 33C] 1 is a SEM photograph of a top view of a wall of a honeycomb body having a filter material deposit formed on the wall 90% axial distance from the inlet end of the honeycomb body. [Figure 33D] 1 is a SEM photograph of a close-up side view of a cross section of a wall of a honeycomb body showing filtration material deposits 10% axial distance from the inlet end of the honeycomb body. [Figure 33E] 1 is an SEM photograph of a close-up side view of a cross section of a wall of a honeycomb body showing filtration material deposits 50% axial distance from the inlet end of the honeycomb body. [Figure 33F] 1 is a SEM photograph of a close-up side view of a cross section of a wall of a honeycomb body showing filtration material deposits 90% of the axial distance from the inlet end of the honeycomb body. [Diagram 34] 1 is a graph showing filtration efficiency versus soot loading comparing an "uncoated" honeycomb body that does not include a filtration material deposit with a honeycomb body having an alumina filtration material deposit according to embodiments disclosed and described herein. [Diagram 35] 1 is a graph showing "clean" backpressure (no soot or ash loading) versus honeycomb flow rate comparing an "uncoated" honeycomb body that does not include a filtration material deposit with two different honeycomb bodies having an alumina filtration material deposit according to embodiments disclosed and described herein. [Diagram 36] 1 is a graph showing backpressure versus soot loading for an "uncoated" honeycomb body that does not include a filtration material deposit compared to a honeycomb body having an alumina filtration material deposit according to embodiments disclosed and described herein; [Figure 37A] 1 is a SEM photograph of a top view of a wall of a honeycomb body with discrete areas of filtration material deposits formed on the wall 50% axial distance from the inlet end of the honeycomb body. [Figure 37B] 1 is a SEM photograph of a top view of a wall of a honeycomb body with discrete areas of filtration material deposits formed on the wall 50% axial distance from the inlet end of the honeycomb body. [Figure 37C] 1 is a SEM photograph of a top view of a wall of a honeycomb body with a discrete area of filtration material deposit formed on the wall 90% axial distance from the inlet end of the honeycomb body. [Figure 37D] 1 is a SEM photograph of a top view of a wall of a honeycomb body with discrete areas of filtration material deposits formed on the wall 10% axial distance from the inlet end of the honeycomb body. [Figure 37E] 1 is a SEM photograph of a top view of a wall of a honeycomb body with discrete areas of filtration material deposits formed on the wall 50% axial distance from the inlet end of the honeycomb body. [Figure 37F]1 is a SEM photograph of a top view of a wall of a honeycomb body with a discrete area of filtration material deposit formed on the wall 90% axial distance from the inlet end of the honeycomb body. [Figure 38A] 1 is a SEM photograph of a top view of a wall of a honeycomb body with discrete areas of filtration material deposits formed on the wall 10% axial distance from the inlet end of the honeycomb body. [Figure 38B] 1 is a SEM photograph of a top view of a wall of a honeycomb body with discrete areas of filtration material deposits formed on the wall 50% axial distance from the inlet end of the honeycomb body. [Figure 38C] 1 is a SEM photograph of a top view of a wall of a honeycomb body with a discrete area of filtration material deposit formed on the wall 90% axial distance from the inlet end of the honeycomb body. [Figure 39] 1 is an annotated close-up SEM picture of exemplary primary particles measured for circularity. [Diagram 40] 1 is annotated SEM photographs of exemplary agglomerates measured for circularity. [Diagram 41] 1 is a graph showing the effect of binder percentage on smoke filtration efficiency loss after exposure to the basal water fog test. [Diagram 42] 1 is a SEM photograph showing alumina particles used to prepare a suspension according to an embodiment of the present disclosure. [Figure 43A] 1 is a SEM photograph showing alumina agglomerates produced from a suspension containing 5% binder according to an embodiment of the present disclosure. [Figure 43B] 1 is a SEM photograph showing alumina agglomerates produced from a suspension containing 15% binder according to an embodiment of the present disclosure. [Diagram 44] 1 is a graph of smoke filtration efficiency versus pressure drop for samples prepared according to embodiments of the present disclosure. [Figure 45A] 1 is a SEM photograph showing alumina agglomerates produced from a suspension containing 5% binder on the wall-flow filter wall surface 50% deep from the inlet before contact with water. [Figure 45B]1 is a SEM photograph showing alumina agglomerates produced from a suspension containing 5% binder on the wall-flow filter wall surface 50% deep from the inlet after contact with water. [Figure 46A] 1 is a SEM photograph showing alumina agglomerates produced from a suspension containing 15% binder on the wall-flow filter wall surface 50% deep from the inlet before contact with water. [Figure 46B] 1 is a SEM photograph showing alumina agglomerates produced from a suspension containing 15% binder on the wall-flow filter wall surface 50% deep from the inlet after contact with water. [Figure 47] 1 is a graph of clean filtration efficiency versus soot loading of samples after exposure of the samples to water. [Figure 48] 1 is a graph showing the decrease in clean filtration efficiency after exposure of samples to water. [Figure 49] 1 is a graph of filtration efficiency versus soot loading after exposure of samples to water. [Figure 50] 1 is a graph of filtration efficiency versus soot loading after exposure of samples to water. [Figure 51] 1 is a graph showing the decrease in filtration efficiency after exposure of samples to water. [Figure 52] 1 is a graph of smoke FE versus pressure drop (Pa) at 1.7 m / s for different slurry compositions. [Figure 53] 1 is a graph of loading (g / L) versus pressure drop (Pa) at 1.7 m / s for different slurry compositions. [Figure 54] 1 is a graph of efficiency versus deposition time (seconds) for different slurry compositions. [Figure 55A] FIG. 13 is an SEM image of siloxane-alumina agglomerates spray dried with 1 wt % PEG-PPG-PEG dispersion in the slurry. [Figure 55B] FIG. 13 is an SEM image of siloxane-alumina agglomerates spray dried with 1 wt % PEG-PPG-PEG dispersion in the slurry. [Figure 55C]FIG. 13 is an SEM image of siloxane-alumina agglomerates spray dried with 1 wt % PEG-PPG-PEG dispersion in the slurry. [Figure 56A] FIG. 13 is an SEM image of siloxane-alumina agglomerates spray dried with 3 wt % PEG-PPG-PEG dispersion in the slurry. [Figure 56B] FIG. 13 is an SEM image of siloxane-alumina agglomerates spray dried with 3 wt % PEG-PPG-PEG dispersion in the slurry. [Figure 56C] FIG. 13 is an SEM image of siloxane-alumina agglomerates spray dried with 3 wt % PEG-PPG-PEG dispersion in the slurry. [Figure 57] 13A-13C are SEM images of cross-sections of unmilled A1000SGD agglomerates using various dispersants. [Figure 58] 13A-13C are SEM images of cross-sections of unmilled A1000SGD agglomerates using various dispersants. [Figure 59] 13A-13C are SEM images of cross-sections of unmilled A1000SGD agglomerates using various dispersants. [Figure 60] 13A-13C are SEM images of cross-sections of unmilled A1000SGD agglomerates using various dispersants. [Figure 61A] 1 shows SEM images of siloxane-alumina agglomerates spray dried using a combination of PEG-PPG-PEG dispersion (1.5% by weight in the slurry) and TEA (1.5% by weight in the slurry) and agglomerates spray dried using only PEG-PPG-PEG dispersion at 1% and 3% by weight in the slurry. [Figure 61B] 1 shows SEM images of siloxane-alumina agglomerates spray dried using a combination of PEG-PPG-PEG dispersion (1.5% by weight in the slurry) and TEA (1.5% by weight in the slurry) and agglomerates spray dried using only PEG-PPG-PEG dispersion at 1% and 3% by weight in the slurry. [Figure 62A]1 shows SEM images of siloxane-alumina agglomerates spray dried using a combination of PEG-PPG-PEG dispersion (1.5% by weight in the slurry) and TEA (1.5% by weight in the slurry) and agglomerates spray dried using only PEG-PPG-PEG dispersion at 1% and 3% by weight in the slurry. [Figure 62B] 1 shows SEM images of siloxane-alumina agglomerates spray dried using a combination of PEG-PPG-PEG dispersion (1.5% by weight in the slurry) and TEA (1.5% by weight in the slurry) and agglomerates spray dried using only PEG-PPG-PEG dispersion at 1% and 3% by weight in the slurry. [Figure 63A] 1 shows SEM images of siloxane-alumina agglomerates spray dried using a combination of PEG-PPG-PEG dispersion (1.5% by weight in the slurry) and TEA (1.5% by weight in the slurry) and agglomerates spray dried using only PEG-PPG-PEG dispersion at 1% and 3% by weight in the slurry. [Figure 63B] 1 shows SEM images of siloxane-alumina agglomerates spray dried using a combination of PEG-PPG-PEG dispersion (1.5% by weight in the slurry) and TEA (1.5% by weight in the slurry) and agglomerates spray dried using only PEG-PPG-PEG dispersion at 1% and 3% by weight in the slurry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Reference will now be made in detail to embodiments of methods for forming honeycomb bodies, including porous honeycomb bodies having inorganic deposits (or "filtration deposits") on, or in, or both on and in the porous ceramic walls of the honeycomb body matrix, embodiments of which are illustrated in the accompanying drawings. The filtration deposits include materials deposited within the honeycomb body as well as compounds that may be produced from one or more materials originally deposited, such as by heating. For example, a binder material may be converted to an organic component by heating, which eventually burns off or volatilizes, while the inorganic component (such as silica) remains contained within the honeycomb filter body. Whenever possible, the same reference numbers are used throughout the drawings to refer to the same or similar parts.
[0018] definition As used in this specification and the appended claims, the singular forms "a," "an," and "the" include embodiments having plural referents unless the content clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally used in its sense including "and / or" unless the content clearly dictates otherwise.
[0019] As used herein, the words "have," "having," "include," "including," "comprise," "comprising," and the like are used in their open-ended sense and generally mean "including, but not limited to."
[0020] As referred to herein, a "honeycomb body" includes a ceramic honeycomb structure of a matrix of intersecting walls forming cells that define channels. Ceramic honeycomb structures can be molded, extruded, or cast from plasticized ceramic or ceramic-producing batch mixtures or pastes. The honeycomb body may include a peripheral wall, or skin, extruded along the matrix of walls or applied after extrusion of the matrix. For example, the honeycomb body may be a plugged ceramic honeycomb structure forming a filter body made of cordierite or other suitable ceramic material. A plugged honeycomb body has one or more channels plugged at one or both ends of the honeycomb body.
[0021] The honeycomb body disclosed herein includes a ceramic honeycomb structure with at least one wall carrying one or more filtration material deposits configured to filter particulate matter from a gas stream. The filtration material deposits may be in discrete regions or may be made up of one or more layers of filtration material in some portions or in some embodiments at given locations on the walls of the honeycomb body. The filtration material deposits preferably include inorganic materials, in some embodiments include organic materials, and in some embodiments include both inorganic and organic materials. For example, the honeycomb body may be formed from cordierite or other porous ceramic materials in one or more embodiments and may further include inorganic material deposits disposed on or below the wall surfaces of the cordierite honeycomb structure.
[0022] In some embodiments, the filtration material includes one or more inorganic materials, such as one or more ceramic or refractory materials.
[0023] As used herein, "green" or "green ceramic" are used interchangeably unless otherwise specified and refer to unsintered or unfired material.
[0024] method Aspects of the present disclosure relate to methods of forming porous bodies, such as porous ceramic honeycomb bodies, that include a material, such as a filtration material, such as a ceramic or refractory material, or further an inorganic material, such as a porous ceramic or refractory material. In certain embodiments, the filtration material is an aerosol-deposited filtration material. In some preferred embodiments, the filtration material includes a plurality of inorganic particle agglomerates of a ceramic material or an inorganic material, such as a refractory material. In some embodiments, the agglomerates are porous, which allows gas to flow through the agglomerates.
[0025] Aerosol deposition allows for the deposition of filtration material onto the porous ceramic walls, which can be in discrete areas as small as a single agglomerate or larger discrete areas such as multiple agglomerates, in some embodiments in the form of a porous layer of filtration material on or in, or both on and in, at least some surfaces of the walls of the ceramic honeycomb body. In certain embodiments, an advantage of the aerosol deposition method according to one or more embodiments is that ceramic honeycomb bodies with improved filtration performance can be produced economically and / or more efficiently.
[0026] In certain embodiments, the aerosol deposition process disclosed herein includes preparing a mixture (e.g., inorganic material, liquid vehicle, and binder), atomizing the mixture using a nozzle with an atomizing gas to form agglomerates and / or aggregates of the inorganic material, liquid vehicle, and binder, if any, drying the agglomerates and / or aggregates in the presence of a carrier gas or gaseous carrier stream, depositing the aggregates and / or agglomerates on a honeycomb body, and optionally hardening the material. In some embodiments, the walls of the apparatus can be heated to aid in drying the aggregates and / or agglomerates.
[0027] In various embodiments, the carrier gas can be heated in addition to or without heating the walls of the apparatus so that the liquid vehicle can evaporate from the agglomerates faster, thus generating the agglomerates more efficiently. The heated gaseous carrier stream transports both the atomized droplets and the generated agglomerates through the apparatus and into the honeycomb body. In some embodiments, the atomizing gas is heated alone or in combination with heating the carrier gas. In some embodiments, the parallel flow of the aerosolized droplets and / or agglomerates and the gaseous carrier stream in substantially the same direction into the chamber of the apparatus can help reduce material loss or overspray onto the walls of the apparatus. Additionally, a tapered section can be added to the apparatus before the agglomerates enter the ceramic honeycomb body to help make the gas flow and particle tracks more uniform across the apparatus. The inner diameter of the end of the tapered section can be slightly larger than the outer diameter of the ceramic honeycomb body to reduce or eliminate boundary effects of non-uniform particle deposition.
[0028] In the atomizing nozzle, or atomizer, high pressure and / or high velocity atomizing gas can be used to break up the suspension containing the mixture of liquid vehicle, binder, and solid particles into small droplets having an average droplet size of, for example, 4-6 μm. Heating of these droplets and fast evaporation of the liquid vehicle produces porous inorganic agglomerates before depositing on the honeycomb body walls as porous inorganic features or structures. In some embodiments, more than one nozzle is utilized so that the liquid flow rate through each nozzle can be reduced, resulting in smaller droplet sizes, even in some cases under the same operating conditions.
[0029] According to one or more embodiments, a process is disclosed herein that includes a step of generating an aerosol containing a binder that is deposited on a honeycomb body to provide a high filtration efficiency material that may be present in discrete regions on the honeycomb body to provide a particulate filter and / or in some parts or in some embodiments in an inorganic layer. According to one or more embodiments, the performance is more than 90% filtration efficiency at the cost of less than 10% pressure loss compared to an uncoated filter. According to one or more embodiments, as shown in FIG. 1, the process 400 includes a step 405 of mixture preparation, a step 410 of atomization to generate droplets, a step 415 of intermixing the droplets with a gaseous carrier flow, a step 420 of evaporating the liquid vehicle to form agglomerates, a step 425 of depositing a material, e.g., agglomerates, on the wall of the wall-flow filter, and an optional post-treatment 430, e.g., to bond the material on, or in, or both on and in the porous wall of the honeycomb body. The aerosol deposition method of forming a binder-containing agglomerate can provide high mechanical integrity without any high temperature curing step (e.g., heating to temperatures above 1000° C.), and in some embodiments can provide even higher mechanical integrity after a curing step, such as a high temperature (e.g., heating to temperatures above 1000° C.) curing step. In the process of FIG. 1, the aerosol deposition produces an inorganic material deposit, which in some particular embodiments is a porous material deposit. In some embodiments, the material deposit is in the form of discrete regions of filtration material. In some embodiments, at least some portions of the material deposit can be in the form of a porous inorganic layer.
[0030] In various embodiments, the process further includes part changeover such that the step of depositing the agglomerates on the porous walls of the plugged honeycomb body is performed semi-continuously or continuously, which reduces the idle time of the equipment. In one or more embodiments, the part changeover is timed such that the deposition is essentially continuous in and / or on the plurality of ceramic honeycomb bodies. Reference to continuous means that the operating equipment is maintained under the operating temperature and pressure as well as the raw material feed stream, and that the gaseous carrier stream and the flow of the agglomerates into the component, such as the wall-flow filter, are interrupted only to switch the loaded component to the unloaded component. Semi-continuous also allows for minor interruptions in the raw material feed stream and adjustments of the operating temperature and pressure. In one or more embodiments, semi-continuous flow means that the flow is interrupted for 0.1% to 5% or less, including 0.5% or more, 1% or more, 1.5% or more, 2% or more, 2.5% or more, and / or 4.5% or less, 4% or less, 3.5% or less, 3% or less of the operating period. In one or more embodiments, the flow is continuous for 95% to 100% of the operating period, including 96% or more, 97% or more, 98% or more, 99% or more, 99.5% or more, and / or 99.9% or less, 99% or less, 98% or less, 97% or less.
[0031] Mixture Preparation 405. In the production of inorganic materials for deposition, commercially available inorganic particles can be used as raw materials in the mixture. According to one or more embodiments, the particles are selected from Al2O3, SiO2, TiO2, CeO2, ZrO2, SiC, MgO, and combinations thereof. In one or more embodiments, the mixture is a suspension. The particles can be provided as raw materials suspended in a liquid vehicle, with additional liquid vehicle optionally being added.
[0032] In some embodiments, the liquid vehicle is an alcohol (e.g., ethanol). In other embodiments, the liquid is water. Thus, in some embodiments, the mixture is aqueous-based, e.g., the liquid vehicle of the suspension can be water. In other embodiments, the mixture is organic-based, e.g., the liquid vehicle of the mixture can be an alcohol, such as ethanol or methanol, or a combination thereof. In one or more embodiments, the liquid vehicle has a vapor pressure that is higher than the vapor pressure of water at the temperature of the gaseous carrier stream. In one or more embodiments, the liquid vehicle consists essentially of a material that has a boiling point that is lower than the boiling point of water at the temperature of the gaseous carrier stream. In one or more embodiments, the liquid vehicle is an alcohol. In one or more embodiments, the liquid vehicle is methoxyethanol, ethanol, xylene, methanol, ethyl acetate, benzene, or a mixture thereof. In one or more embodiments, the liquid vehicle is an alcohol. In one or more embodiments, the liquid vehicle consists essentially of water.
[0033] In some embodiments, the suspension comprises, by weight, 5-20% particles and 80-95% liquid, and all values and subranges therebetween. In one embodiment, the suspension comprises, by weight, 11%±1% alumina and 89%±1% ethanol.
[0034] In one or more embodiments, the particles have an average primary particle size in the range of about 10 nm to about 4 μm, about 20 nm to about 3 μm, or about 50 nm to about 2 μm, or about 50 nm to about 900 nm, or about 50 nm to about 600 nm. In certain embodiments, the average primary particle size is in the range of about 100 nm to about 200 nm, e.g., 150 nm. The average primary particle size can be determined as a calculation from the BET surface area of the aerosol particles, which in some embodiments is currently within the range of 10 m 2 / g.
[0035] In one or more embodiments, the primary particles include oxide particles, such as ceramic particles, such as Al2O3, SiO2, MgO, CeO2, ZrO2, CaO, TiO2, cordierite, mullite, SiC, aluminum titanate, and mixtures thereof.
[0036] The mixture is produced with a solvent added to dilute the suspension as necessary. Reducing the solids content in the mixture can also reduce the aggregate size proportionally if the droplets produced by atomization have a similar size. The solvent should be miscible with the suspension and should be a solvent for the binder and other ingredients.
[0037] Binders are optionally added to strengthen the agglomeration, preferably to provide adhesion or cohesion, and may include inorganic binders to provide mechanical integrity to the deposited material. Binders can provide bond strength between particles at high temperatures (>500°C). The starting materials can be organic. After exposure to high temperatures above about 150°C, the organic starting materials will decompose or react with moisture and oxygen in the air, and the final deposited material composition may include Al2O3, SiO2, MgO, CeO2, ZrO2, CaO, TiO2, cordierite, mullite, SiC, aluminum titanate, and mixtures thereof. An example of a suitable binder is Dowsil™ US-CF-2405 and Dowsil™ US-CF-2403, both available from Dow Chemical Company. Exemplary binder contents are in the range of 5% to 25% by weight of the particle content. In an embodiment, the binder content is 15-20% by weight ±1% by weight.
[0038] A catalyst can be added to accelerate the curing reaction of the binder. An exemplary catalyst in Dowsil™ US-CF-2405 used to accelerate the curing reaction is titanium butoxide. An exemplary catalyst content is 1% by weight of the binder.
[0039] Agitation of the mixture or suspension during storage and / or while waiting to be delivered to the nozzle may be performed using any desired agitation method. In one or more embodiments, agitation is performed by a mechanical agitation device. In certain embodiments, the use of a mechanical agitation device facilitates the reduction and / or elimination of potential contamination from plastic coated mixing rods in contact with the holding vessel used in magnetic agitation systems.
[0040] Atomization to generate droplets step 410. The mixture is atomized into fine droplets by high pressure gas through a nozzle. An example nozzle is 1 / 4J-SS+SU11-SS from Spraying Systems Co. The setup consists of the nozzle body as well as a fluid cap 2050 and an air cap 67147. The atomization gas can help break up the liquid-particulate-binder stream into droplets.
[0041] In one or more embodiments, the nozzles herein are nozzles that utilize internal mixing, such as the internal mix nozzles with part numbers listed above. In one or more embodiments, the nozzles herein are nozzles that utilize external mixing, such as the Spraying Systems external mix nozzle setup: 1 / 4J-SS+SU1A configured with a 64 aircap and a 1650 fluid cap. Another useful setup consists of a 64 aircap and a 1250 fluid cap. External mix nozzles can be advantageous in allowing smaller particle sizes with a narrower particle size distribution that improves material utilization and filtration efficiency. External mix nozzles tend to clog less frequently compared to internal mix nozzles. In one or more embodiments, the nozzles herein are convergent nozzles. As used herein, a convergent nozzle refers to a nozzle having a fluid flow passage in which the cross-sectional area decreases from the inlet to the outlet, thereby accelerating the flow of the fluid. A convergent nozzle may be internally mixed or externally mixed.
[0042] In one or more embodiments, the liquid-particulate-binder droplets are directed into the chamber by a single nozzle.
[0043] In one or more embodiments, the liquid-particulate-binder droplets are directed into the chamber by a plurality of nozzles. In one or more embodiments, the step of atomizing the plurality of liquid-particulate-binder streams is performed using a plurality of atomizing nozzles. The plurality of nozzles may include two or more nozzles, three or more, four or more, five or more, six or more, seven or more, eight or more, nine or more, ten or more, etc. The plurality of nozzles may be evenly spaced within the chamber. In one or more embodiments, each of the plurality of nozzles is angled toward the center of the device. The angle of the nozzle may be an acute angle ranging from less than 90° to more than 10°, inclusive, between 20° and 45°, relative to the sidewall of the device, and all values and subranges therebetween.
[0044] The pressure of the atomizing gas may be in the range of 20 psi to 150 psi (about 140 kPa to about 1.03 MPa). The pressure of the liquid may be in the range of 1 to 100 psi (about 7 to about 689 kPa). The average droplet size according to one or more embodiments may be in the range of 1 μm to 40 μm, including, for example, in the ranges of 1 μm to 15 μm, 2 μm to 8 μm, 4 μm to 8 μm, and 4 μm to 6 μm, and all values and subranges therebetween. The droplet size can be adjusted by adjusting the surface tension of the mixture, the viscosity of the mixture, the density of the mixture, the gas flow rate, the gas pressure, the liquid flow rate, the liquid pressure, and the nozzle design. In one or more embodiments, the atomizing gas comprises nitrogen. In one or more embodiments, the atomizing gas may consist essentially of an inert gas. In one or more embodiments, the atomizing gas may be primarily one or more inert gases. In one or more embodiments, the atomizing gas may be primarily nitrogen gas. In one or more embodiments, the nebulizing gas may be primarily air. In one or more embodiments, the nebulizing gas may consist essentially of nitrogen or air. In one or more embodiments, the nebulizing gas may be dry. In one or more embodiments, the nebulizing gas may be essentially free of liquid vehicle when it enters the chamber.
[0045] In some embodiments, the suspension flow rate is within the range of 10 to 25 g / min, including all values and subranges therebetween, including 18 g / min.
[0046] In some embodiments, the nitrogen flow rate of the atomizing gas flow rate is 5 to 6 Nm 3 2 to 10 Nm / hr, including all values and subranges therebetween 3 / hr.
[0047] The suspension flow and corresponding agglomerate size may be controlled by a pressure control system or a flow control system, as appropriate for the device. For a pressure control system, a pressure controller is in communication with a delivery conduit, such as a tube or pipe, into which the suspension of primary particles in liquid is introduced and then flowed to the nozzle. For a flow control system, an injector pump is provided, which delivers the suspension of primary particles in liquid to the nozzle. Atomization gas is typically supplied separately to the nozzle. In a preferred embodiment, the pump directs the liquid-particulate-binder mixture to the atomization nozzle at a substantially constant flow rate. A constant flow rate may be advantageous as opposed to maintaining a constant pressure, as it can help reduce particle size variation, thus improving material utilization.
[0048] In one or more embodiments, the suspension includes an inorganic material, a liquid vehicle, and in some embodiments, a binder, and is provided to the nozzle as a liquid-particulate-binder stream. That is, particles of the inorganic material can be mixed with the liquid vehicle and the binder material to generate the liquid-particulate-binder stream. The liquid-particulate-binder stream is atomized by the nozzle into liquid-particulate-binder droplets using an atomizing gas. In one or more embodiments, the liquid-particulate-binder stream is mixed with the atomizing gas. In one or more embodiments, the liquid-particulate-binder stream is directed into an atomizing nozzle, thereby atomizing the particles into liquid-particulate-binder droplets. The liquid-particulate-binder droplets consist of the liquid vehicle, the binder material, and the particles.
[0049] In one or more embodiments, the liquid-particulate-binder stream mixes with the atomizing gas through an atomizing nozzle. In one or more embodiments, the liquid-particulate-binder stream enters the atomizing nozzle. In one or more embodiments, mixing of the atomizing gas and the liquid-particulate-binder stream occurs inside the atomizing nozzle. In one or more embodiments, mixing of the atomizing gas and the liquid-particulate-binder stream occurs outside the atomizing nozzle.
[0050] Intermixing the droplets with a gaseous carrier stream 415. The droplets are transported by the gaseous carrier stream toward the honeycomb body. In one or more embodiments, the gaseous carrier stream includes a carrier gas and an atomizing gas. In one or more embodiments, at least a portion of the carrier gas contacts an atomizing nozzle. In one or more embodiments, substantially all of the liquid vehicle is evaporated from the droplets to form an agglomerate of particles and binder material.
[0051] In one or more embodiments, the gaseous carrier stream is heated before being mixed with the droplets. In one or more embodiments, the gaseous carrier stream is at a temperature in the range of 50°C to 500°C, including 80°C to 300°C, 50°C to 150°C, and all values and subranges therebetween. Operationally, the temperature can be chosen to at least evaporate the solvent of the mixture or suspension, as long as the final temperature is above the dew point. As a non-limiting example, ethanol can be evaporated at a low temperature. Without being bound by theory, it is believed that the advantage of a higher temperature is that the droplets evaporate faster and, once most of the liquid has evaporated, the droplets are less likely to stick together when they collide. In certain embodiments, smaller agglomerates contribute to better filtration material deposit formation. Furthermore, it is believed that if the droplets collide but contain only a small amount of liquid (such as only in the interior), the droplets will not coalesce into a spherical shape. In some embodiments, non-spherical agglomerates can provide desirable filtration performance.
[0052] In one or more embodiments, the atomizing gas is heated and then passed through and / or contacted with the nozzle to produce a heated atomizing gas, in one or more embodiments, the heated atomizing gas is at a temperature in the range of from 80° C. to 300° C., from 50° C. to 150° C., including all values and subranges therebetween.
[0053] In one or more embodiments, both the carrier gas and the atomizing gas are independently heated and contacted with the nozzle. In one or more embodiments, the gaseous vapor is heated, but the atomizing gas and nozzle are maintained at a low temperature (approximately equal to room temperature, e.g., 25-40°C). In one or more embodiments, the atomizing nozzle is cooled during atomization. In one or more embodiments, the temperature of the atomizing nozzle is maintained below the boiling point of the liquid vehicle.
[0054] A carrier gas is provided to the apparatus to facilitate drying and transporting the liquid-particulate-binder droplets and resulting agglomerates through the apparatus and into the honeycomb body. In one or more embodiments, the carrier gas is primarily an inert gas, such as nitrogen, which is particularly advantageous for alcohol-based liquid vehicles and droplets. In one or more embodiments, the carrier gas consists essentially of an inert gas. In one or more embodiments, the carrier gas is primarily one or more inert gases. In one or more embodiments, the carrier gas is primarily nitrogen gas. In one or more embodiments, the carrier gas is primarily air. In one or more embodiments, the carrier gas consists essentially of nitrogen or air. In one or more embodiments, the carrier gas is dry. In one or more embodiments, the carrier gas is essentially free of liquid vehicle when it enters the chamber. In one or more embodiments, the carrier gas contains less than 5% water vapor by weight. In one or more embodiments, the carrier gas is heated before being mixed with the droplets. In one or more embodiments, the carrier gas is at a temperature within the range of 50° C. or greater and 500° C. or less, including 80° C. or greater and 300° C. or less, 50° C. or greater and 150° C. or less, and all values and subranges therebetween.
[0055] In one or more embodiments, the nebulizing gas and carrier gas are independently delivered to the device at pressures of 90 psi (about 620 kPa) or greater, including 95 psi (about 660 kPa) or greater, 100 psi (about 689 kPa) or greater, 105 psi (about 724 kPa) or greater, 100 psi (about 689 kPa) or greater, 115 psi (about 793 kPa) or greater, or 120 psi (about 827 kPa) or greater. In one or more embodiments, a booster provides the nebulizing gas and carrier gas at the desired pressure.
[0056] The apparatus may include a diffusion zone downstream of the nozzle, wherein at least a portion of the intermixing of the liquid-particulate-binder droplets and the gaseous carrier stream occurs in the diffusion zone.
[0057] Upon intermixing of the liquid-particulate-binder droplets and the gaseous carrier stream inside the chamber, a gas-liquid-particulate-binder mixture is produced. The gas-liquid-particulate-binder mixture is heated in the intermixing zone. In one or more embodiments, droplets of liquid containing the particles and binder are present during intermixing. In one or more embodiments, the gaseous carrier stream is heated prior to intermixing with the liquid-particulate-binder droplets.
[0058] In some embodiments, the carrier gas is delivered to the chamber in an annular co-flow around the nozzle. In some embodiments, the carrier gas is delivered to the chamber of the duct in an annular flow around the nozzle and in a co-flow around the droplets at the end of the nozzle.
[0059] Evaporation 420 to form agglomerates. To avoid the effects of capillary forces of liquids that can produce inhomogeneous materials that can lead to high pressure drop costs, the droplets are dried in the evaporation section of the device to form dry solid agglomerates, sometimes called secondary particles, or "microparticles", composed of primary nanoparticles and binder-type material. The liquid vehicle, or solvent, evaporates and passes through the honeycomb body in a gas or vapor phase, so liquid solvent residue or condensation is minimized during material deposition. When the agglomerates are transported into the honeycomb body by the gas flow, the residual liquid in the inorganic material should be less than 10 wt. %. All liquid is preferably evaporated as a result of drying and converted to a gas or vapor phase. Liquid residue may also include solvents in the mixture (such as ethanol in the example), or water condensed from the gas phase. The binder is not considered a liquid residue, even if some or all of the binder is in a liquid or non-solid state before curing. In one or more embodiments, the total volumetric flow rate through the chamber is less than 20 Nm 3 / h or more and / or 100Nm 3 / h and all values and subranges therebetween 3 / h or more and / or 200Nm 3 / h or less. Higher flow rates can deposit more material than lower flow rates. Higher flow rates can be useful when larger cross-sectional area filters are produced. Larger cross-sectional area filters can have applications in filter systems for buildings or outdoor filtration systems.
[0060] In one or more embodiments, substantially all of the liquid vehicle is evaporated from the droplets to form agglomerates of particle and binder material, the agglomerates being interspersed in the gaseous carrier stream. In one or more embodiments, the apparatus has an evaporation section having an axial length sufficient to evaporate at least a portion of the liquid vehicle, including a substantial portion and / or all of the liquid vehicle from the agglomerates.
[0061] With respect to flow, in some embodiments, the path of the droplets and the path of the gaseous carrier stream are substantially perpendicular before entering the evaporation section. In one or more embodiments, the carrier gas contacts the atomizing nozzle by a first path, and the path of the droplets and the second path of the carrier gas are substantially perpendicular to each other before entering the evaporation section of the duct.
[0062] In another embodiment, the path of the droplets and the path of the gaseous carrier stream are substantially parallel as they enter the evaporation section. In one or more embodiments, the path of the droplets and the path of the gaseous carrier stream are substantially parallel to one another as they enter the evaporation section of the duct. In one or more embodiments, the path of the droplets and the path of the carrier gas are substantially parallel to one another as they enter the evaporation section of the duct.
[0063] In some embodiments, the gaseous carrier flow exits the chamber in a direction substantially parallel to gravity. In some embodiments, the gaseous carrier flow exits the chamber in a substantially downward direction. In some embodiments, the gaseous carrier flow exits the chamber in a substantially upward direction.
[0064] Deposition 425 in the honeycomb body. The secondary particles or agglomerates of the primary particles are transported by the gas flow and the secondary particles or agglomerates and / or agglomerates are deposited on the inlet wall surface of the honeycomb body as the gas passes through the honeycomb body. In one or more embodiments, the agglomerates and / or agglomerates are deposited on the porous walls of the plugged honeycomb body. The deposited agglomerates may be located on, in, or both on and in the porous walls. In one or more embodiments, the plugged honeycomb body comprises an inlet channel that is plugged at a distal end of the plugged honeycomb body and an outlet channel that is plugged at a proximal end of the plugged honeycomb body. In one or more embodiments, the agglomerates and / or agglomerates are deposited on, in, or both on and in the walls that define the inlet channels.
[0065] The flow can be driven by a fan, blower or vacuum pump. Additional air can be drawn into the system to achieve the desired flow rate. The desired flow rate can range from 5 to 200 m 3 / hr.
[0066] One exemplary honeycomb body is suitable for use as a gasoline particulate filter (GPF) and has the following non-limiting characteristics: 4.055 inch (10.3 cm) diameter, 5.47 inch (13.9 cm) length, 200 cells per square inch (CPSI) (approximately 31.0 cells / cm 2 ), a wall thickness of 8 mils (203 μm), and an average pore size of 14 μm.
[0067] In one or more embodiments, the average diameter of the secondary particles or agglomerates is in the range of 300 nm to 10 μm, 300 nm to 8 μm, 300 nm to 7 μm, 300 nm to 6 μm, 300 nm to 5 μm, 300 nm to 4 μm, or 300 nm to 3 μm. In certain embodiments, the average diameter of the secondary particles or agglomerates is in the range of 1.5 μm to 3 μm, including about 2 μm. The average diameter of the secondary particles or agglomerates can be measured by scanning electron microscopy.
[0068] In one or more embodiments, the average diameter of the secondary particles or agglomerates is within the range of 300 nm to 10 μm, 300 nm to 8 μm, 300 nm to 7 μm, 300 nm to 6 μm, 300 nm to 5 μm, 300 nm to 4 μm, or 300 nm to 3 μm, including the range of 1.5 μm to 3 μm, and including about 2 μm, and is preferably within the range of about 2:1 to about 67:1, about 2:1 to about 9:1, about 2:1 to about 8:1, about 2:1 to about 7:1, about 2:1 to about 6:1, about 2:1 to about 5:1, about 3:1 to about 10:1, about 3:1 There is a ratio of the average diameter of the secondary particles or agglomerates to the average diameter of the primary particles in the range of about 10:1 to about 20:1, about 9:1, about 3:1 to about 8:1, about 3:1 to about 7:1, about 3:1 to about 6:1, about 3:1 to about 5:1, about 4:1 to about 10:1, about 4:1 to about 9:1, about 4:1 to about 8:1, about 4:1 to about 7:1, about 4:1 to about 6:1, about 4:1 to about 5:1, about 5:1 to about 10:1, about 5:1 to about 9:1, about 5:1 to about 8:1, about 5:1 to about 7:1, or about 5:1 to about 6:1, including about 10:1 to about 20:1.
[0069] In one or more embodiments, depositing the agglomerates onto the porous walls further comprises passing a gaseous carrier stream through the porous walls of the honeycomb body, where the walls of the honeycomb body filter out at least some of the agglomerates by trapping the filtered agglomerates on or in the walls of the honeycomb body. In one or more embodiments, depositing the agglomerates onto the porous walls comprises filtering the agglomerates from the gaseous carrier stream with the porous walls of the plugged honeycomb body.
[0070] Post-treatment 430. Post-treatment may optionally be used to adhere the agglomerates to the honeycomb body and / or to each other. That is, in one or more embodiments, at least some of the agglomerates adhere to the porous walls. In one or more embodiments, the post-treatment includes heating and / or curing the binder according to one or more embodiments, when present. In one or more embodiments, the binder material adheres or attaches the agglomerates to the walls of the honeycomb body. In one or more embodiments, the binder material makes the agglomerates sticky.
[0071] Depending on the binder composition, the curing conditions vary. According to some embodiments, a low temperature cure reaction is utilized, for example at temperatures below 100° C. In some embodiments, the cure can be completed in vehicle exhaust gases having temperatures below 950° C. Calcination is optional and can be carried out at temperatures below 650° C. Exemplary cure conditions are in the temperature range of 40° C. to 200° C. for 10 minutes to 48 hours.
[0072] In one or more embodiments, the agglomerates and / or aggregates thereof are heated after being deposited on the honeycomb body. In one or more embodiments, heating the agglomerates causes the organic components of the binder material to be removed from the deposited agglomerates. In one or more embodiments, heating the agglomerates causes the inorganic components of the binder material to physically bond the agglomerates to the walls of the honeycomb body. In one or more embodiments, heating the agglomerates causes the inorganic components of the binder to form a porous inorganic structure on the porous walls of the honeycomb body. In one or more embodiments, heating the deposited agglomerates burns off or volatilizes the organic components of the binder material from the deposited agglomerates.
[0073] In one aspect, a method for applying a surface treatment to a plugged honeycomb body with porous walls includes mixing particles of an inorganic material with a liquid vehicle and a binder material to generate a liquid-particulate-binder stream; mixing the liquid-particulate-binder stream with an atomizing gas; directing the liquid-particulate-binder stream into an atomizing nozzle, thereby atomizing the particles into liquid-particulate-binder droplets comprised of the liquid vehicle, the binder material, and the particles; transporting the droplets toward the plugged honeycomb body with a gaseous carrier stream, the gaseous carrier stream comprising a carrier gas and an atomizing gas; evaporating substantially all of the liquid vehicle from the droplets to form agglomerates comprised of the particles and the binder material; and depositing the agglomerates on the porous walls of the plugged honeycomb body, the deposited agglomerates being disposed on, in, or both on and in the porous walls.
[0074] In another aspect, a method for forming a honeycomb body includes the steps of: supplying a suspension to a nozzle in fluid communication with a duct comprising an evaporation section, the suspension including an inorganic material, a binder material, and a liquid vehicle, supplying a carrier gas to the duct, contacting the nozzle with the carrier gas, evaporating at least a portion of the liquid vehicle in the evaporation section, thereby forming agglomerates of inorganic material, depositing the agglomerates on walls of the honeycomb body, and bonding the inorganic material to the honeycomb body to produce a porous inorganic material. The porous inorganic material may include primary particles and agglomerates of the primary particles.
[0075] A further aspect is a method for applying an inorganic material to a plugged honeycomb body having a porous wall, the method comprising: supplying a suspension including particles of the inorganic material and a liquid vehicle to a nozzle in fluid communication with a duct having an evaporation section; atomizing the suspension with an atomizing gas to generate droplets; supplying a heated carrier gas; intermixing a gaseous carrier stream including the heated carrier gas with the droplets inside a chamber of the duct to generate a gas-liquid-particulate-binder mixture; evaporating at least a portion of the liquid vehicle from the droplets to form agglomerates of particles, the agglomerates being interspersed in the gaseous carrier stream; and advancing the agglomerates and the gaseous carrier stream into the plugged honeycomb body in fluid communication with the duct such that the gaseous carrier stream passes through the porous walls of the plugged honeycomb body and the walls of the plugged honeycomb body capture the agglomerates, the agglomerates and / or their aggregates being deposited on or in the walls of the honeycomb body.
[0076] Device Examples of apparatus that may be used for the process of depositing inorganic material with a binder on a ceramic honeycomb body are shown in Figures 2-6. Generally, an apparatus suitable for the methods herein includes a duct defining a chamber. The duct may have several sections defining different spaces and chambers. In one or more embodiments, the liquid droplets and the gaseous carrier stream are transported through a duct having an outlet end proximate to the plugged honeycomb body. The duct may include a tapered section for engaging the proximal end of the honeycomb body. The tapered section is advantageous in that fluid convection is enhanced. The duct may be in sealed fluid communication with the plugged honeycomb body during the deposition step. In one or more embodiments, the duct is adiabatic or essentially adiabatic. In some embodiments, the nozzle temperature is adjusted to achieve favorable atomization.
[0077] In some embodiments, a circular cross-section chamber can facilitate keeping the agglomerates entrained in the gaseous carrier flow. In various embodiments, a circular cross-section duct reduces and / or prevents recirculation regions or "dead zones" that may result, for example, from the presence of corners.
[0078] In one or more embodiments, the average temperature of the duct walls is lower than the temperature of the gaseous carrier stream.In one or more embodiments, the average temperature of the duct walls is higher than the temperature of the gaseous carrier stream.
[0079] In the following, devices A-D (Figures 2-3 and 5-6) show generally parallel flows where the path of the droplets and the path of the gaseous carrier stream are substantially parallel as they enter the evaporation section. Device "T" (Figure 4) shows a carrier gas contacting the atomizing nozzle by a first path, where the path of the droplets and a second path of the carrier gas are substantially perpendicular to each other before entering the evaporation section of the duct.
[0080] FIG. 2 shows an apparatus 500 for forming a honeycomb body, apparatus “A”, which includes a duct 551 , a deposition zone 531 , an exit zone 536 , an exit conduit 540 , and a flow driver 545 .
[0081] The duct 551 extends from a first end 550 to a second end 555 that defines a chamber of the duct including a plenum volume 503 at the first end 550 and an evaporation chamber 523 downstream of the plenum volume 503. In one or more embodiments, the duct 551 is essentially adiabatic. That is, the duct 551 may not have an external heat source. The evaporation chamber 523 is defined by an evaporation section 553 of the duct 551, which in this embodiment includes a first section 527 of non-uniform diameter and a second section 529 of substantially uniform diameter. The evaporation section 553 includes an inlet end 521 and an outlet end 525. The first section 527 of non-uniform diameter has a diameter that increases from the inlet end 521 to the uniform diameter section 529, which creates a divergence space for the flow to occupy.
[0082] A carrier gas is supplied by conduit 501 to duct 551, which may have a heat source for generating heated carrier gas 505. The atomizing gas 515 and suspension 510 are separately supplied by individual delivery conduits, such as tubes or pipes, to nozzle 520, which is at the inlet end 521 of evaporation section 553 and in fluid communication with duct 551, and specifically with evaporation chamber 523 in this embodiment. The suspension 510 is atomized in nozzle 520 using atomizing gas 515. In one or more embodiments, suspension 510 includes inorganic material, liquid vehicle, and binder, as defined herein, and is a liquid-particulate-binder stream when supplied to the nozzle. The liquid-particulate-binder stream is atomized by nozzle 520 into liquid-particulate-binder droplets using atomizing gas 515.
[0083] In one or more embodiments, the heated carrier gas 505 flows over a nozzle 520. The nebulizing gas 515 can be heated to produce a heated nebulizing gas. The temperature of the nozzle can be adjusted as desired.
[0084] The outlet flow from the nozzle 520 and the flow of heated carrier gas 505 are both in the "Z" direction as shown in Figure 2. There may be a diffusion zone 522 downstream of the nozzle where at least some intermixing occurs. In this embodiment, the diffusion zone 522 is located within the evaporation chamber 523, but in other embodiments the diffusion zone 522 may be located within the plenum volume 503 depending on the location of the nozzle.
[0085] The outlet flow from the nozzle intermixes with the heated carrier gas 505, thereby producing a gas-liquid-particulate-binder mixture that flows through the chamber of duct 551. Specifically, the gas-liquid-particulate-binder mixture flows through the evaporation chamber 523 of the evaporation section 553 and into a deposition zone 531 at the outlet end 525 of the evaporation section 553. Upon intermixing, the gas-liquid-particulate-binder mixture is heated inside the chamber by the heated carrier gas.
[0086] In this embodiment, the nozzle exit flow and the heated carrier gas enter the evaporation chamber 523 of the evaporation section 553 from substantially the same direction. Within the evaporation chamber 523, substantially all of the liquid vehicle is evaporated from the droplets, thereby forming agglomerates of particle and binder material interspersed in a gaseous carrier flow, which is comprised of the carrier gas and the atomizing gas.
[0087] The deposition zone 531, in fluid communication with the duct 551, contains a plugged ceramic honeycomb body 530, e.g., a wall-flow type particulate filter. The deposition zone 531 has an inner diameter larger than the outer diameter of the ceramic honeycomb body 530. To avoid leakage of the gas transporting the ceramic powder, the ceramic honeycomb body 530 is sealed at the inner diameter of the deposition zone 531, a suitable seal being, for example, an inflatable "inner tube". A pressure gauge marked "PG" measures the pressure difference upstream and downstream of the particulate filter.
[0088] The gas-liquid-particulate-binder mixture flows into the ceramic honeycomb body 530, thereby depositing the inorganic material in suspension on the ceramic honeycomb body. Specifically, the gaseous carrier stream passes through the porous walls of the honeycomb body, and the agglomerates and gaseous carrier stream advance into the honeycomb body such that the walls of the honeycomb body capture the agglomerates, and the agglomerates and / or their aggregates are deposited on or in the walls of the honeycomb body. The inorganic material bonds to the ceramic honeycomb body during post-processing of the ceramic honeycomb body. In some embodiments, the binder material adheres or attaches the agglomerates to the walls of the honeycomb body.
[0089] Downstream of the ceramic honeycomb body 530 is an exit zone 536 that defines an exit chamber 535. A flow driver 545 is downstream of the ceramic honeycomb body 530 and is in fluid communication with the deposition zone 531 and the exit zone 536 by an exit conduit 540. Non-limiting examples of flow drivers are fans, blowers, and vacuum pumps. The aerosolized suspension is dried and deposited on one or more walls of the particulate filter as agglomerates of filtration material, which exist as discrete regions of filtration material or as layers in some portions or in some embodiments, or both, and the agglomerates are composed of primary particles of inorganic material.
[0090] Flow-through embodiments such as device 500 are contemplated for a downward direction, e.g., substantially parallel to the direction of gravity. In other embodiments, the device is configured to direct flow in a substantially upward or vertical direction.
[0091] FIG. 3 shows an apparatus 600 for forming a honeycomb body, apparatus “B”, including a duct 651 , a deposition zone 631 , an exit zone 636 , an exit conduit 640 , and a flow driver 645 .
[0092] The duct 651 extends from a first end 650 to a second end 655 that defines a chamber of the duct including a plenum space 603 at the first end 650 and an evaporation chamber 623 downstream of the plenum space 603. In one or more embodiments, the diameter of the duct 651 that defines the plenum space 603 can be equal to the diameter of an evaporation section 653 of the duct 651 that defines the evaporation chamber 623. In one or more embodiments, the duct 651 is essentially adiabatic. That is, the duct 651 may not have an external heat source. The evaporation chamber 623, in this embodiment, includes a single section 629 of substantially uniform diameter. The evaporation section 653 includes an inlet end 621 and an outlet end 625.
[0093] A carrier gas is supplied by conduit 601 to duct 651, which may have a heat source for generating heated carrier gas 605. Atomization gas 615 and suspension 610 are separately supplied by individual delivery conduits, such as tubes or pipes, to nozzle 620, which is at the inlet end 621 of evaporation section 653 and in fluid communication with duct 651, and specifically, in this embodiment, evaporation chamber 623. Suspension 610 is atomized in nozzle 620 using atomization gas 615. In one or more embodiments, suspension 610 includes inorganic material, liquid vehicle, and binder, as defined herein, and is a liquid-particulate-binder stream when supplied to the nozzle. The liquid-particulate-binder stream is atomized by nozzle 620 into liquid-particulate-binder droplets using atomization gas 615.
[0094] In one or more embodiments, the heated carrier gas 605 flows over a nozzle 620. The atomizing gas 615 can be heated to produce a heated atomizing gas. The temperature of the nozzle can be adjusted as desired.
[0095] The outlet flow from the nozzle 620 and the flow of heated carrier gas 605 are both in the "Z" direction as shown in Figure 3. In certain embodiments, downstream of the nozzle is a diffusion zone 622 where at least some intermixing occurs. In this embodiment, the diffusion zone 622 is located within the evaporation chamber 623, although in other embodiments the diffusion zone may be located within the plenum volume 603 depending on the location of the nozzle.
[0096] The outlet flow from the nozzle intermixes with the heated carrier gas 605, thereby producing a gas-liquid-particulate-binder mixture that flows through the chamber of the duct 651. Specifically, the gas-liquid-particulate-binder mixture flows through the evaporation chamber 623 of the evaporation section 653 and into a deposition zone 631 at the outlet end 625 of the evaporation section 653. Upon intermixing, the gas-liquid-particulate-binder mixture is heated inside the chamber by the heated carrier gas.
[0097] In this embodiment, the nozzle exit flow and the carrier gas enter the evaporation chamber 623 of the evaporation section 653 from substantially the same direction. Within the evaporation chamber 623, substantially all of the liquid vehicle is evaporated from the droplets, thereby forming agglomerates of particle and binder material interspersed in a gaseous carrier flow, which is comprised of the carrier gas and the atomizing gas.
[0098] The deposition zone 631, in fluid communication with the duct 651, contains a plugged ceramic honeycomb body 630, e.g., a wall-flow type particulate filter. The deposition zone 631 has an inner diameter larger than the outer diameter of the ceramic honeycomb body 630. To avoid leakage of the gas transporting the ceramic powder, the ceramic honeycomb body 630 is sealed to the inner diameter of the deposition zone 631, a suitable seal being, for example, an inflatable "inner tube". A pressure gauge labeled "PG" measures the pressure difference upstream and downstream of the particulate filter. The gas-liquid-particulate-binder mixture flows into the ceramic honeycomb body 630, thereby depositing the inorganic material in suspension on the ceramic honeycomb body. Specifically, the gaseous carrier flow passes through the porous walls of the honeycomb body, and the agglomerates and the gaseous carrier flow proceed into the honeycomb body, such that the walls of the honeycomb body capture the agglomerates, and the agglomerates are deposited on or in the walls of the honeycomb body. The inorganic material bonds to the ceramic honeycomb body during post processing of the ceramic honeycomb body, hi some embodiments, the binder material adheres or attaches the agglomerates to the walls of the honeycomb body.
[0099] Downstream of the ceramic honeycomb body 630 is an exit zone 636 that defines an exit chamber 635. A flow driver 645 is downstream of the ceramic honeycomb body 630 and is in fluid communication with the deposition zone 631 and the exit zone 636 by an exit conduit 640. Non-limiting examples of flow drivers are fans, blowers, and vacuum pumps. The aerosolized suspension is dried and deposited on one or more walls of the particulate filter as agglomerates of filtration material, which exist as discrete regions of filtration material or as layers in some portions or in some embodiments, or both, and the agglomerates are composed of primary particles of inorganic material.
[0100] Flow-through embodiments such as device 600 are contemplated for a downward direction, e.g., substantially parallel to the direction of gravity. In other embodiments, the device is configured to direct flow in a substantially upward or vertical direction.
[0101] FIG. 4 shows an apparatus 900 for forming a honeycomb body, apparatus “T”, including a duct 951 , a deposition zone 931 , an exit zone 936 , an exit conduit 940 , and a flow driver 945 .
[0102] The duct 951 extends from a first end 950 including a right cylindrical section 928 to a second end 955, all defining a chamber of the duct comprising a first plenum space 903 at the first end 950, an evaporation chamber 923 downstream of the plenum space 603, and a second plenum space 929 defined by the right cylindrical section 928. In one or more embodiments, the diameter of the duct 951 defining the plenum space 903 can be equal to the diameter of the first inlet location 921 of the evaporation section 953 of the duct 951. In one or more embodiments, the duct 951 is essentially adiabatic. That is, the duct 951 may not have an external heat source. The evaporation chamber 923 is defined by the evaporation section 953 of the duct 951. The evaporation section 953 comprises a first inlet location 921 from the first plenum volume 903, a second inlet location 924 from the second plenum volume 929, and an outlet end 925. In some embodiments, some evaporation may occur within at least a portion of the second plenum volume 929 defined by the right cylindrical section 928.
[0103] A carrier gas is supplied by a conduit 901 in a first path to a duct 951, which may have a heat source 906a for generating a heated primary carrier gas 905a that enters the first plenum space 903 and, optionally, another heated secondary carrier gas 905b that enters the second plenum space 929 by a second path. The atomizing gas 915 and the suspension 910 are separately supplied by respective delivery conduits, such as tubes or pipes, to a nozzle 920, which is in the second plenum space 929 of the right cylindrical section 928 and in fluid communication with an evaporation chamber 923 of the evaporation section 953. The suspension 910 is atomized in the nozzle 920 with the atomizing gas 915. In one or more embodiments, the suspension 910 includes an inorganic material, a liquid vehicle, and a binder, as defined herein, and is a liquid-particulate-binder stream when supplied to the nozzle. The liquid-particulate-binder stream is atomized into liquid-particulate-binder droplets by nozzle 920 using atomizing gas 915 .
[0104] In one or more embodiments, the heated secondary carrier gas 905b flows across a nozzle 920. The temperature of the nozzle may be adjusted as desired.
[0105] The outlet flow from the nozzle 920 and the flow of the heated secondary carrier gas 905b, when present, are both in the "X" direction as shown in Figure 4. The flow of the heated primary carrier gas 905a is in the "Z" direction as shown in Figure 4. There may be a diffusion zone 922 downstream of the nozzle where at least some intermixing occurs. In this embodiment, the diffusion zone 922 is at least partially located within the second plenum volume 929, although in other embodiments the diffusion zone 922 may be located within the evaporation chamber 923 depending on the location of the nozzle.
[0106] The outlet flow from the nozzles intermixes with heated carrier gas 905a and 905b, thereby producing a gas-liquid-particulate-binder mixture that flows through the chamber of duct 951. Specifically, the gas-liquid-particulate-binder mixture flows through evaporation chamber 923 of evaporation section 953 and into deposition zone 931 at the outlet end 925 of evaporation section 953. Upon intermixing, the gas-liquid-particulate-binder mixture is heated inside the chamber by the heated carrier gas.
[0107] In this embodiment, the nozzle exit flow and primary carrier gas 905a enter the evaporation chamber 923 of the evaporation section 953 from a substantially vertical direction. Within the evaporation chamber 923, substantially all of the liquid vehicle is evaporated from the droplets, thereby forming agglomerates of particle and binder material interspersed in a gaseous carrier flow, which is comprised of the carrier gas and the atomizing gas.
[0108] The deposition zone 931, in fluid communication with the duct 951, contains a plugged ceramic honeycomb body 930, e.g., a wall-flow type particulate filter. The deposition zone 931 has an inner diameter larger than the outer diameter of the ceramic honeycomb body 930. To avoid leakage of the gas transporting the ceramic powder, the ceramic honeycomb body 930 is sealed to the inner diameter of the deposition zone 931, a suitable seal being, for example, an inflatable "inner tube". A pressure gauge labeled "PG" measures the pressure difference upstream and downstream of the particulate filter. The gas-liquid-particulate-binder mixture flows into the ceramic honeycomb body 930, thereby depositing the inorganic material in suspension on the ceramic honeycomb body. Specifically, the gaseous carrier flow passes through the porous walls of the honeycomb body, and the agglomerates and the gaseous carrier flow proceed into the honeycomb body, such that the walls of the honeycomb body capture the agglomerates, and the agglomerates are deposited on or in the walls of the honeycomb body. The inorganic material bonds to the ceramic honeycomb body during post processing of the ceramic honeycomb body, hi some embodiments, the binder material adheres or attaches the agglomerates to the walls of the honeycomb body.
[0109] Downstream of the ceramic honeycomb body 930 is an exit zone 936 that defines an exit chamber 935. A flow driver 945 is downstream of the ceramic honeycomb body 930 and is in fluid communication with the deposition zone 931 and the exit zone 936 by an exit conduit 940. Non-limiting examples of flow drivers are fans, blowers, and vacuum pumps. The aerosolized suspension is dried and deposited on one or more walls of the particulate filter as agglomerates of filtration material, which exist as discrete regions of filtration material or as layers in some portions or in some embodiments, or both, and the agglomerates are composed of primary particles of inorganic material.
[0110] The overall flow-through embodiment, such as device 900, is considered to be in a downward direction, e.g., substantially parallel to the direction of gravity. In other embodiments, the device is configured to direct flow in a substantially upward or vertical direction.
[0111] FIG. 5 illustrates an apparatus 700 for forming a honeycomb body, apparatus “C”, which includes a duct 751 , a deposition zone 731 , an exit zone 736 , an exit conduit 740 , and a flow driver 745 .
[0112] The duct 751 extends from a first end 750 to a second end 755 that defines a chamber of the duct including a plenum volume 703 at the first end 750 and an evaporation chamber 723 downstream of the plenum volume 703. In one or more embodiments, the diameter of the duct 751 that defines the plenum volume 703 can be equal to the diameter of the evaporation section 753 at the inlet end 721. In one or more embodiments, the duct 751 is essentially adiabatic. That is, the duct 751 may not have an external heat source. The evaporation chamber 723 is defined by the evaporation section 753 of the duct 751, which in this embodiment includes a first section 727 of non-uniform diameter and a second section 729 of substantially uniform diameter. The evaporation section 753 includes an inlet end 721 and an outlet end 725. The non-uniform diameter first section 727 has a diameter that decreases from the exit end 725 to the uniform diameter section 729 creating a tapered space for the flow as it enters the deposition zone 731 .
[0113] A carrier gas is supplied by conduit 701 to duct 751, which may have a heat source for generating heated carrier gas 705. The atomizing gas 715 and suspension 710 are separately supplied by individual delivery conduits, such as tubes or pipes, to nozzle 720, which is at the inlet end 721 of evaporation section 753 and in fluid communication with duct 751, and specifically, in this embodiment, evaporation chamber 723. The suspension 710 is atomized in nozzle 720 using atomizing gas 715. In one or more embodiments, suspension 710 includes inorganic material, liquid vehicle, and binder, as defined herein, and is a liquid-particulate-binder stream when supplied to the nozzle. The liquid-particulate-binder stream is atomized by nozzle 720 into liquid-particulate-binder droplets using atomizing gas 715.
[0114] In one or more embodiments, the heated carrier gas 705 flows over a nozzle 720. The atomizing gas 715 can be heated to produce a heated atomizing gas. The temperature of the nozzle can be adjusted as desired.
[0115] The outlet flow from the nozzle 720 and the flow of heated carrier gas 705 are both in the "Z" direction as shown in Figure 5. There may be a diffusion zone 722 downstream of the nozzle where at least some intermixing occurs. In this embodiment, the diffusion zone 722 is located within the evaporation chamber 723, but in other embodiments the diffusion zone may be located within the plenum volume 703 depending on the location of the nozzle.
[0116] The outlet flow from the nozzle intermixes with the heated carrier gas 705, thereby producing a gas-liquid-particulate-binder mixture that flows through the chamber of the duct 751. Specifically, the gas-liquid-particulate-binder mixture flows through the evaporation chamber 723 of the evaporation section 753 and into a deposition zone 731 at the outlet end 725 of the evaporation section 753. Upon intermixing, the gas-liquid-particulate-binder mixture is heated inside the chamber by the heated carrier gas.
[0117] In this embodiment, the nozzle exit flow and the heated carrier gas enter the evaporation chamber 723 of the evaporation section 753 from substantially the same direction. Within the evaporation chamber 723, substantially all of the liquid vehicle is evaporated from the droplets, thereby forming agglomerates of particle and binder material interspersed in a gaseous carrier flow, which is comprised of the carrier gas and the atomizing gas.
[0118] The deposition zone 731, in fluid communication with the duct 751, contains a plugged ceramic honeycomb body 730, e.g., a wall-flow type particulate filter. The deposition zone 731 has an inner diameter larger than the outer diameter of the ceramic honeycomb body 730. To avoid leakage of the gas transporting the ceramic powder, the ceramic honeycomb body 730 is sealed to the inner diameter of the deposition zone 731, a suitable seal being, for example, an inflatable "inner tube". A pressure gauge labeled "PG" measures the pressure difference upstream and downstream of the particulate filter. The gas-liquid-particulate-binder mixture flows into the ceramic honeycomb body 730, thereby depositing the inorganic material in suspension on the ceramic honeycomb body. Specifically, the gaseous carrier flow passes through the porous walls of the honeycomb body, and the agglomerates and the gaseous carrier flow proceed into the honeycomb body such that the porous walls of the honeycomb body capture the agglomerates, and the agglomerates and / or their aggregates are deposited on or in the porous walls of the honeycomb body. The inorganic material bonds to the ceramic honeycomb body during post processing of the ceramic honeycomb body, hi some embodiments, the binder material adheres or attaches the agglomerates to the walls of the honeycomb body.
[0119] Downstream of the ceramic honeycomb body 730 is an exit zone 736 that defines an exit chamber 735. A flow driver 745 is downstream of the ceramic honeycomb body 730 and is in fluid communication with the deposition zone 731 and the exit zone 736 by an exit conduit 740. Non-limiting examples of flow drivers are fans, blowers, and vacuum pumps. The atomized suspension droplets are aerosolized, dried, and deposited on one or more walls of the particulate filter as agglomerates of filtration material, which exist as discrete regions of filtration material or as layers in some portions or in some embodiments, or both, and the agglomerates are composed of primary particles of inorganic material.
[0120] Flow-through embodiments such as device 700 are contemplated for a downward direction, e.g., substantially parallel to the direction of gravity. In other embodiments, the device is configured to direct flow in a substantially upward or vertical direction.
[0121] FIG. 6 illustrates an apparatus 800 for forming a honeycomb body, apparatus “D”, which includes a duct 851 , a deposition zone 831 , an exit zone 836 , an exit conduit 840 , and a flow driver 845 .
[0122] The duct 851 extends from a first end 850 to a second end 855 that defines a chamber of the duct including a plenum volume 803 at the first end 850 and an evaporation chamber 823 downstream of the plenum volume 803. In one or more embodiments, the duct 851 is essentially adiabatic. That is, the duct 851 may not have an external heat source. The evaporation chamber 823 is defined by an evaporation section 853 of the duct 851, which in this embodiment includes a first section 827 of non-uniform diameter and a second section 829 of substantially uniform diameter. The evaporation section 853 includes an inlet end 821 and an outlet end 825. The first section 827 of non-uniform diameter has a diameter that decreases from the outlet end 825 to the uniform diameter section 829, creating a tapered space for the flow as it enters the deposition zone 831. In some embodiments, evaporation section 853 is configured to have a single section of substantially uniform diameter, similar to device "B." Alternatively, evaporation section 853 has a non-uniform diameter section that increases from inlet end 821 to the uniform diameter section, similar to device "A."
[0123] A carrier gas is supplied by conduit 801 to duct 851, which may have a heat source for generating heated carrier gas 805. Atomization gas 815 and suspension 810 are separately supplied by individual delivery conduits, such as tubes or pipes, to a number of nozzles 820a, 820b, and 820c, which are in fluid communication with plenum space 803. Each nozzle has an input of atomization gas, e.g., 815a supplies nozzle 820a and 815b supplies nozzle 820b. Each nozzle has an input of suspension, e.g., 810a supplies nozzle 820a and 810b supplies nozzle 820b. Optionally, each nozzle has a supply of heated carrier gas, e.g., 802a supplies nozzle 820a and 802b supplies nozzle 820b. Although the embodiment of FIG. 6 shows three nozzles, in other embodiments, any number of multiple nozzles are used. The suspension 810 is atomized in the nozzle 820 using an atomizing gas 815. In one or more embodiments, the suspension 810 includes an inorganic material, a liquid vehicle, and a binder, as defined herein, and is a liquid-particulate-binder stream when delivered to the nozzle. The liquid-particulate-binder stream is atomized by the nozzle 820 using the atomizing gas 815 into liquid-particulate-binder droplets.
[0124] In one or more embodiments, heated carrier gas 805 and optionally 802a and 802b flow across the nozzles. Atomizing gases 815a and 815b can be heated to generate heated atomized gas. The temperature of the nozzles can be adjusted individually or collectively as desired.
[0125] The flow of heated carrier gas 805 is in the "Z" direction as shown in Figure 6. The exit flows from nozzles 820a, 820b, and 820c may be angled toward the center of duct 851, but upon intermixing with heated carrier gas 805, the exit flows of the nozzles are generally in the "Z" direction. There may be a diffusion zone 822 downstream of the nozzle where at least some intermixing occurs. In this embodiment, diffusion zone 822 is located in plenum volume 803, but in other embodiments, the diffusion zone may be located in evaporation chamber 823 depending on the location of the nozzle.
[0126] The outlet flow from the nozzle intermixes with the heated carrier gas 805, thereby producing a gas-liquid-particulate-binder mixture that flows through the chamber of duct 851. Specifically, the gas-liquid-particulate-binder mixture flows through evaporation chamber 823 of evaporation section 853 and into deposition zone 831 at the outlet end 825 of evaporation section 853. Upon intermixing, the gas-liquid-particulate-binder mixture is heated inside the chamber by the heated carrier gas.
[0127] In this embodiment, the nozzle exit flow and the heated gas enter the evaporation chamber 823 of the evaporation section 853 from substantially the same direction. Within the evaporation chamber 823, substantially all of the liquid vehicle is evaporated from the droplets, thereby forming agglomerates of particle and binder material interspersed in a gaseous carrier flow, which is comprised of the carrier gas and the atomizing gas.
[0128] The deposition zone 831, in fluid communication with the duct 851, contains a plugged ceramic honeycomb body 830, for example a wall-flow particulate filter or "wall-flow filter". The deposition zone 831 has an inner diameter larger than the outer diameter of the ceramic honeycomb body 830. To avoid leakage of the gas transporting the ceramic powder, the ceramic honeycomb body 830 is sealed to the inner diameter of the deposition zone 831, a suitable seal being for example an inflatable "inner tube". A pressure gauge labeled "PG" measures the pressure difference upstream and downstream of the particulate filter. The gas-liquid-particulate-binder mixture flows into the ceramic honeycomb body 830, thereby depositing the inorganic material in suspension on the ceramic honeycomb body. Specifically, the gaseous carrier stream passes through the porous walls of the honeycomb body, and the agglomerates and gaseous carrier stream advance into the honeycomb body such that the porous walls of the honeycomb body capture the agglomerates, and the agglomerates and / or their aggregates are deposited on or in the porous walls of the honeycomb body. The inorganic material bonds to the ceramic honeycomb body during post-processing of the ceramic honeycomb body. In some embodiments, the binder material adheres or attaches the agglomerates to the walls of the honeycomb body.
[0129] Downstream of the ceramic honeycomb body 830 is an exit zone 836 that defines an exit chamber 835. A flow driver 845 is downstream of the ceramic honeycomb body 830 and is in fluid communication with the deposition zone 831 and the exit zone 836 by an exit conduit 840. Non-limiting examples of flow drivers are fans, blowers, and vacuum pumps. The atomized suspension droplets are aerosolized, dried, and deposited on one or more walls of the particulate filter as agglomerates of filtration material, which exist as discrete regions of filtration material or as layers in some portions or in some embodiments, or both, and the agglomerates are composed of primary particles of inorganic material.
[0130] Flow-through embodiments such as device 800 are contemplated in a downward direction, e.g., substantially parallel to the direction of gravity. In other embodiments, the device may be configured to direct flow in a substantially upward or vertical direction.
[0131] General overview of honeycomb bodies The ceramic articles herein include a honeycomb body comprising a porous ceramic honeycomb structure with porous walls having wall surfaces defining a plurality of internal channels.
[0132] In some embodiments, the porous ceramic wall includes a material such as a filtration material, which may include a porous inorganic layer disposed on some portions or, in some embodiments, one or more surfaces of the porous ceramic wall. In some embodiments, the filtration material includes one or more inorganic materials, such as one or more ceramic materials or refractory materials. In some embodiments, the filtration material is disposed on the wall to provide improved filtration efficiency through the wall and both locally at the wall and generally through the honeycomb body, at least during initial use of the honeycomb body as a filter after the honeycomb body is in a clean or regenerated state, such as before significant accumulation of ash and / or soot occurs inside the honeycomb body after extended use of the honeycomb body as a filter.
[0133] In one aspect, the filtration material is present as a portion or in some embodiments a layer disposed on one or more surfaces of the walls of the honeycomb structure. The layer is in some embodiments porous to allow gas flow through the walls. In some embodiments, the layer is present as a continuous coating over at least a portion or the entire surface of one or more walls. In some embodiments of this aspect, the filtration material is a flame-deposited filtration material.
[0134] In another aspect, the filtration material is present as a plurality of discrete regions of filtration material disposed on one or more surfaces of the walls of the honeycomb structure. The filtration material may partially block some of the pores of the porous walls, but still allow gas flow through the walls. In some embodiments of this aspect, the filtration material is an aerosol-deposited filtration material. In some preferred embodiments, the filtration material comprises a plurality of inorganic particle agglomerates of inorganic or ceramic or refractory materials. In some embodiments, the agglomerates are porous, thereby allowing gas to flow through the agglomerates.
[0135] In some embodiments, the honeycomb body comprises a porous ceramic honeycomb body having a first end, a second end, and a plurality of walls having wall surfaces defining a plurality of internal channels. A deposited material, such as a filtration material, which may be a porous inorganic layer in some portions or in some embodiments, is disposed on one or more of the wall surfaces of the honeycomb body. The deposited material, such as a filtration material, which may be a porous inorganic layer, is about 20% to about 95%, or about 25% to about 95%, or about 30% to about 95%, or about 40% to about 95%, or about 45% to about 95%, or about 50% to about 95%, or about 55% to about 95%, or about 60% to about 95%, or about 65% to about 95%, or about 70% to about 95%, or about 75% to about 95%, or about 80% to about 95%, or about 85% to about 95%, about 30% to about 95%, or about 40% to about 95%, or about 45% to about 95%, or about 50% to about 95%, or about 55% to about 95%, or about 60% to about 95%, or about 65% to about 95%, or about 70% to about 95%, or about 75% to about 95%, or about 80% to about 95%, or about 85% to about 95%, or about 20% to about 90%, or about 25% to about 90%, or about 30% to about 90%, or about 40% to about 90%, or about 45% to about 90%, or about 50% to about 90%, or or about 55% to about 90%, or about 60% to about 90%, or about 65% to about 90%, or about 70% to about 90%, or about 75% to about 90%, or about 80% to about 90%, or about 85% to about 90%, or about 20% to about 85%, or about 25% to about 85%, or about 30% to about 85%, or about 40% to about 85%, or about 45% to about 85%, or about 50% to about 85%, or about 55% to about 85%, or about 60% to about 85%, or about 65% to about 85%. %, or about 70% to about 85%, or about 75% to about 85%, or about 80% to about 85%, or about 20% to about 80%, or about 25% to about 80%, or about 30% to about 80%, or about 40% to about 80%, or about 45% to about 80%, or about 50% to about 80%, or about 55% to about 80%, or about 60% to about 80%, or about 65% to about 80%, or about 70% to about 80%, or about 75% to about 80%or a porosity measured by X-ray tomography, the deposited material, such as a filtration material, which may be a porous inorganic layer, has an average thickness of 0.5 μm to 50 μm, or 0.5 μm to 45 μm, or 0.5 μm to 40 μm, or 0.5 μm to 35 μm, or 0.5 μm to 30 μm, or 0.5 μm to 25 μm, or 0.5 μm to 20 μm, or 0.5 μm to 15 μm, or 0.5 μm to 10 μm. Various embodiments of honeycomb bodies and methods for forming such honeycomb bodies are described herein with particular reference to the accompanying drawings.
[0136] The material comprises a filtration material in some embodiments, and in some embodiments, an inorganic filtration material. According to one or more embodiments, the inorganic filtration material provided herein comprises discrete regions and / or discontinuous layers formed from an inlet end to an outlet end including disconnected and discrete patches of material or filtration material, and a binder comprised of primary particles within secondary particles or agglomerates that are substantially spherical. In one or more embodiments, the primary particles are non-spherical. In one or more embodiments, "substantially spherical" refers to agglomerates having a cross-sectional circularity in the range of about 0.8 to about 1 or about 0.9 to about 1, where 1 represents a perfect circle. In one or more embodiments, 75% of the primary particles deposited on the honeycomb body have a circularity of less than 0.8. In one or more embodiments, the secondary particles or agglomerates deposited on the honeycomb body have an average circularity of greater than 0.9, greater than 0.95, greater than 0.96, greater than 0.97, greater than 0.98, or greater than 0.99.
[0137] Circularity can be measured using a scanning electron microscope (SEM). The term "cross-sectional circularity (or simply circularity)" is a value that is expressed using the formula shown below. A circle with a circularity of 1 is a perfect circle.
[0138] Circularity = (4π × cross-sectional area) / (perimeter of cross section) 2 .
[0139] A honeycomb body of one or more embodiments may include a honeycomb structure and a deposited material, such as a filtration material, disposed on one or more walls of the honeycomb structure. In some embodiments, the deposited material, such as a filtration material, is applied to a surface of a wall present within the honeycomb structure, the wall having a surface that defines a plurality of internal channels.
[0140] The internal channels, when present, may have a variety of cross-sectional shapes, such as circles, ovals, triangles, squares, pentagons, hexagons, or a tessellated combination of any of these, and may be arranged in any suitable geometric configuration. The internal channels, when present, may be discrete or intersecting and may extend through the honeycomb body from a first end of the honeycomb body to a second end of the honeycomb body opposite the first end.
[0141] Referring now to FIG. 7, there is shown a honeycomb body 100 according to one or more embodiments shown and described herein. The honeycomb body 100, in embodiments, may comprise a plurality of walls 115 defining a plurality of interior channels 110. The plurality of interior channels 110 and intersecting channel walls 115 extend between a first end 105, which may be an inlet end of the honeycomb body, and a second end 135, which may be an outlet end. The honeycomb body may have one or more channels plugged at one or both of the first end 105 and the second end 135. The pattern of plugged channels in the honeycomb body is not limited. In some embodiments, the pattern of plugged and unplugged channels at one end of the honeycomb body may be a checkerboard pattern, for example, where alternating channels at one end of the honeycomb body are plugged. In some embodiments, a plugged channel at one end of the honeycomb body has a corresponding unplugged channel at the other end, and an unplugged channel at one end of the honeycomb body has a corresponding plugged channel at the other end.
[0142] In one or more embodiments, the honeycomb body may be formed from cordierite, aluminum titanate, enstatite, mullite, forsterite, corundum (SiC), spinel, sapphireline, and periclase. Generally, cordierite has the formula Mg2Al4Si5O 18 In some embodiments, the pore size of the ceramic material, the porosity of the ceramic material, and the pore size distribution of the ceramic material are controlled, for example, by varying the particle size of the ceramic raw materials. Additionally, a pore former can be included in the ceramic batch used to form the honeycomb body.
[0143] In some embodiments, the walls of the honeycomb body may have an average thickness of 25 μm to 250 μm, such as 45 μm to 230 μm, 65 μm to 210 μm, 65 μm to 190 μm, or 85 μm to 170 μm. The walls of the honeycomb body may be described as having a base portion consisting of a bulk portion (also referred to herein as bulk) and a surface portion (also referred to herein as surface). The surface portion of the wall extends into the wall from the surface of the honeycomb body wall towards the bulk portion of the honeycomb body. The surface portion may extend to a depth of 0 to about 10 μm into the base portion of the honeycomb body wall. In some embodiments, the surface portion may extend about 5 μm, about 7 μm, or about 9 μm (i.e., a depth of 0) into the base portion of the wall. The bulk portion of the honeycomb body is equal to the thickness of the wall minus the surface portion. Thus, the bulk portion of the honeycomb body may be determined by the following formula: t total -2t surface (In the formula, t total is the total thickness of the wall, and t surface is the thickness of the wall surface).
[0144] In one or more embodiments, the bulk of the honeycomb body (before any filtration material is applied) has a bulk average pore size of 7 μm to 25 μm, such as 12 μm to 22 μm, or 12 μm to 18 μm. For example, in some embodiments, the bulk of the honeycomb body may have a bulk average pore size of about 10 μm, about 11 μm, about 12 μm, about 13 μm, about 14 μm, about 15 μm, about 16 μm, about 17 μm, about 18 μm, about 19 μm, or about 20 μm. In general, the pore sizes of any given material exist in a statistical distribution. Thus, the term "average pore size" or "d50" (before any filtration material is applied) refers to the length measurement above which 50% of the pores have a pore size and below which the remaining 50% of the pores have a pore size based on the statistical distribution of all pores. Porosity within ceramic bodies can be produced by at least one of the following: (1) inorganic batch material particle size and size distribution, (2) furnace / heat treatment firing time and temperature schedule, (3) furnace atmosphere (e.g., low or high oxygen and / or water content), and (4) pore formers, such as polymers and polymer particles, starch, wood flour, hollow inorganic particles, and / or graphite / carbon particles.
[0145] In certain embodiments, the average pore size (d50) of the bulk of the honeycomb body (before any filtration material is applied) is in the range of 10 μm to about 16 μm, for example 13-14 μm, where d10 refers to the length measurement above which 90% of the pores are sized and below which the remaining 10% of the pores are sized, based on a statistical distribution of all pores, and is about 7 μm. In certain embodiments, d90 refers to the length measurement above which 10% of the pores of the bulk of the honeycomb body (before any filtration material is applied) are sized and below which the remaining 90% of the pores are sized, based on a statistical distribution of all pores, and is about 30 μm. In certain embodiments, the average diameter (D50) of the secondary particles or agglomerates is about 2 μm. In certain embodiments, it has been found that excellent filtration efficiency results and low pressure drop results are obtained when the agglomerate average size D50 and the average wall pore size d50 of the bulk honeycomb body are such that the ratio of the agglomerate average size D50 to the average wall pore size d50 of the bulk honeycomb body is within the range of 5:1 to 16:1. In further particular embodiments, the ratio of the agglomerate average size D50 (before any filtration material is applied) to the average wall pore size d50 of the bulk of the honeycomb body is within the range of 6:1 to 16:1, 7:1 to 16:1, 8:1 to 16:1, 9:1 to 16:1, 10:1 to 16:1, 11:1 to 16:1, or 12:1 to 6:1, providing excellent filtration efficiency results and low pressure drop results.
[0146] In some embodiments, the bulk of the honeycomb body may have a bulk porosity of 50% to 75% as measured by mercury intrusion porosimetry, not taking into account coatings. Other methods for measuring porosity include scanning electron microscopy (SEM) and X-ray tomography, two methods that are particularly useful for measuring surface and bulk porosity independently of one another. In one or more embodiments, the bulk porosity of the honeycomb body may be, for example, in the range of about 50% to about 75%, in the range of about 50% to about 70%, in the range of about 50% to about 65%, in the range of about 50% to about 60%, in the range of about 50% to about 58%, in the range of about 50% to about 56%, or in the range of about 50% to about 54%.
[0147] In one or more embodiments, the surface portion of the honeycomb body has a surface average pore size of from 7 μm to 20 μm, such as from 8 μm to 15 μm, or from 10 μm to 14 μm. For example, in some embodiments, the surface of the honeycomb body may have a surface average pore size of about 8 μm, about 9 μm, about 10 μm, about 11 μm, about 12 μm, about 13 μm, about 14 μm, or about 15 μm.
[0148] In some embodiments, the surface of the honeycomb body may have a surface porosity of 35% or more and 75% or less, prior to application of the filtration material deposit, as measured by mercury intrusion porosimetry, SEM, or X-ray tomography. In one or more embodiments, the surface porosity of the honeycomb body may be less than 65%, such as less than 60%, less than 55%, less than 50%, less than 48%, less than 46%, less than 44%, less than 42%, less than 40%, less than 48%, or less than 36%, etc.
[0149] 8 and 9, a honeycomb body in the form of a particulate filter 200 is shown in schematic form. The particulate filter 200 can be used as a wall-flow filter for filtering particulate matter from an exhaust gas flow 250, such as an exhaust gas flow from a gasoline engine (in this case, the particulate filter 200 is a gasoline particulate filter). The particulate filter 200 generally includes a honeycomb body having a plurality of channels 201 or cells extending between an inlet end 202 and an outlet end 204, defining an overall length La (shown in FIG. 9). The channels 201 of the particulate filter 200 are formed and at least partially defined by a plurality of intersecting channel walls 206 extending from the inlet end 202 to the outlet end 204. The particulate filter 200 may include a skin layer 205 surrounding the plurality of channels 201. This skin layer 205 may be extruded during formation of the channel walls 206, or may be formed as a subsequently applied skin layer, such as by applying a skinning cement to the perimeter portion of the channel in later processing.
[0150] An axial cross section of the particulate filter 200 of FIG. 8 is shown in FIG. 9. In some embodiments, certain channels are designated as inlet channels 208, and certain other channels are designated as outlet channels 210. In some embodiments of the particulate filter 200, at least a first set of channels may be plugged with plugs 212. Generally, the plugs 212 are arranged close to the ends (i.e., inlet or outlet ends) of the channels 201. The plugs are generally arranged in a predefined pattern, such as the checkerboard pattern shown in FIG. 8, with every other channel plugged at its end. As shown in FIG. 9, the inlet channels 208 may be plugged at or near the outlet end 204, and the outlet channels 210 may be plugged at or near the inlet end 202 on the channels that do not correspond to the inlet channels. Thus, each cell may be plugged only at or near one end of the particulate filter.
[0151] 8 generally illustrates a checkerboard plugging pattern, it should be understood that alternative plugging patterns may be used in the porous ceramic honeycomb article. In the embodiments described herein, the particulate filter 200 has a plugging density of up to about 600 channels per square inch (cpsi) (about 93.0 channels / cm 2 For example, in some embodiments, the particulate filter 200 may be formed with a channel density of about 100 cpsi to about 600 cpsi (about 15.5 channels / cm 2 ~ approx. 93.0 channels / cm 2 In some other embodiments, the particulate filter 200 may have a channel density in the range of about 100 cpsi to about 400 cpsi (about 15.5 channels / cm). 2 ~ approx. 62.0 channels / cm 2 ) or even about 200 cpsi to about 300 cpsi (about 31.0 channels / cm 2 ~ approx. 46.5 channels / cm 2 ) may have a channel density in the range of
[0152] In the embodiments described herein, the channel walls 206 of the particulate filter 200 may have a thickness of more than about 4 mils (101.6 μm). For example, in some embodiments, the thickness of the channel walls 206 may be in the range of about 4 mils (about 0.1 mm) up to about 30 mils (762 μm). In some other embodiments, the thickness of the channel walls 206 may be in the range of about 7 mils (177.8 μm) to about 20 mils (508 μm).
[0153] In some embodiments of the particulate filter 200 described herein, the channel walls 206 of the particulate filter 200 may have an uncoated open porosity (i.e., porosity before any coating is applied to the honeycomb body) %P≧35% before application of any coating to the particulate filter 200. In some embodiments, the uncoated open porosity of the channel walls 206 may be such that 40%≦%P≦75%. In other embodiments, the uncoated open porosity of the channel walls 206 may be such that 45%≦%P≦75%, 50%≦%P≦75%, 55%≦%P≦75%, 60%≦%P≦75%, 45%≦%P≦70%, 50%≦%P≦70%, 55%≦%P≦70%, or 60%≦%P≦70%.
[0154] Furthermore, in some embodiments, the channel walls 206 of the particulate filter 200 are formed such that the pore distribution within the channel walls 206 has an average pore size of 30 μm or less before application of any coating (i.e., uncoated). For example, in some embodiments, the average pore size may be 8 μm or more and 30 μm or less. In other embodiments, the average pore size may be 10 μm or more and 30 μm or less. In other embodiments, the average pore size may be 10 μm or more and 25 μm or less. In some embodiments, particulate filters produced with an average pore size greater than about 30 μm have reduced filtration efficiency, while particulate filters produced with an average pore size less than about 8 μm may have difficulty penetrating the pores with a washcoat containing a catalyst. Therefore, in some embodiments, it is desirable to maintain the average pore size of the channel walls within a range of about 8 μm to about 30 μm, such as a range of 10 μm to about 20 μm.
[0155] In one or more embodiments described herein, the honeycomb body of the particulate filter 200 is formed from a metal or ceramic material, such as cordierite, silicon carbide, aluminum oxide, aluminum titanate, or any other ceramic material suitable for use in high-temperature particulate filtration applications. For example, the particulate filter 200 may be formed from cordierite by mixing a batch of ceramic precursor materials that may include building materials suitable for producing ceramic articles that primarily include a cordierite crystalline phase. Building materials suitable for cordierite formation generally include a combination of inorganic components that include talc, a silica-producing source, and an alumina-producing source. The batch composition may additionally include a clay, such as kaolin clay. The cordierite precursor batch composition may include an organic component, such as an organic pore former, which is added to the batch mixture to achieve a desired pore size distribution. For example, the batch composition may include starch that is suitable for use as a pore former and / or other processing aid. Alternatively, the build materials may include one or more cordierite powders and an organic pore former material suitable for forming a sintered cordierite honeycomb structure upon firing.
[0156] The batch composition may additionally include one or more processing aids, such as binders, and a liquid vehicle, such as water or a suitable solvent. Processing aids are added to the batch mixture to plasticize the batch mixture and generally to improve processing, reduce drying time, reduce cracking during firing, and / or help produce desired properties in the honeycomb body. For example, the binder may include an organic binder. Suitable organic binders include water-soluble cellulose ether binders, such as methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose derivatives, hydroxyethyl acrylate, polyvinyl alcohol, and / or any combination thereof. The incorporation of an organic binder into the plasticized batch composition allows the plasticized batch composition to be easily extruded. In some embodiments, the batch composition may include one or more optional forming or processing aids, such as lubricants that aid in the extrusion of the plasticized batch mixture. Exemplary lubricants may include tall oil, sodium stearate, or other suitable lubricants.
[0157] After the batch of ceramic precursor material is mixed with appropriate processing aids, the batch of ceramic precursor material is extruded and dried to form a green honeycomb body having an inlet end and an outlet end with a plurality of channel walls extending between the inlet end and the outlet end. The green honeycomb body is then fired according to a firing schedule suitable for producing a fired honeycomb body. At least a first set of the channels of the fired honeycomb body are then plugged with a ceramic plugging composition in a predefined plugging pattern, and the fired honeycomb body is fired again to ceramify the plugs and secure the plugs within the channels.
[0158] In various embodiments, the honeycomb body is configured to filter particulate matter from a gas stream, such as an exhaust gas stream from a gasoline engine. Thus, the average pore size, porosity, geometry and other design aspects of both the bulk and surface of the honeycomb body are selected with these filtration requirements of the honeycomb body in mind. By way of example and as shown in the embodiment of FIG. 10, the wall 310 of a honeycomb body 300, which may be in the form of a particulate filter as shown in FIGS. 8 and 9, has a filtration material deposit 320 disposed thereon, which in some embodiments is sintered or bonded by heat treatment. The filtration material deposit 320 is deposited on the wall 310 of the honeycomb body 300 and includes particles 325 that help prevent particulate matter, such as soot and / or ash, from leaving the honeycomb body with the gas stream 330 and help prevent the particulate matter from clogging the base portion of the wall 310 of the honeycomb body 300. In this manner, and according to an embodiment, the filtration material deposit 320 can function as the primary filtration component, while the base portion of the honeycomb body can instead be configured to minimize pressure loss, for example, as compared to a honeycomb body that does not include such a filtration material deposit. The filtration material deposit is delivered by an aerosol deposition method as disclosed herein.
[0159] As mentioned above, the material, which may be an inorganic layer in some parts or in some embodiments, on the wall of the honeycomb body is very thin compared to the thickness of the base part of the wall of the honeycomb body. As will be discussed in more detail below, the material, which may be an inorganic layer, on the honeycomb body can be formed by a method that allows the deposited material to be applied to the surface of the wall of the honeycomb body in very thin applications or parts, layers. In embodiments, the average thickness of the deposited area or material, which may be an inorganic layer, on the base part of the wall of the honeycomb body is 0.5 μm to 50 μm, or 0.5 μm to 45 μm, 0.5 μm to 40 μm, or 0.5 μm to 35 μm, or 0.5 μm to 30 μm, 0.5 μm to 25 μm, or 0.5 μm to 20 μm, or 0.5 μm to 15 μm, 0.5 μm to 10 μm.
[0160] As discussed above, the deposited material, which may be an inorganic layer in some embodiments, or in some parts, may be applied to the walls of the honeycomb body by a method that allows the inorganic material, which may be an inorganic layer, to have a small average pore size. This small average pore size allows the material, which may be an inorganic layer, to filter a high percentage of particulates and prevents the particulates from penetrating the honeycomb and settling in the pores of the honeycomb. The small average pore size of the material, which may be an inorganic layer according to embodiments, increases the filtering efficiency of the honeycomb body. In one or more embodiments, the material, which may be an inorganic layer, on the walls of the honeycomb body has an average pore size of 0.1 μm to 5 μm, such as 0.5 μm to 4 μm, or 0.6 μm to 3 μm. For example, in some embodiments, the material, which may be an inorganic layer, on the walls of the honeycomb body may have an average pore size of about 0.5 μm, about 0.6 μm, about 0.7 μm, about 0.8 μm, about 0.9 μm, about 1 μm, about 2 μm, about 3 μm, or about 4 μm.
[0161] The deposited material, which may be an inorganic layer, on the walls of the honeycomb body may in some embodiments cover substantially 100% of the wall surfaces defining the internal channels of the honeycomb body, while in other embodiments the material, which may be an inorganic layer, on the walls of the honeycomb body covers substantially less than 100% of the wall surfaces defining the internal channels of the honeycomb body. For example, in one or more embodiments, the deposited material, which may be an inorganic layer, on the walls of the honeycomb body covers at least 70% of the wall surfaces defining the internal channels of the honeycomb body, covers at least 75% of the wall surfaces defining the internal channels of the honeycomb body, covers at least 80% of the wall surfaces defining the internal channels of the honeycomb body, covers at least 85% of the wall surfaces defining the internal channels of the honeycomb body, covers at least 90% of the wall surfaces defining the internal channels of the honeycomb body, or covers at least 85% of the wall surfaces defining the internal channels of the honeycomb body.
[0162] As described above with reference to Figures 8 and 9, the honeycomb body can have a first end and a second end. The first end and the second end are separated by an axial length. In some embodiments, the filtration material deposit on the walls of the honeycomb body can extend along the entire axial length of the honeycomb body (i.e., along 100% of the axial length). However, in other embodiments, the material, which can be an inorganic layer, on the walls of the honeycomb body extends along at least 60% of the axial length, such as extending along at least 65% of the axial length, extending along at least 70% of the axial length, extending along at least 75% of the axial length, extending along at least 80% of the axial length, extending along at least 85% of the axial length, extending along at least 90% of the axial length, or extending along at least 95% of the axial length.
[0163] In embodiments, the material, which may be portions or in some embodiments an inorganic layer, on the walls of the honeycomb body extends from a first end of the honeycomb body to a second end of the honeycomb body. In some embodiments, the material, which may be an inorganic layer, on the walls of the honeycomb body extends the entire distance from a first surface of the honeycomb body to a second surface of the honeycomb body (i.e., extends along 100% of the distance from the first surface of the honeycomb body to the second surface of the honeycomb body). However, in one or more embodiments, the layer or material, which may be an inorganic layer, on the wall of the honeycomb body extends along 60% of the distance between the first surface of the honeycomb body and the second surface of the honeycomb body, such as extending along 65% of the distance between the first surface of the honeycomb body and the second surface of the honeycomb body, extending along 70% of the distance between the first surface of the honeycomb body and the second surface of the honeycomb body, extending along 75% of the distance between the first surface of the honeycomb body and the second surface of the honeycomb body, extending along 80% of the distance between the first surface of the honeycomb body and the second surface of the honeycomb body, extending along 85% of the distance between the first surface of the honeycomb body and the second surface of the honeycomb body, extending along 90% of the distance between the first surface of the honeycomb body and the second surface of the honeycomb body, or extending along 95% of the distance between the first surface of the honeycomb body and the second surface of the honeycomb body.
[0164] The selection of a honeycomb body having a low pressure drop in combination with a low porosity and low thickness of the filtration material on the honeycomb body according to the embodiment allows the honeycomb body of the embodiment to have a low initial pressure drop when compared to other honeycomb bodies. In the embodiment, the loading amount of the inorganic deposit is in the range of 0.1-30 g / L on the honeycomb body or in the range of 0.3-30 g / L on the honeycomb body, such as in the range of 1-30 g / L on the honeycomb body, or in the range of 3-30 g / L on the honeycomb body, or in the range of 0.1-10 g / L, or in the range of 0.1-5 g / L on the honeycomb body. In other embodiments, the loading amount of the inorganic deposit is in the range of 1-20 g / L on the honeycomb body, such as in the range of 1-10 g / L on the honeycomb body. In certain embodiments, the loading of the inorganic deposit is in the range of 1-9 g / L, 1-8 g / L, 1-7 g / L, 1-8 g / L, 1-5 g / L, 1-4 g / L, 1-3 g / L, 2-10 g / L, 2-9 g / L, 2-8 g / L, 2-7 g / L, 2-6 g / L, 2-5 g / L, 2-4 g / L, 3-10 g / L, 3-9 g / L, 3-8 g / L, 3-7 g / L, 3-6 g / L, 3-5 g / L, 4-10 g / L, 4-9 g / L, 4-8 g / L, 4-7 g / L, or 4-6 g / L on the honeycomb body. In some embodiments, the increase in pressure drop across the honeycomb due to application of the porous layer over the entire honeycomb is less than 20% of that of an uncoated honeycomb. In other embodiments, the increase can be 9% or less, or 8% or less. In other embodiments, the pressure drop increase across the honeycomb body is 7% or less, such as 6% or less. In yet other embodiments, the pressure drop increase across the honeycomb body is 5% or less, such as 4% or less, or 3% or less.
[0165] Without being bound to any particular theory, it is believed that the small pore size in the filter material deposit on the wall of the honeycomb body allows the honeycomb body to have good filtration efficiency even before ash or soot accumulation occurs in the honeycomb body. The filtration efficiency of the honeycomb body is measured herein using the procedure outlined in Tandon et al., 65 CHEMICAL ENGINEERING SCIENCE 4751-60 (2010). As used herein, the initial filtration efficiency of the honeycomb body refers to a new or regenerated honeycomb body that does not contain any measurable soot or ash load. In an embodiment, the initial filtration efficiency (i.e., clean filtration efficiency) of the honeycomb body is 70% or more, such as 80% or more, or 85% or more. In yet another embodiment, the initial filtration efficiency of the honeycomb body is greater than 90%, such as 93% or more, or 95% or more, or 98% or more.
[0166] The material, which in some embodiments is an inorganic filtration material, on the walls of the honeycomb body according to the embodiment is thin, has a certain porosity, and in some embodiments also has good chemical durability and physical stability. The chemical durability and physical stability of the filtration material deposit on the honeycomb body can be determined in embodiments by subjecting the honeycomb body to a test cycle including a burn-off cycle and an aging test, and measuring the initial filtration efficiency before and after the test cycle. For example, one exemplary method for measuring the chemical durability and physical stability of the honeycomb body includes measuring the initial filtration efficiency of the honeycomb body, loading soot on the honeycomb body under simulated operating conditions, burning off the accumulated soot at about 650°C, subjecting the honeycomb body to an aging test at 1050°C and 10% humidity for 12 hours, and measuring the filtration efficiency of the honeycomb body. Multiple soot accumulation and burn-off cycles may be performed. A smaller change in filtration efficiency (ΔFE) from before the test cycle to after the test cycle indicates better chemical durability and physical stability of the filtration material deposit on the honeycomb body. In some embodiments, ΔFE is 5% or less, such as 4% or less, or 3% or less, In other embodiments, ΔFE is 2% or less, or 1% or less.
[0167] In some embodiments, the filtration material deposit on the walls of the honeycomb body may be composed of one or a mixture of ceramic components, such as ceramic components selected from the group consisting of SiO2, Al2O3, MgO, ZrO2, CaO, TiO2, CeO2, Na2O, Pt, Pd, Ag, Cu, Fe, Ni, and mixtures thereof. Thus, the filtration material deposit on the walls of the honeycomb body may include oxide ceramics. As discussed in more detail below, the method for forming the filtration material deposit on the honeycomb body according to the embodiments allows the filtration material composition to be customized for a given application. This may be beneficial because the ceramic components may be combined to match the physical properties, such as the coefficient of thermal expansion (CTE) and Young's modulus, of the honeycomb body, thereby improving the physical stability of the honeycomb body. In some embodiments, the filtration material deposit on the walls of the honeycomb body may include cordierite, aluminum titanate, enstatite, mullite, forsterite, corundum (SiC), spinel, sapphirine, and periclase.
[0168] In some embodiments, the composition of the filtration material deposit on the walls of the honeycomb body is the same as the composition of the honeycomb body, however, in other embodiments, the composition of the filtration material is different from the composition of the walls of the honeycomb body matrix.
[0169] The properties of the filtration material deposit, and therefore the entire honeycomb body, can be attributed to the ability to apply a sparse or thin porous filtration material having a smaller median pore size compared to the host honeycomb body.
[0170] In some embodiments, a method of forming a honeycomb body includes producing or obtaining a mixture or suspension including ceramic precursor materials and a solvent. The ceramic precursor materials of the filtration material precursor include ceramic materials that serve as a source of, for example, SiO2, Al2O3, TiO2, MgO, ZrO2, CaO, CeO2, Na2O, Pt, Pd, Ag, Cu, Fe, Ni, etc.
[0171] In one or more embodiments, the suspension is atomized using an atomizing gas to generate liquid-particulate-binder droplets of liquid vehicle, binder material, and particles that are directed to the honeycomb body, and then the agglomerates formed upon removal or evaporation of the liquid vehicle are deposited on the honeycomb body. In some embodiments, the honeycomb body may have one or more channels plugged at one end, such as a first end of the honeycomb body, during deposition of the aerosol on the honeycomb body. The plugged channels may be removed after deposition of the aerosol in some embodiments. However, in other embodiments, the channels may remain plugged even after deposition of the aerosol. The pattern of plugged channels in the honeycomb body is not limited, and in some embodiments, all of the channels in the honeycomb body may be plugged at one end. In other embodiments, only a portion of the channels in the honeycomb body may be plugged at one end. In such an embodiment, the pattern of plugged and unplugged channels at one end of the honeycomb body is not limited and may be, for example, a checkerboard pattern in which alternating channels at one end of the honeycomb body are plugged. By plugging all or a portion of the channels at one end of the honeycomb body during deposition of the aerosol, the aerosol can be evenly distributed within the channels of the honeycomb body.
[0172] According to one or more embodiments, a binder having high temperature resistance (e.g., greater than 400° C.) is included in the agglomerates and filtration material deposit to improve the integrity of the agglomerates and deposits at the high temperatures encountered in exhaust gas emission treatment systems. In certain embodiments, the filtration material may include about 5-25 wt. % Dowsil™ US-CF-2405 (alkoxy-siloxane resin). The microstructure of the filtration material deposit resembled the as-deposited morphology after various tests described below. Inorganic binders Aremco Ceramabind™ 644A and 830 may also be used in one or more embodiments. The filtration efficiency of all samples was measured using a high flow blowing test (850 Nm 3 / h) was higher than 60%. This test showed that even when exposed to high temperatures encountered in engine exhaust gas streams, binders including organic and inorganic binders bind primary particles together to produce secondary particles (also called agglomerates) that are bound to the filter wall. According to one or more embodiments, silicates (e.g. Na2SiO3), phosphates (e.g. AlPO4, AlH2(PO4)3), hydraulic cements (e.g. calcium aluminate), sols (e.g. mSiO2·nH2O, Al(OH) x (H2O) 6-x ) and other inorganic and organic binders such as metal alkoxides can also be utilized to increase mechanical strength, for example, by a suitable curing process.
[0173] Water-based or alcohol-based methods According to one or more embodiments, a method for aqueous or alcohol-based aerosol deposition of inorganic material onto the porous walls of a plugged honeycomb body is disclosed. The porous walls of the plugged honeycomb body form a plurality of channels within the honeycomb body. In certain embodiments, a liquid-based suspension of inorganic material and binder, after contact with gas flow and heat, passes through a nozzle to provide a stream of aerosol particles before being pumped into the open channels of the honeycomb body. The inorganic material is then deposited onto the porous walls, with some agglomerates or inorganic material penetrating the pores. An offline heat treatment process may be applied to cure the layer, which in some embodiments forms a membrane. According to one or more embodiments, the honeycomb bodies manufactured and described herein, both before and after curing, exhibit significantly higher filtration efficiency and / or better FE / dP tradeoff than uncoated honeycomb body substrate portions.
[0174] 11, according to one or more embodiments, a process 1400 includes steps 1405 of aqueous or alcoholic suspension preparation, 1410 of atomization to generate droplets, 1415 of intermixing the droplets with a gaseous carrier stream, 1420 of evaporation of the liquid vehicle to form agglomerates, 1425 of deposition of material, e.g., agglomerates, on the walls of the wall-flow filter, and optional post-treatment 1430 to bond (e.g., offline curing) the material onto, or into, or both onto and into the porous walls of the honeycomb body. The aerosol deposition method of forming agglomerates with binder can provide high mechanical integrity without any high temperature curing step (e.g., heating to temperatures above 1000° C.), and in some embodiments can provide even higher mechanical integrity after an optional offline curing step, such as a high temperature (e.g., heating to temperatures above 1000° C.) curing step. In one or more embodiments, "offline" refers to a curing process that is performed separately from the aerosol deposition device, such as in a separate device.
[0175] In one or more embodiments, a stable aqueous or alcohol-based inorganic material suspension or slurry is prepared by mixing a powder of an inorganic material (e.g., alumina) with deionized water and an aqueous-based binder. In some embodiments, such a suspension is prepared by diluting a commercially available inorganic suspension (e.g., an aqueous-based alumina suspension with deionized water or an ethanol-based alumina suspension) and then adding an aqueous-based binder. In some embodiments, it may be desirable to add a dispersing agent. The inorganic material is in the form of particles that are spherical, rod-like, flat or irregular with a primary particle size of 30 nm to 500 nm. The concentration of the inorganic material according to one or more embodiments varies within the range of 1% to 20% by weight of the suspension. Exemplary ranges for inorganic materials in weight percent are 1-2%, 1-3%, 1-4%, 1-5%, 1-6%, 1-8%, 1-9%, 1-10%, 1-15%, 1-20%, 2-3%, 2-4%, 2-5%, 2-6%, 2-8%, 2-9%, 2-10%, 2-15%, 2-20%, 3-4%, 3-5%, 3-6%, 3-8%, 3-9%, 3-10%, 3-15%, 3-20%, 4-5%, 4-6%, 4-8%, 4-9%, 4-10%, 4-15%, 4-20%, 5-6%, 5-8%, 5-9%, 5-10%, 5-15%, 5-20%, 10-15%, 10-16%, 10-17%, 10-18%, 10-19%, 10-20%, 15-18%, 15-19%, and 15-20%. In one or more embodiments, the binder comprises an inorganic or organic material. Non-limiting examples of inorganic binders include silica, titania, silicates, aluminates, phosphates, or hydraulic cements. Non-limiting examples of organic binders include silicone resins, polyvinyl alcohol (PVA), or polyethylene glycol (PEG). The concentration of the binder may be in the range of 5% to 100% by mass of the alumina.Exemplary ranges of binder by weight of inorganic material in weight percent are 5-100%, 10-100%, 15-100%, 20-100%, 25-100%, 30-100%, 35-100%, 40-100%, 45-100%, 50-100%, 55-100%, 60-100%, 5-90%, 10-90%, 15-90%, 20-90%, 25-90%, 30-90%, 35-90%, 40-90%, 45-90%, 50-90%, 55-90%. , 60~90%, 5~80%, 10~80%, 15~80%, 20~80%, 25~80%, 30~80%, 35~80%, 40~80%, 45~80%, 50~80%, 55~80%, 60~80%, 5~70%, 10~70%, 15~70%, 20~70%, 25~70%, 30~70%, 35~70%, 40~70%, 45~70%, 50~70%, 55~70%, 60~70%, 5~60%, 10~60%, 15~60%, 20~60 %, 25~60%, 30~60%, 35~60%, 40~60%, 45~60%, 50~60%, 55~60%, 5~50%, 10~50%, 15~50%, 20~50%, 25~50%, 30~50%, 35~50%, 40~50%, 45~50%, 5~40%, 10~40%, 15~40%, 20~40%, 25~40%, 30~40%, 35~40%, 5~30%, 10~30%, 15~30%, 20~30%, 25~30%, 5~2 5%, 10-25%, 15-25%, 20-25%, 1-20%, 2-20%, 3-20%, 4-20%, 5-20%, 6-20%, 7-20%, 8-20%, 9-20%, 10-20%, 1-15%, 2-15%, 3-15%, 4-15%, 5-15%, 6-15%, 7-15%, 8-15%, 9-15%, 10-15%, 1-10%, 2-10%, 3-10%, 4-10%, 5-10%, 6-10%, 7-10% and 8-10%. In one or more embodiments, the mixing is performed mechanically or acoustically. The as-prepared suspension according to some embodiments is stable for at least 1 hour without obvious settling.
[0176] In some embodiments, a tape test may be used to roughly evaluate the effectiveness of different binders and to determine the amount of binder to be added to the suspension. A layer of wet coating of the sample suspension is prepared according to the embodiments described herein and then coated onto one microscope slide using the as-prepared inorganic material suspension. After drying, the coated slide is placed in an oven and heated to a curing temperature for a time ranging from 10 minutes up to 2 hours. The curing temperature and distribution will depend on the binder used. After curing, a piece of regular tape, such as Highland™ transparent tape, is pressed onto the cured coating and then peeled off the coating. According to some embodiments, if particles of inorganic material are observed on the tape, the cohesive strength of the cured suspension is unacceptable. More binder or a different binder can be used and the test can be repeated.
[0177] FIG. 4, discussed above, shows a schematic of a deposition system that can be used for aerosol deposition of an aqueous-based suspension including inorganic materials according to one or more embodiments. In FIG. 4, the suspension is contained in a suspension vessel 902, and liquid pressure is applied and controlled by a gas supply 904. The gas supply 904 is in the form of a cylinder in some embodiments. In one or more embodiments, the pressure is controlled by a digital automatic pressure regulator or a piezo actuator valve. The atomization gas according to one or more embodiments includes nitrogen or air. A first heat source 906a heats the carrier gas 905a entering the first plenum volume 903. A second heat source 906b is placed downstream of the nozzle 920 to heat the suspension 910 to be atomized in the nozzle 920. A third heat source 906c is placed in the evaporation chamber 923, and the nozzle outlet flow and the primary carrier gas 905a enter the evaporation chamber 923 in the evaporation section 953.
[0178] In one or more embodiments, an aqueous or alcohol-based aerosol deposition process and products prepared thereby are provided that provide plugged honeycomb bodies having porous walls and inorganic materials deposited thereon that exhibit significantly higher filtration efficiency and minimal backpressure tradeoffs than honeycomb bodies prepared by other methods. Such honeycomb bodies, in some embodiments, exhibit superior water resistance in certain tests, including vibration tests, vehicle tests, and water resistance tests, as further described below.
[0179] In certain embodiments, a process is provided that includes flowing a liquid suspension of inorganic material (e.g., alumina nanoparticles) in a suspension containing a binder (e.g., a water-soluble silicate binder or an alcohol-soluble alkoxysiloxane binder) through a spray nozzle to provide a stream of aerosol particles that form agglomerates after contact with a dry gas stream. In certain embodiments, the agglomerates are then pumped into the open channels of the plugged honeycomb body on and / or in the surfaces of the porous walls that form the channels. In some embodiments, the agglomerates first contact the surface pores. In one or more embodiments, an offline heat treatment process is utilized for binder curing and deposit strengthening. After deposition and heat treatment, the filter components exhibit improved filtration efficiency or FE / dP tradeoff performance compared to uncoated plugged honeycomb bodies. Plugged honeycomb bodies manufactured according to the methods described herein pass various durability tests, including water resistance tests with heat treatment. Binders that are water-soluble or alcohol-soluble binders or water-compatible or alcohol-compatible binders are used according to one or more embodiments. The process according to one or more embodiments forms a deposit having a closely packed agglomerate microstructure.
[0180] Plugged honeycomb body containing inorganic material An embodiment of the present disclosure relates to a plugged honeycomb body having porous walls and inorganic material deposited on or in, or both on, the porous walls, providing a filtration article configured to filter particulates from an exhaust gas stream. In a particular embodiment, the filtration article has a gasoline particulate filter (GPF) used to remove particulates from a gasoline engine exhaust gas. The exhaust gas to be filtered enters the inlet cells, passes through the cell walls, and exits the filter via the outlet channels. As the gas passes through the filter and then exits the filter, the particulates are trapped on or in the inlet cell walls. According to one or more embodiments, the porous walls of the filtration article having inorganic material deposited on or in, or both on, the porous walls provide improved filtration efficiency and excellent durability, including durability when exposed to water.
[0181] In one or more embodiments, the inorganic material includes fine particles or primary particles of inorganic material (e.g., alumina), fine particle-binder agglomerates (referred to as "agglomerates") consisting of particles and binder material, and aggregates of fine particle-binder agglomerates. In one or more embodiments, "fine particles" or "primary particles" refer to the smallest discrete masses of inorganic material. In one or more embodiments, "agglomerates" refer to masses of primary particles or fine particles and binder, where the primary particles or fine particles are bound by the binder. In one or more embodiments, "agglomerates of fine particle-binder agglomerates" or "aggregates of primary particle-binder agglomerates" (referred to as "agglomerates") refer to clustered masses of individual fine particle-binder agglomerates or primary particle-binder agglomerates that are bound by the binder. In one or more embodiments, a portion of the agglomerates and individual agglomerates, e.g., non-agglomerates, are deposited on the porous walls of the honeycomb filter body. In one or more embodiments, at least a portion of the primary particles or fine particles are present in, on, or both in and on the porous walls as discrete masses that are not part of the agglomerates or agglomerates. In one or more embodiments, at least a portion of the particulate-binder agglomerates or primary particle-binder agglomerates are present in, on, or in and on the porous walls as discrete masses that are not part of an agglomerate.
[0182] In one or more embodiments, the inorganic material in or on or in and on the porous walls of the filtration article in the form of a plugged honeycomb body is present as "clusters" or "chains" of agglomerates and / or aggregates. In some embodiments, the clusters or chains provide an inorganic material morphology that is one or more of finger-like, fibrillar, or spongy, such as a morphology resembling a seawool sponge.
[0183] As discussed herein, according to embodiments, the inorganic material is produced from a suspension of nanoparticles (e.g., inorganic particles, ceramic particles, refractory particles, alumina particles, etc.), a binder (e.g., a silicon-containing binder and / or an aqueous binder), and a liquid vehicle (e.g., alcohol or water). The suspension is delivered to a nozzle that sprays droplets of the suspension with gas flow assistance. The liquid vehicle evaporates from the droplets to form spherical agglomerates of the nanoparticles. The binder functions as one or more of an agglomeration promoter, aggregate promoter, chain promoter, and cluster promoter. Some of the spherical agglomerates are transported to the porous ceramic wall and remain on the surface of the porous ceramic wall (on, in, or across the surface pores present on the wall), or remain in the pores inside the porous ceramic wall (below the surface of the porous ceramic wall), or remain in contact with other pre-deposited agglomerates that are located either in or on the porous ceramic wall to form an agglomerate of spherical agglomerates in or on the porous ceramic wall. The other spherical agglomerates, while being transported towards the honeycomb filter body, contact further other spherical agglomerates to form an agglomerate of spherical agglomerates, where the agglomerates are then transported towards the porous ceramic wall where the agglomerates then reside on the surface of the porous ceramic wall (on, in, or across the surface pores present on the wall), or reside within the pores inside the porous ceramic wall (below the surface of the porous ceramic wall), or contact and reside with other previously deposited agglomerates or agglomerates disposed either in or on the porous ceramic wall to form an agglomerate of spherical agglomerates in or on the porous ceramic wall.
[0184] Thus, according to one or more embodiments, the inorganic deposits consist of individual agglomerates of nanoparticles (e.g., spherical agglomerates of nanoparticles), aggregates of agglomerates, and / or porous clusters or chains of aggregates of spherical agglomerates, where some clusters or chains are disposed within pores in or under the surface of the porous ceramic wall and / or where some clusters are disposed above the surface of the porous ceramic wall. In some embodiments, some of the porous clusters are porous clusters or cluster islands that include exposed aggregates of agglomerates (e.g., spherical agglomerates). In some embodiments, the porous clusters or cluster islands include one or more chains of two or more agglomerates, each chain extending in a substantially outward direction from the porous ceramic wall. In some embodiments, the multiple outwardly extending chains collectively provide a morphology that resembles a member of the group consisting of fingers, tufts, sponges (e.g., sea wool sponges), and fans. In some embodiments, at least one chain includes a free end of the chain that protrudes above the surface of the porous ceramic wall. In some embodiments, the inorganic material on the honeycomb body is present as an inorganic deposit that comprises a network of aggregated spherical agglomerates of inorganic material particles.
[0185] In an embodiment, the loading of inorganic material present on the honeycomb body is in the range of 0.3-30 g / L on the honeycomb body, such as in the range of 1-30 g / L on the honeycomb body, or in the range of 3-30 g / L on the honeycomb body. In another embodiment, the loading of inorganic material is in the range of 1-20 g / L on the honeycomb body, such as in the range of 1-10 g / L on the honeycomb body. In certain embodiments, the loading of inorganic material is in the range of 1-9 g / L, 1-8 g / L, 1-7 g / L, 1-8 g / L, 1-5 g / L, 1-4 g / L, 1-3 g / L, 2-10 g / L, 2-9 g / L, 2-8 g / L, 2-7 g / L, 2-6 g / L, 2-5 g / L, 2-4 g / L, 3-10 g / L, 3-9 g / L, 3-8 g / L, 3-7 g / L, 3-6 g / L, 3-5 g / L, 4-10 g / L, 4-9 g / L, 4-8 g / L, 4-7 g / L, or 4-6 g / L on the honeycomb body. The loading of inorganic material is the mass of the added material in grams divided by the geometric partial volume in liters. The geometric partial volume is based on the outer dimensions of the honeycomb filter body (or the plugged honeycomb body).
[0186] In one or more embodiments, the particles of inorganic material are 2 / g~15m 2 / g, 5m 2 / g~14m 2 / g, 5m 2 / g~13m 2 / g, 5m 2 / g~12m 2 / g, 5m 2 / g~12m 2 / g, or 5m 2 / g~10m 2 / g.
[0187] In one or more embodiments, the inorganic material deposit on the honeycomb body does not include rare earth oxides such as ceria, lanthana, and yttria. In one or more embodiments, the inorganic material does not include a catalyst, for example, an oxidation catalyst such as a platinum group metal (e.g., platinum, palladium, and rhodium) or a selective catalytic reduction catalyst such as a copper, nickel, or iron promoted molecular sieve (e.g., zeolite).
[0188] In one or more embodiments, prior to heat treatment of the honeycomb body including inorganic material on or in or on and in the porous walls, the honeycomb body further includes a water soluble binder, such as a water soluble silicon-containing binder, a water soluble silicate binder (e.g., a metal silicate binder such as sodium silicate), a water soluble aluminate binder (e.g., a metal aluminate binder such as sodium aluminate). In one or more embodiments, the binder is present on the honeycomb body in a range of 5% to 40%, 5% to 35%, 5% to 30%, 5% to 25%, 5% to 20%, 5% to 15%, or 5% to 10% by weight based on the weight of the organic material. In one or more embodiments, the binder or binder material is provided by a precursor binder or precursor binder material. In one or more embodiments, the precursor binder or precursor binder material contains silicon. In one or more embodiments, the silicon-containing precursor binder is a silicone resin, or a siloxane, or an alkali siloxane, or an alkoxy siloxane, or a silicate, such as an alkali silicate or a sodium silicate. In one or more embodiments, the silicon-containing precursor binder is composed of an inorganic component and an organic component. In one or more embodiments, the silicon-containing precursor binder is converted to silica upon application of heat. In one or more embodiments, the silicon-containing precursor binder is composed of an inorganic component and an organic component, and the organic component is driven off and the inorganic component is converted to silica upon application of heat.
[0189] FIG. 31A shows a pressure control system that can be used to control agglomerate size when forming agglomerates that are deposited on a gasoline particulate filter, labeled GPF in FIGS. 31A-31D. In FIG. 31A, a pressure controller is in communication with a delivery conduit, such as a tube or pipe, into which a suspension of primary particles in a liquid is introduced and then flowed to a nozzle. In a separate line, an atomizing gas, which can be any suitable gas, e.g., nitrogen, air, etc., is flowed to the nozzle to atomize the suspension in a suitable nozzle, as described further below. The GPF is placed in an enclosure as shown in FIG. 31A, and gas is flowed into the enclosure from one end while the atomized suspension is directed through the GPF. Heaters H1 and H2 heat the gas flowed from one end of the enclosure, and pressure gauges, labeled PG in FIGS. 31A-31B, measure the pressure upstream and downstream of the GPF. A fan is placed downstream of the GPF in the enclosure as shown in FIG. 31A, connected by a conduit, and the flow rate is monitored by a flow measuring device. According to one or more embodiments, control of the pressure of the suspension delivered to the nozzle can control the agglomerate size formed during the process. The atomized suspension is deposited onto one or more walls of the GPF as a material, such as a filtration material, which may be an inorganic layer made of primary particles formed into agglomerates.
[0190] FIG. 31B shows an alternative system using flow control to control agglomerate size. As shown in FIG. 31B, the flow control includes an injector pump that delivers a suspension of primary particles in a liquid through a conduit to a nozzle as shown. An atomizing gas is circulated through a separate conduit as shown in FIG. 31B, and a nozzle atomizes the suspension, which is delivered to the GPF as shown. Pressure gauges, labeled PG in FIG. 31A-FIG. 31B, measure the pressure upstream and downstream of the GPF. Heaters H1 and H2, which may be resistive heaters or other suitable heaters, heat the gas delivered from a first end of the enclosure containing the GPF. A fan, as shown in FIG. 31A, is connected to a conduit in fluid communication with the enclosure containing the GPF, and a flow monitor, labeled Flow, monitors the flow rate provided by the fan. The atomized suspension is deposited on one or more walls of the GPF as a material, such as a filtration material, which may be an inorganic layer formed of primary particles into agglomerates.
[0191] FIG. 31C shows another embodiment of a system for atomizing a suspension for the purpose of depositing a material on a GPF. Nitrogen gas or other suitable process gas is delivered through a conduit monitored by a pressure regulator, and a flow meter monitors the flow rate to a nozzle. Nitrogen gas or any other suitable process gas is flowed in a separate conduit, and a pressure regulator PR monitors the pressure. A suspension of primary particles in a liquid is delivered to a nozzle, and the flow rate is measured by a flow meter FM. The gas is delivered to an enclosure with a heater as shown upstream of the GPF in the enclosure. A pressure meter measures the pressure upstream and downstream of the GPF. A blower or fan is in fluid communication with the enclosure containing the GPF through a conduit, and a flow meter measures the flow rate in this conduit. The atomized suspension is deposited on one or more walls of the GPF as a material, such as a filtration material, which may be an inorganic layer formed into an agglomerate, consisting of primary particles. It should be understood that in FIG. 31C, the suspension is delivered in a downward direction. The atomized suspension is deposited onto one or more walls of the GPF as a material, such as a filtration material, which may be an inorganic layer composed of primary particles formed into agglomerates.
[0192] In Figure 31D, the system is configured similarly to the system shown in Figure 31C, except that the flow of suspension is delivered upward through the GPF as shown, and a blower connected to the enclosure containing the GPF directs gas downstream of the GPF.
[0193] In one or more embodiments, the inorganic deposit on the honeycomb filter body produces a filtration article that is water resistant. The formulation that delivers the inorganic material of the inorganic deposit includes a hydrophilic base material, an adhesion promoter, and a surfactant. Although the hydrophilic base material in the dispersion example was alumina, the hydrophilic base material can be any metal oxide with similar attributes, alone or in combination with others, including alumina. Enhanced formulations with additional amounts of adhesion promoter and the use of surfactants are provided in the dispersion example.
[0194] Articles manufactured according to embodiments herein are highly water resistant, allowing them to repeatedly withstand harsh water conditions without suffering adverse filtration efficiency (FE) degradation. The use of small molecule dispersants, which can be adhesive, non-adhesive, or a combination of both, when added to the slurry, improves the strength and durability of the applied material. These materials directly affect agglomerate formation such that changes in these components reduce the loading (g / L) required to achieve FE specifications. Such organic additives can affect the morphology of the agglomerates, affecting the particle size distribution as they form, and potentially affecting their pore structure.
[0195] In some embodiments, the addition of small molecule dispersants advantageously promotes the strength and durability of the inorganic deposits and the overall filtration article. The addition of small molecule dispersants allows for reduced material loading while maintaining the desired FE / dP specifications. The addition of small molecule dispersants can promote the structure and uniformity of the agglomerate composition.
[0196] Filtration articles according to embodiments herein are expected to withstand a variety of environmental conditions, such as those encountered in vehicle exhaust systems, including the presence of high velocity gases and condensate (water), without compromising filtration efficiency (FE) by a significant amount (>5%). The slurry / aerosol process is a cost-effective and efficient method of adding inorganic material to a honeycomb filter body, followed by a sintering step, to impart excellent durability.
[0197] According to one or more embodiments, the addition of a binder (Dowsil 2405) to the aerosol mixture or slurry improves the durability of the filtration article. Several materials have been identified that are adhesive and some that are non-adhesive. EXAMPLES
[0198] The embodiments will be further understood by the following non-limiting examples.
[0199] Wall-flow filter. The diameter and length of the wall-flow filter substrate used in the examples were 4.055 inches (about 10.30 cm) and 5.47 inches (about 13.9 cm). The CPSI and wall thickness were 200 (about 31.0 cells / cm 2 ) and 8 mil (about 0.2 mm). The pore size was 14 μm.
[0200] Raw Materials. Unless otherwise specified in the examples, the following raw materials were used: The inorganic material to be deposited was alumina, the atomizing gas was nitrogen, and a binder was present. The carrier gas was either air or nitrogen.
[0201] Raw Material Utilization. Raw material utilization was determined by determining the weight gain of the honeycomb and comparing it to the calculated amount of ceramic put into the process. For example, if the weight gain was equal to the amount of ceramic put into the process, raw material utilization was calculated as 100%, or if the weight gain was only half of the ceramic put into the process, raw material utilization was calculated as 50%.
[0202] In accordance with one or more embodiments, a honeycomb filter body having an inorganic deposit disposed therein to produce a filtration article is characterized according to the following tests, unless otherwise specified or modified in the examples.
[0203] Smoke Filtration Efficiency (FE) A smoke filtration test was used to evaluate the smoke filtration efficiency performance of deposited inorganic materials disposed within a honeycomb filter body.
[0204] Filtration efficiency (in percent) is: FE=(1-C 出口 / C 入口 )·100 where C is the smoke concentration at the exit and entrance sides of the part, respectively.
[0205] Two particle counter units (Lighthouse 2016, USA) are used simultaneously at upstream and downstream positions relative to the items located under the floor of the dilution chamber. A cigarette is lit in the smoke generator to deliver the desired amount of soot particles into the dilution chamber, reaching a certain level (500,000 particles / cm 3 After the concentration was maintained at 0.05 µm, the smoke proceeded into the inlet side of the tunnel. The flow was driven by a blower which carried the soot particles through the tunnel and finally into the wall-flow filter element. Once the concentration upstream of the GPF reached a steady state, the two particle counters were reset and started counting for 60 seconds and the filtration efficiency (FE) was calculated based on the difference in the total number of particles 0.3 µm and above. The pressure drop (dP) measured by pressure gauges located upstream and downstream of the item was also 51 Nm 3 Recorded at a fixed flow rate of 1000 Hz / hr.
[0206] Pre-test CanningDuring pre-test canning, the article is wrapped in a ceramic fiber mat material and then placed in a metal can. The article, mat and can assembly is heated in an oven to 650°C and held at 650°C for a period of time. The mat expands to help hold the article in place within the can. This process is called mat popping because as the mat expands it "pops" inside the can, holding the article in place. The duration of pre-test canning is chosen based on the subsequent tests to be performed.
[0207] Clean out after the test. After a test has been performed, the following steps are completed to achieve a post-test cleanout of the article: The article, mat and can assembly is placed in a 650° C. oven and held at 650° C. for a period of time, typically about 6 hours, so that the soot loaded within the article is burned off of the article.
[0208] Clean Filtration Efficiency As used herein, the "clean filtration efficiency" of a honeycomb body or filtration article refers to a new or regenerated honeycomb body that does not contain any measurable soot loading. In embodiments, the clean filtration efficiency of the honeycomb body or filtration article is 70% or greater, such as 80% or greater, or 85% or greater. In yet other embodiments, the initial filtration efficiency of the honeycomb body or filtration article is greater than 90%, such as 93% or greater, or 95% or greater, or 98% or greater.
[0209] As used herein, the "Clean Filtration Efficiency Test" refers to testing an article as follows.
[0210] After 6 hours of pre-test canning, airflow is provided at a ramp rate by a blower upstream of the article and the clean pressure drop across the filter is measured at room temperature (approximately 25°C) using a differential pressure sensor / gauge. The airflow rate is 25.5 m 3 / h to 356.8m 3 / h in 10 step increments, with the flow rate maintained for 1 minute at each new increment. Each step increment ranged from approximately 8 to 68 m 3 / h. Next, the dose was within 8 mg / m 3 Soot particles with a concentration of 22.5m 3 An air flow with a flow rate of 100000 / h is introduced upstream of the filter for 45 minutes. Soot is produced from a commercial propane burner with a particle size of about 110 nm. The clean filtration efficiency at 30°C is determined by measuring the difference between the number of particulates introduced to the article and the number of particulates exiting the article before and after exposure to the flow conditions. After the clean filtration efficiency is measured, a post-test cleanout is performed for 6 hours.
[0211] Water Exposure Test Several evaluation procedures were utilized to understand the durability of the filtration articles disclosed herein. Analysis of the effect of various intensities of water exposure on honeycomb filter bodies having aerosol-deposited inorganic materials is indicative of the durability of the filtration articles.
[0212] Water absorption test As used herein, "Water Absorption Test" refers to testing an article as follows.
[0213] Water absorption tests were performed to simulate the source of incoming water found in vehicle exhaust lines under floor conditions.
[0214] The article is first measured for a baseline FE / dP measurement by a clean filtration efficiency test.
[0215] The article is then weighed at 75°C to determine the initial weight. The article is then placed skin side down in a petri dish to simulate the underfloor location of the filter in a vehicle exhaust system and submerged in a volume of deionized water for 2 hours. After the part has soaked up the target amount of water, the part is dried at 75°C until completely dry (weight returns to as deposited). The target amount of water may be pre-measured. For example, a nominal 300g of water may be used. In one or more embodiments, there is a water absorption level that can be described as the percentage of the distance along the diameter of the article surface that the water has been absorbed, e.g., 1 / 2 to 3 / 4 of the filter diameter. The article is then dried in a 100°C oven for 5 to 6 hours until the initial weight is reached. The clean filtration efficiency is then measured. To evaluate the clean filtration efficiency, a 8mg / m 3 Soot particles with a concentration of 22.5m 3 An air flow with a flow rate of 100 g / L soot is introduced 45 min upstream of the filter. Soot is generated from a commercial propane burner with a particle size of about 110 nm. The clean filtration efficiency at 30°C is determined by measuring the difference between the number of particulates introduced to the article and the number of particulates exiting the article. After the filtration efficiency is measured, a post-test cleanout is performed for 6 hours. The filtration efficiency at 0 g / L soot is compared before and after the article is exposed to a water absorption test.
[0216] Water Immersion Test Another method for evaluating the durability of filtration articles is the water immersion test, in which the parts are completely submerged in water to mimic the worst case scenario of an exhaust line being submerged under water.
[0217] As used herein, "water immersion test" refers to testing an article as follows.
[0218] The article is first measured for a baseline FE / dP measurement by a clean filtration efficiency test.
[0219] The article is then weighed at 75°C to determine the initial weight. The article, with the inlet end facing down, is slowly immersed in a container of water for a period of time. The amount of water required to completely immerse the article depends on the size of the article. The sample is left in the water for 1 minute, then slowly removed from the water and allowed to sit for 2 hours. The article is weighed. The filter is then dried in an oven at 100°C for 5-6 hours until it reaches its initial weight. Another clean filtration efficiency measurement is performed to evaluate the change in filtration efficiency after exposure to water.
[0220] Water spray test As used herein, "water spray test" refers to testing an article as follows: The article is placed into a can containing a bladder. The bladder is inflated with air to hold the filter in place. The clean pressure drop across the filter is then measured at room temperature (approximately 25°C) using a differential pressure sensor / gauge. The flow rate of exhaust gas upstream of the assembly is 25.5 Nm 3 / h to 356.8Nm 3 / h in 10 step increments. At each new step increment the flow rate was maintained for 1 minute. Each step increment varied from approximately 8 to 68 Nm 3 / h. Then, 21 Nm3 was introduced upstream of the filter for 45 min using a propane burner. 3 / h exhaust flow rate and 8.5 mg / m 3 The filtration efficiency is measured at 30°C using a concentration of 120 nm median particle size soot particles. The particle mass and particle number are measured upstream and downstream of the filter using an AVL microsoot sensor and a TSI Engine Exhaust Particle Sizer (EEPS), respectively. After the filtration efficiency is measured, the article is removed from the can and placed in a 650°C oven and held at 650°C for 9 hours. Thus, the soot loaded in the article has been burned off from the honeycomb.
[0221] The article is weighed at room temperature. The article is exposed to a fine mist or spray of water using a sprayer or atomizer as described in U.S. Pat. No. 7,520,918 until the part is exposed to 15 g / L of water. The article is then dried in an oven using 250° C. for 3 hours. The article and can assembly are then dried at 30° C. and 8.5 mg / m 3 21Nm at 3 The filter is tested for filtration efficiency at 1000 g / L soot / hr and the filtration efficiency at 0 g / L soot is compared to the filtration efficiency measured before the 650° C. heat treatment and atomizer water exposure. A cleanout procedure is then performed on the article in an oven at 650° C. for 12 hours. The filter is then removed from the can and exposed to a fine mist or spray of water using a fogger or atomizer as described in U.S. Pat. No. 7,520,918 until the part is exposed to 15 g / L water. The article is then dried in an oven using 650° C. for 9 hours. The article and can assembly is then dried at 30° C. and 8.5 mg / m 3 21Nm at 3 The filtration efficiency at 0 g / L soot measured after the second atomizer water exposure is compared to the baseline filtration efficiency at 0 g / L soot before the first 650° C. heat treatment and atomizer water exposure.
[0222] High Flow Test As used herein, "High Flow Testing" refers to testing an article as follows.
[0223] The article is first measured for a baseline FE / dP measurement by a clean filtration efficiency test.
[0224] A high flow rate is then introduced into the article. The flow rate of the exhaust gases upstream of the assembly is 85 m 3 / h to 850.8m 3 The flow rate was increased at approximately 25°C over 10 step increments up to 1000 s / h. At each new step increment the flow rate was maintained for 1 min. Each step increment was approximately 85 to 170 m 3 / h. Next, the dose was within 8 mg / m3 Soot particles with a concentration of 22.5m 3 An air flow with a flow rate of 100 g / L / h is introduced upstream of the filter for 45 minutes. Soot is generated from a commercial propane burner with a particle size of about 110 nm. The clean filtration efficiency at 30°C is determined by measuring the difference between the number of particulates introduced to the article and the number of particulates exiting the article before and after exposure to flow conditions. After the filtration efficiency is measured, a post-test cleanout is performed for 6 hours. The filtration efficiency at 0 g / L soot is compared before and after the article is exposed to the high flow test.
[0225] Soot Loaded Pressure Drop Test After 6 hours of pre-test canning, 25.5m 3 / h to 356.8m 3 Soot was loaded into the article using a flow rate of exhaust gas upstream of the assembly that was increased at about 25°C in 10 step increments up to 1000 sq. m / h. At each new step increment the flow rate was maintained for 1 min. Each step increment was approximately 8 to 68 m / h. 3 / h. The soot loading was increased from 0g / L to 3g / L. After the filter was soot loaded, the soot loaded pressure drop across the filter was measured at room temperature (approximately 25°C) using a differential pressure sensor / gauge. After the soot loaded pressure drop was measured, a post test cleanout was performed for 6 hours.
[0226] Low temperature vibration test An object is placed on a shaker table that vibrates in two directions, with a velocity of 706 m / s along the longitudinal and cross-sectional axes. 2 , and vibrated at 200Hz for 2 hours.
[0227] Vehicle Testing The canned article is placed in a vehicle driven under acceleration conditions simulating highway driving followed by a "fuel cut" or reduction in speed. The article is subjected to a short pulse of high temperature and a 1000m 3 / h with a target flow rate of 5 times higher.
[0228] Example 1 Aqueous-based suspensions were prepared using Ceramabind™ 880 binder, Allied 0.3 μm alumina suspension as the inorganic material of the suspension. Ceramabind™ 880, purchased from Aremco, is a water-dispersible high-temperature silicone resin. It cures at 232° C. for 1 hour or at 249° C. for 45 minutes. It has a pH=6.5 and a solids content of 50% by weight. Allied 0.3 μm alumina suspension, purchased from Allied High Tech, has a median particle size of 0.3 μm or 300 nm. It contains 18.2% alumina and 81.8% distilled water by weight. It has a pH=9 and is completely miscible in water. In this example, four diluted alumina suspensions were prepared by diluting the as-received Allied 0.3 μm alumina suspension with deionized (DI) water, followed by the addition of different amounts of Ceramabind™ 880. All four samples had the same alumina concentration of 3%, but different concentrations of binder, 10%, 30%, 50%, and 100% by weight of alumina, respectively. The pH values were measured for each sample as listed in Table 1. The stability of the suspension with 10% binder was acceptable, with the sample showing no clear separation for 1-2 hours. The other suspension samples with more binder had good stability, showing no clear separation for more than 4 hours. The tape test showed that samples with up to 50% binder added did not pass the test, while the sample with 100% binder passed the test. However, the tape test is not considered a conclusive test as to whether the suspension will work in the manufacture of honeycomb filter bodies.
[0229] [Table 1]
[0230] Example 2 An aqueous-based suspension was prepared containing a suspension of BINDZIL 9950 colloidal silica and Sky Spring alumina powder. The binder, BINDZIL 9950 colloidal silica, purchased from AkzoNoble, contains 50% silica in water with colloidal particles in the size range of 10-20 nm. It was prepared at pH=9 and 80 m. 2 SkySpring alpha-alumina powder, purchased from SkySpring Nanomaterials, Inc., has an average alumina particle size of 150 nm and a specific surface area of 10 m 2 / g. In this example, five diluted alumina suspensions were prepared by mixing SkySpring alumina powder with DI water, followed by the addition of different amounts of BINDZIL 9950 colloidal silica. As listed in Table 2, all four samples had the same alumina concentration of 10%, but different concentrations of binder, 20%, 30%, 50%, and 100% by weight of alumina, respectively. The stability of the suspension was good, and the samples did not clearly separate for more than four hours. Tape tests showed that samples with up to 50% binder added did not pass the test, and samples with 100% binder barely passed the test.
[0231] [Table 2]
[0232] Example 3 Ethanol-based aerosol deposition experiments were performed on the same type of wall-flow filter substrate used in Examples 1 and 2.
[0233] 150 nm Al2O3 in ethanol suspension (30 wt% solids, Beijing Dk Nano technology Co. LTD http: / / www.nanoinglobal.com / en / ProductShow.asp?ID=189 ) was diluted to 11% by weight with ethanol (AR, Sinopharm Group Co. LTD). Dowsil 2405 was added as a binder.
[0234] The solution was atomized using a two-phase fluid nozzle (1 / 4J-SS+SU11-SS, Spraying Systems Co.) The atomization gas was nitrogen at 91.5 psi (approximately 631 kPa), and the liquid atomization rate was 18 ml / min.
[0235] The droplets were dried in a deposition chamber as shown in Figure 4. The gas flow and droplets were heated by heaters placed around the chamber. The set temperatures of heat sources 906a, 906b and 906c shown in Figure 4 were 350°C, 350°C and 120°C.
[0236] The flow was driven by a 2518RPM fan (TBR R11Q CL.HP manufactured by Twin city fan (Shanghai) Co. Ltd.). The total flow rate was 21.5Nm 3 / h. Additional air was pumped into the system to achieve the required total flow rate. The final Al2O3 loading was 4.4 g / part. After deposition, the parts were cured at 200 °C for 1 h.
[0237] Filtration efficiency was then measured using 300 nm median tobacco smoke particulates. The upstream concentration was 500,000 particles over 30 seconds. This was measured using a flow rate of 0.1 cfm (approximately 0.17 m3) into a Lighthouse Handheld 3016 particle counter. 3 / h), which equates to approximately 353 particles / cc. Particle counts were tallied for 30 seconds upstream and 30 seconds downstream. The entire test was completed in approximately 1-2 minutes. Air velocity was 51 m / s. 3 / h. The filtration efficiency was calculated based on the reduction in the particle number concentration downstream. The pressure loss was measured at the same flow rate using a differential pressure gauge. The filtration efficiency was 80% and the pressure loss was 195 Pa.
[0238] Example 4 Aqueous-based aerosol deposition experiments on wall-flow filters.
[0239] Two types of Al2O3 aqueous suspensions were used. One suspension was a 0.3 μm alumina suspension from Allied and the other was a 0.15 μm alumina suspension (30 wt.% solids, Beijing DK Nano technology Co. LTD). http: / / www.nanoinglobal.com / en / ProductShow.asp?ID=189 The suspension was diluted with DI water and mixed with a binder to produce the solution composition shown in Table 3.
[0240] The solution was atomized using a two-phase fluid nozzle (1 / 4J-SS+SU11-SS, Spraying Systems Co.). The atomizing gas was nitrogen and the liquid pressure was adjusted to obtain a liquid flow rate of about 10 ml / min, as listed in Table 3. The droplets were dried in a deposition chamber as shown in Figure 1. The gas flow and droplets were heated by heaters placed around the chamber. The set temperatures of heat sources 906a, 906b and 906c shown in Figure 4 were 350°C, 350°C and 300°C. The flow was driven by a 2518RPM fan (TBR R11Q CL.HP, Twin city fan (Shanghai) Co. Ltd.). The total flow rate was 21.5 Nm 3 / h. Additional air was drawn into the system to achieve the required total flow rate.
[0241] After deposition, the parts were cured for 1 hour at the temperatures listed in Table 3. Filtration efficiency was measured using tobacco smoke particulates with a median particle size of 300 nm. The procedure was described above. Comparisons of FE and dP are shown in Figures 12 and 13. All samples had higher filtration efficiency compared to the uncoated honeycomb body. There was little difference before and after curing.
[0242] [Table 3]
[0243] 14A-14D show SEM images of the morphology of alumina agglomerates formed from ethanol-based and aqueous-based suspensions. The aqueous-based process produced agglomerates smaller than 10 μm, similar to the ethanol-based process (e.g., DK-2405-5%). Through adjustments to the batch formulation (e.g., reducing the alumina concentration) and atomization conditions (e.g., reducing the liquid flow rate), the agglomerate size of the aqueous-based samples prepared with the DK binder was controlled, especially those prepared with the DK suspension.
[0244] Example 5 The sodium silicate solution purchased from Sigma-Aldrich is reagent grade and contains about 10.6% Na2O and about 26.5% SiO2. It has a density of 1.39 g / mL and a pH value of 12.9 at 25°C. The alumina suspension ("DK suspension") purchased from Beijing DK Nano technology Co. LTD has a solid concentration of 21.7% and a pH of about 9 and alumina nanoparticles with a size of approximately 150 nm. Seven samples were prepared by mixing 5 g of DK suspension with different amounts of sodium silicate solution as shown in Table 4, followed by vortex mixing at a speed of 3000 rpm for 10 seconds. The resulting suspension was applied onto a glass slide to form a thin layer coating, followed by a heat drying step. Tape tests showed that samples without or containing 5.1% binder did not pass the test, while samples containing 7.7% or more binder passed the test.
[0245] [Table 4]
[0246] Example 6 A series of aqueous-based aerosol deposition experiments were performed on a wall-flow filter. The wall-flow filter had a diameter of 4.055 in. (10.3 cm), a length of 5.47 in. (13.9 cm), and a density of 200 cells per square inch (CPSI) (approximately 31.0 cells / cm). 2), a wall thickness of 8 mil (203 μm), and an average pore size of 14 μm. The same 0.15 μm alumina suspension (21.7 wt. % solids, Beijing DK Nano technology Co. LTD.) was used for each sample shown in Table 5. http: / / www.nanoinglobal.com / en / ProductShow.asp?ID=189 The suspension was diluted with DI water and mixed with a binder to produce the solution composition shown in Table 5.
[0247] The suspension was atomized using a two-phase fluid nozzle (2050 / 70, 1 / 4J-SS+SU11-SS, Spraying Systems Co.) and the atomizing gas was nitrogen. The suspension, as listed in Table 5, was delivered to the nozzle by a syringe pump at a flow rate of 10 ml / min.
[0248] Droplets were generated and dried into alumina agglomerates in the deposition chamber shown in Figure 3. A heat source 606 in the form of an electrical resistive heating tape was placed in the evaporation section 653 before the exit end 625. The drying gas was heated to 220°C by a heat transmitter and the chamber mixture temperature was maintained at 120°C while the chamber surface heating tape was set at 130°C to evaporate the water. The gas flow was driven by a 2518RPM fan (TBR R11Q CL.HP from Twin city fan (Shanghai) Co. Ltd.). The total flow rate was 40Nm 3 / h. Additional air was pumped into the system to achieve the required total flow rate. After deposition, the parts were then thermally treated at different temperatures ranging from 250 °C to 1100 °C for 1 h.
[0249] [Table 5]
[0250] Filtration efficiency was tested using tobacco smoke particulates with a median particle size of 300 nm. The procedure was described above. FE vs. dP and FE vs. loading are shown in Figure 15A and Figure 15B. All samples had higher filtration efficiency compared to uncoated wall-flow filters. There was a difference between samples before and after curing. The pressure drop compensation was comparable to the ethanol-based process at similar filtration efficiency levels.
[0251] A two-stage water-resistance test was performed using a two-stage water spray test to measure the full water-immersion FE / dP performance before and after mist immersion or full water immersion followed by full drying. The water spray test was performed in such a way that the deposited channels faced the mist flow and thus the deposited agglomerates were in direct contact with the water droplets (mist) and suction, keeping the water droplets in the pores due to the capillary forces of the pores. The two-stage water spray test included a first stage with a water uptake of 15-20 g and a second stage with a water uptake of 60-70 g if the first stage test was passed. The full water immersion test was performed by completely immersing the filter in a tank of water for several minutes and the water uptake was at least 300 g for the substrate.
[0252] Figures 15A and 15B show the performance of parts containing sediment from aqueous-based and ethanol-based processes in terms of FE / dP performance and FE as a dependency of sediment loading. Suspension and processing conditions are compared in Table 5. Figure 15A shows similar FE-dP trends for the two processes. Figure 15B shows that at the same sediment loading, the aqueous process gave higher FE values. As an example, at 3 g / L sediment loading, the aqueous-based process yielded 90% FE, while the ethanol-based process yielded 84% FE.
[0253] 16A and 16B show the morphology and size of the alumina agglomerates formed on the surface of the wall-flow filter for the aqueous-based process deposit and the ethanol-based process. It can be seen that the aqueous-based process forms a deposit microstructure of packed spherical agglomerates, some of which partially penetrate into the pores of the honeycomb walls.
[0254] Another difference observed for these particular examples and for these particular process conditions is that the aqueous process resulted in larger agglomerates than the ethanol-based process. As shown in Figure 16B, the agglomerate sizes were 1.72 μm and 1.78 μm for the ethanol-based and aqueous processes, respectively. However, further experimentation with fluid flow (gas and suspension) and nozzle design modifications showed that similar agglomerate sizes could be achieved between the two processes.
[0255] Table 6 lists the FE / dP performance of filters made with different amounts of sodium silicate binder (10%, 20%, and 30% by weight, respectively).
[0256] [Table 6]
[0257] FIG. 16C is a graph showing the agglomerate size distribution for the aqueous-based and ethanol-based examples. The agglomerate sizes were measured using a scanning electron microscope. FIG. 16D is a graph showing the agglomerate cumulative size distribution between the two process embodiments. The data for the ethanol-based process is shown as a dotted line, and the data for the aqueous-based process is shown as a solid line. Table 7 shows further details of the particle size for both processes. The values d10, d50 and d90 refer to the diameter at which 10%, 50% and 90% of the deposited mass of the sample are made up of particles with a diameter less than the stated value.
[0258] [Table 7]
[0259] Figures 17A and 17B show the effect of heat treatment temperature on water resistance. As shown in Table 8, the samples were prepared using the same 5 wt% alumina suspension with 20 wt% sodium silicate binder, except for one sample, L-0411-02. It can be seen that heat treatment at temperatures above 600°C, preferably above 650°C, significantly improves the water resistance of FE performance, preferably with less than 6% FE loss after exposure to one of the water resistance tests (spray-1, spray-2, water immersion). Higher temperature heat treatments resulted in less FE loss after exposure to water tests. For example, after completion of the two-stage spray test and full water immersion test, there was no FE loss for the 1100°C treated filters and a net total loss of 5.9% for the 650°C treated samples. The 425°C treated filters lost 36% net FE after exposure to water immersion. In some embodiments, a porous ceramic honeycomb body comprising an agglomerate of 1-15 wt. % alumina nanoparticles and 5-25 wt. % binder is heat treated by raising the temperature of the alumina nanoparticle-containing honeycomb body to a maximum temperature of 600-1200°C, e.g., 650-1100°C, for a period of 1-24 hours.
[0260] [Table 8]
[0261] The inventors have found that post-deposition heat treatment can reduce FE, dP, or both FE and dP, as shown in Figures 18A and 18B. As shown in Figure 18A, the lower treatment temperatures of the examples in Table 8 caused a smaller decrease in filtration efficiency due to heat treatment (smaller FE loss), e.g., 1100°C treatment reduced the FE value of the filter by 6.3%, and after 650°C treatment, a similar alumina-supported filter suffered a loss of FE of about 2% (two examples in Figure 18A showing a net loss of FE of 2.2% to 2.5%). As shown in FIG. 18B, the lower treatment temperatures of the examples in Table 8 showed an increase in pressure drop across the filter for lower heat treatment temperatures (below 600°C, or in the range of 400-600°C, where FIG. 18B shows two examples for a heat treatment temperature of 425°C), whereas higher heat treatment temperatures resulted in a decrease in pressure drop compared to the as-deposited state, with the examples in FIG. 18B corresponding to 650°C, 910°C, and 1100°C showing a reduction in pressure drop of 10 Pa or more for heat treatment temperatures above 600°C. Thus, the maximum heat treatment temperatures of 600-700°C, preferably 625-675°C, showed a small decrease in FE after heat treatment, as well as an advantageous reduction in pressure drop.
[0262] Figure 19 shows the smoke FE data measured after heat treatment and each durability (e.g. water resistance) test. The water resistance test included three steps: 1) a first water spray test with a water load of 15-20g, 2) a second water spray test with a water load of 60-70g, and 3) a water absorption test with a water load of >300g. The total FE net loss during the test was 1.66% for the 250°C treated filters and 8.74% for the 650°C treated filters. Note that the 250°C treated samples were exposed to 650°C for 10 hours during high temperature canning before the vehicle test and water test, which was to the benefit of the deposit strength and water resistance.
[0263] Example 7 - Morphology of inorganic deposits This example illustrates the morphology of a filtration article, such as a plugged honeycomb body having inorganic material deposited on or in or on and in the porous walls of the plugged honeycomb body, which is achieved by an aerosol deposition process of the inorganic material.
[0264] 4.252" diameter and 4.724" length, 200 CPSI (31.0 cells / cm 2 Ethanol-based aerosol deposition experiments were conducted on a wall-flow filter substrate with a thickness of 1.0 mm (0.2 mm), a wall thickness of 8 mils (approximately 0.2 mm), and an average pore size of 13.5 μm and an average porosity of 55%. The inorganic material was deposited to a loading of 6.95 g / L. A parallel-flow type chamber similar to that shown in FIG. 5 was used with 11% solids alumina (DK-2405), 15% Dow 2405 binder, and a spray nozzle external mixing nozzle (SU1A, 2050 / 7). The liquid flow rate was 24 g / min (8 g / min through each of the three nozzles). The atomizing gas flow rate was 10 Nm through each of the three nozzles. 3 / h, total 30Nm 3 / h. The carrier gas flow rate was 70 Nm 3 / h. Heat transmitter 706a was used to increase the inlet temperature above nozzle 720. The set point of heat transmitter 706a was 230°C to give a measured temperature of approximately 150°C. The first heater 706b was set at 270°C (actually 150°C), the second heater 706c was set at 300°C (actually 155°C), and the third heater 706d was set at 300°C (actually 120°C).
[0265] SEM pictures of the resulting wall-flow filter with aerosol-deposited alumina on the wall-flow filter were obtained as follows.
[0266] FIG. 20 is an SEM photograph of a top view of the inlet region of the inlet channel.
[0267] FIG. 21 is an SEM photograph of a cutaway side view of the inlet region of the inlet channel.
[0268] FIG. 22 is an SEM photograph of a top view of the middle region of the inlet channel.
[0269] FIG. 23 is an SEM photograph of a cut-away side view of the mid-region of the inlet channel.
[0270] FIG. 24 is an SEM photograph of a top view of the exit region of the inlet channel.
[0271] FIG. 25 is an SEM photograph of a cut-away side view of the exit region of the inlet channel.
[0272] FIG. 26 is an SEM photograph of a close-up cut-away side view of the exit region of the inlet channel.
[0273] FIG. 27 is a color-inverted SEM photograph of FIG.
[0274] FIG. 28 is a portion of the SEM photograph of FIG. 27 with aggregate 1500 surrounded by a dashed line.
[0275] FIG. 29 is a schematic diagram of the agglomerates 1502 that form the region of agglomerate 1500 outlined by dashed lines in FIG.
[0276] As best seen in Figures 26, 27 and 28-29, the inorganic material on the porous walls includes fine particles or primary particles of the inorganic material (alumina in this particular example), fine particle-binder agglomerates of particles and binder material, and aggregates of the fine particle-binder agglomerates. The inorganic material in or on or in and on the porous walls of the filtration article in the form of a plugged honeycomb body is present as "clusters" or "chains" of agglomerates and / or aggregates. In some embodiments, the clusters or chains provide an inorganic material morphology that is one or more of finger-shaped, fibril-shaped, or spongy, such as a morphology resembling a seawool sponge. As can be seen, the inorganic material morphology in Figures 26, 27 and 28-29 has a morphology that is spongy with aggregates having a morphology that is one or more of finger-shaped, fibril-shaped, or spongy.
[0277] Examples 8 to 14 In the exemplary process illustrated in the flow chart of FIG. 30 and the apparatus illustrated in FIGS. 31A-31D, the cordierite honeycomb filters used had a diameter of 4.055 inches (10.3 cm) and a length of 5.47 inches (13.9 cm). 2 ) and wall thickness is 200 (approximately 31.0 cells / cm 2 ) and 8 mil (about 0.2 mm). The average pore size was 14 μm.
[0278] Particles with an average primary particle size of 150 nm prepared from Al2O3 were used to generate a suspension using ethanol (30% solids by mass, Beijing Dk Nano technology Co. Ltd. The suspension was diluted to 11% by mass with ethanol (AR, Sinopharm Group Co. LTD). Dowsil™ US-CF-2405 and TnBT were added as binder and curing reaction catalyst. The ratio of binder to Al2O3 was 5% by mass. The ratio of catalyst to binder was 1% by mass.
[0279] The solution was atomized using a two-phase fluid nozzle (1 / 4J-SS+SU11-SS, Spraying systems Co.). The atomization gas was nitrogen at 116 psi (approximately 800 kPa), and the liquid pressure was 78 psi (approximately 540 kPa). The liquid atomization rate was approximately 32 ml / min.
[0280] The droplets were dried in a deposition chamber shown in Figures 31A and 31B. Figure 31A shows the pressure control system utilized in the examples. Figure 31B shows the flow control system not used in the examples. The gas flow and droplets were heated by heaters placed around them, and the set temperatures of zones T1-2 and T1-1 were 350°C and 200°C.
[0281] The flow was driven by a 2518RPM (TBR R11Q CL.HP manufactured by Twin city fan (Shanghai) Co. Ltd.). The total flow rate was 20Nm 3 / h (standard cubic meters per hour). Additional air was drawn into the system to achieve the required total flow rate. Deposition onto the honeycomb filter was carried out for 173 seconds, with a final Al2O3 loading of 5.6 g / L.
[0282] After deposition, the parts were cured within a temperature range of 40°C to 200°C for 10 minutes to 48 hours.
[0283] FIG. 31A shows a schematic of an exemplary embodiment of a deposition system. The components include a solution container, and liquid pressure was applied and controlled by a nitrogen gas cylinder. Atomization gas was supplied by a nitrogen gas cylinder. Further components in FIG. 31A show an atomization nozzle, a deposition chamber; heater 1 and heater 2, and a honeycomb body sample holder. The apparatus further comprises a fan, and sensors, and control components including pressure gauges for the atomization gas and liquid pressure, a differential pressure gauge for monitoring cross GPF pressure loss, a flow meter for monitoring total flow rate, and a control valve.
[0284] FIG. 32 illustrates an exemplary aggregate or agglomerate 1600 morphology according to one or more embodiments. Primary particles 1602 are bonded together to form spherical aggregates or agglomerates 1600. In one or more embodiments, the primary particles 1602 are non-spherical. In some embodiments, the primary particles 1602 are oval and non-spherical. In some embodiments, the primary particles 1602 comprise closed curves that are non-spherical. In some embodiments, the primary particles 1602 comprise multiple lobes. The surface of each aggregate or agglomerate 1600 is rough to provide friction between the aggregate and the aggregate into the pores of the honeycomb. FIGS. 33A-33F illustrate the morphology and distribution of material, which may be an inorganic layer of different depths. The ratio is the distance to the inlet face to the total length of the honeycomb body. The honeycomb body can have a first end and a second end. The first end and the second end are separated by an axial length. The aggregates are deposited from the first end to form a material, which may be an inorganic layer, on the inlet channel walls of the honeycomb body. In some embodiments, the material, which may be an inorganic layer, extends over the entire axial length of the honeycomb body (i.e., extends along 100% of the axial length). In some embodiments, the layer on the walls of the honeycomb body is not uniform, with thicknesses varying from 10% of the axial length, 50% of the axial length, and 90% of the axial length. The material, which may be an inorganic layer, is relatively thin at the inlet end (10% of the axial length from the inlet end) and relatively thick at the outlet end (90% of the axial length from the inlet end). The aggregates or agglomerates 400 plug the surface pores, effectively reducing the pore size.
[0285] The aggregate 400 size distribution and relative pore size distribution from SEM image analysis are listed in Table 9. The average diameter, Q1, Q3 and sample number are listed. The average aggregate size is in the range of about 1 μm to about 3 μm. The average pore size at the end of the channel (90% axial length from the inlet end) was smaller than the average pore size at the inlet (10% axial length from the inlet end). The reason is that the material was thicker and more layers of aggregates formed the pores. The average pore size was less than 2.5 μm, significantly smaller than the average pore size of the honeycomb body, which was 14 μm. The pore size was measured from the SEM image as the distance between two adjacent aggregates on the surface. Since the porous inorganic layer is made by multiple layers of aggregates, the average pore size in three-dimensional measurement should be smaller than the average pore size measured by two-dimensional measurement.
[0286] [Table 9]
[0287] Due to the smaller pore size and thin thickness, Al2O3 provided high filtration efficiency without the cost of high clean pressure drop. Clean pressure drop is the component pressure drop without soot loading. Soot loaded pressure drop can be further improved by mitigating soot deep layer penetration.
[0288] FIG. 34 compares the filtration efficiency progression with soot loading between an uncoated honeycomb body and a honeycomb body coating with an Al2O3 material, which may be an inorganic layer. The filtration efficiency at 0.01 g / L soot loading increased from 78.4% to 97.6%. The simulated laboratory particle number emissions decreased by about an order of magnitude. This was also an order of magnitude lower than the Euro 6 regulations for GDI vehicle emissions. The coating could effectively accelerate the filtration efficiency to 100% and significantly reduce particle emissions. The filtration efficiency of the honeycomb body is measured herein using the procedure outlined in Tandon et al., 65 CHEMICAL ENGINEERING SCIENCE 4751-60 (2010).
[0289] Figure 35 plots clean pressure loss against flow rate. 3 The soot loading pressure drop in Figure 36 shows the improvement with the Al2O3 coating, which reduces the pressure drop by 9% at 3 g / L.
[0290] The process flow shown in Figure 30 was followed. A suspension of Al2O3 (30 wt% solids) with an average primary particle size of 150 nm (Beijing Dk Nano technology Co. Ltd.) was produced in ethanol and stirred for 1 h, after which a diluted suspension was prepared to prevent the settling of the Al2O3 primary particles. The raw material components and contents of Examples 1-7 are listed in Table 10. For Example 8, the crude suspension was directly diluted to 11 wt% solids in ethanol (AR, Sinopharm Group Co. Ltd.).
[0291] During the atomization step, droplets were generated using a two-phase fluid nozzle (1 / 4J-SS+SU11-SS, Spraying systems Co.). A schematic diagram of the deposition process was shown in FIG. 31A. For Examples 8-11, atomization was achieved by a pressure control system. The pressure was supplied by a N2 gas cylinder and adjusted by a pressure regulator. The mixed suspension was delivered by high-pressure nitrogen from a separate line maintained at a pressure of 78 psi (about 540 kPa), while the atomization gas was supplied by a nitrogen supply cylinder at a pressure maintained at 116 psi (about 800 kPa). For Examples 11-14, atomization was achieved by a flow control system using a mass flow controller, and the liquid flow rate was controlled by a syringe pump. The atomization gas was also supplied by a nitrogen cylinder, but was controlled by flow rate instead of pressure. The atomization gas flow rate was fixed at 20 L / min. The mixed suspension was delivered by an injector pump, and the liquid injection rate was fixed at 1.4 ml / min.
[0292] In the drying step, the airflow was heated by heating bands (resistance heaters) in the areas H, H1, and H2 marked in red in FIG. 31A. The temperatures of H1 and H2 were set at 350° C. and 200° C., while the temperature of H was set at 350° C. The atomized droplets were dried in the hot airflow to produce secondary agglomerate particles before the inlet of the honeycomb filter. The diameter and length of the honeycomb filters used in Examples 8-14 were 4.055 inches (about 10.30 cm) and 5.47 inches (about 13.9 cm). The CPSI and wall thickness were 200 (about 31.0 cells / cm). 2 ) and 8 mil (about 0.2 mm). In the deposition step, the flow was driven by a fan in the pressure control system and by a pump in the flow control system. The secondary agglomerate particles were transported by the flow and deposited under the wall of the honeycomb filter to form a good material in the inorganic layer. In the curing step, the curing temperature and time of Examples 9 to 14 are listed in Table 10.
[0293] [Table 10]
[0294] To evaluate the robustness of the inorganic layer, Examples 8 to 14 were subjected to a high flow rate blowing test. The test flow rate was 850 Nm 3 / h, which was much higher than the vehicle exhaust flow rate. The total test time was about 10 minutes, with the highest flow rate lasting for 1 minute. After high flow rate blowing, the FE and pressure drop (dP) at a velocity of 1.7 m / s were measured and listed in Table 11.
[0295] [Table 11]
[0296] The FE of Examples 9-12 was considered to be at a stable value within the measurement error range. The FE of Examples 13 and 14 dropped by about 1 / 4 after the high flow test, but was still at the 60% level. For Comparative Example 8, which does not contain a binder, the FE dropped much more than that of the inorganic layer-friendly material, including the binder example. These examples show that the binder improved the strength of the inorganic layer-friendly material. Comparative Example 8 utilized a curing catalyst and reduced the curing time to 4 hours at room temperature. However, the other binder systems required at least 12 hours of curing time, and the curing temperature was 40°C. For Example 10, the FE drop after the high flow test was only 3%, the same as Example 9. Therefore, a small amount of a suitable catalyst can obviously accelerate the curing speed and did not affect the strength of the material.
[0297] Figures 33A-F are SEM images showing the morphology of the filter wall surface at different depths from the filter inlet. Figure 33A shows Example 9 at 10% depth. Figure 33B shows Example 9 at 50% depth. Figure 33C shows Example 9 at 90% depth. Figure 33D shows Example 9 at 10% depth. Figure 33E shows Example 9 at 50% depth. Figure 33F shows Example 14 at 90% depth.
[0298] 33A-33F show the morphology at different depths from the inlet for Examples 9 and 14 after high flow testing. The material was not a continuous layer, but particles filled the open pores below the surface of the filter. According to one or more embodiments, the material provided herein, which may be an inorganic layer, includes a discontinuous layer formed from the inlet end to the outlet end that includes disconnected and discrete patches of material, and a binder consisting of primary particles within secondary aggregate particles or agglomerates that are substantially spherical. In one or more embodiments, the primary particles are non-spherical. In one or more embodiments, "substantially spherical" refers to agglomerates having a cross-sectional circularity factor in the range of about 0.8 to about 1 or about 0.9 to about 1, where 1 represents a perfect circle.
[0299] The material became thicker with increasing depth from the filter inlet. Comparing the microstructures of Examples 9 and 14, the material containing Dowsil™ US-CF-2405 showed better adhesion than the high temperature inorganic binder 830. The particles present in the surface pores contributed to the FE remaining after high flow rate blowing. The material morphology followed the FE measurements.
[0300] To further verify the mechanical strength of the material containing the binder system, various tests were carried out using Example 11. After high flow testing, the filter was sealed in a can and then placed in a vehicle exhaust pipe (GEELY EmgrandGT, 1.8T GDI). The vehicle was driven on the highway for about 1 hour. After the vehicle test, the filter was calcined in a muffle furnace at 650°C for 5 hours to remove soot.
[0301] Vibration testing (76g, 200Hz, 2h) was performed by fixing the canned filters in a metal box and then placing them on a vibrating bed. The vibration acceleration was a maximum of 76g acceleration and the frequency was 200Hz. The canned filters were vibrated horizontally for 1h and then vertically for another 1h. The filters were treated at 1150°C for 0.5h.
[0302] The tests were performed in the following order: high flow test, canning, first vehicle test, first vibration test, second vibration test, high heat treatment and second vehicle test. FE and dP were measured after each test. FE results remained above 75% with an overall maximum variation of only 7%. After the first vehicle test, the material with the binder was subjected to calcination at 650°C for 5 hours, but the filtration efficiency only decreased by 5%. This result showed that the binder 2405 and the integrity of the material were stable at the high temperatures tested, which are within the range of normal temperatures of vehicle exhaust. The filtration efficiency and pressure loss did not change between the two successive vibration tests. These results showed that the binder improved the mechanical integrity of the material in various tests simulating real use and in the actual vehicle test. For the high temperature treatment, only a filtration decrease of 2% was observed. These results showed the thermal robustness of the material. Overall, materials with appropriate binders could achieve the mechanical strength of advanced materials that could withstand a variety of conditions, such as high flow blowing, excessive G-force vibration, high temperature processing, and actual vehicle engine exhaust processing.
[0303] After various conditions of testing, the material of Example 11 was examined using a scanning electron microscope. The microstructure of the material after use is shown in Figures 38A-C. As can be seen from Figures 38A-C, the material distribution on the wall is substantially similar to that of Examples 9 and 14. As the depth from the filter inlet increases, the material becomes thicker. All open pores below the surface are filled with particles, which resulted in high filtration efficiency of the filter. These examples showed that the use of high temperature binder was an effective way to build a stable material structure.
[0304] Roundness measurement Samples prepared as in Examples 9-14 were examined using a scanning electron microscope. Primary particles and aggregate particles (agglomerates) were measured for circularity. Figure 39 shows primary particles measured by SEM. Primary particles measured were randomly selected from individual particles. Table 12 tabulates the measurement data for 25 particles.
[0305] [Table 12]
[0306] The measured agglomerates are shown in the SEM photograph in Figure 40. The measured agglomerates were randomly selected. Table 13 tabulates the measurement data for 25 agglomerates.
[0307] [Table 13]
[0308] Examples 15 to 18 Binder In one or more embodiments, the aerosol deposited inorganic deposits on the honeycomb filter body produce a filtration article that is water resistant.
[0309] Advantages: The articles produced herein are highly water resistant, allowing them to repeatedly withstand harsh water conditions without suffering from detrimental filtration efficiency degradation. The method of making the formulation is simple and does not involve sophisticated preparation procedures. The article made of honeycomb filter body and inorganic deposit can maintain the original mechanical durability and chemical stability of the underlying honeycomb filter body.
[0310] Test-Binder Example Smoke Filtration Efficiency (FE) - Change 211 particles / cm in the chamber 3 The smoke filtration efficiency performance of Examples 15-18 was altered from that discussed above by using concentrations of 1.0% to 1.2%.
[0311] Water absorption test-modified.
[0312] The water absorption performance of Examples 15-18 was modified from the water absorption test discussed above by using a nominal 50 g of water (instead of a nominal 300 g) for a 5.2 inch by 5 inch (approximately 13.2 cm by 12.7 cm) part.
[0313] Basic water sprayer test.
[0314] Another method for evaluating the durability of filtration articles is the Basic Water Spray Test, which is used to evaluate the effect of water vapor coming from the engine during a cold start of the vehicle while simulating a filter in a close connection position to the engine. The Basic Water Spray Test is a variation of the Water Spray Test discussed above.
[0315] As used herein, "Basic Water Spray Test" refers to testing an article as follows.
[0316] The article is first measured for a baseline FE / dP measurement by the Smoke Filtration Efficiency Test. The article is placed in a 650° C. oven for heat treatment and held at 650° C. for 9 hours.
[0317] The article is weighed at room temperature. The article is placed in a jog on an open box, with the honeycomb body inlet facing the incoming water mist generated by the sprayer. The article is exposed to a fine mist or spray of water using a sprayer or atomizer as described in US Pat. No. 7,520,918. The sprayer and fan are turned on to a certain speed and the water mist is passed over the part long enough to reach a target amount of water on the part (e.g., 70 g). The sample is then dried in an oven at 150° C. until it reaches its original weight. Another FE / dP measurement is performed to evaluate the change in filtration efficiency after exposure to water.
[0318] According to one or more embodiments, honeycomb bodies with inorganic materials deposited thereon exhibit improved water resistance as a result of high binder loading. In the examples and according to one or more embodiments, improved resistance to water exposure refers to cases where there is a 5% or less decrease in observed clean PN FE performance. In one or more embodiments, due to the inherent hydrophobicity of the selected binder, increased binder loading provides the added benefit of improved resistance to water while maintaining a viable manufacturing process that provides a sprayable suspension. The suspension formulations described according to one or more embodiments are atomized during an aerosol deposition process to produce a product with high temperature tolerance and structural stability.
[0319] As shown in FIG. 41 and in the Examples, a correlation between the amount of binder added to the suspension and the water resistance of honeycomb bodies comprising aerosol-deposited inorganic material is demonstrated, with the filtration articles retaining a high percentage of filtration efficiency after exposure to the basal water spray test. In other words, the filtration efficiency of the filtration articles produced in accordance with one or more embodiments is maintained after exposure to water. In one or more embodiments, the decrease in filtration efficiency of the honeycomb body is less than 1%, less than 2%, less than 3%, less than 4%, less than 5%, less than 6%, less than 7%, less than 8%, less than 9%, or less than 10% below the filtration efficiency of the honeycomb body prior to water exposure. According to embodiments, the average particle size in the range of 150 nm to 500 nm and the average particle size in the range of 4 m 2 / g~15m 2 By increasing the amount of binder for inorganic materials with surface areas in the range of 1 / g, the inorganic material layer has been shown to be more resilient to water exposure as indicated by a reduced decrease in the filtration efficiency of the honeycomb body compared to the filtration efficiency of the honeycomb body before water exposure.
[0320] Example 15 A high purity alpha alumina (>99%) suspension was obtained from Beijing DK Nano technology Co. LTD. The average particle size of the alumina by SEM was 150 nm. A scanning electron microscopy (SEM) image of the alumina in the as-received suspension is shown in FIG. 42. The as-received suspension contained about 20 wt% alumina dispersed in analytical grade ethanol (AR, Sinopharm Group Co. LTD). An example composition is as follows: The suspended 150 nm median particle size alumina raw powder was 20 wt% based on the total weight of the suspension in analytical grade ethanol (>99.7%). The solvent content (wt% based on the total suspension) was 76 wt%. The solution contained other additives in an amount of about 3 wt%. The alumina suspension was then further diluted with ethanol to 11 wt% alumina. There was 15 wt% Dowsil 2405 binder based on the total weight of alumina in the diluted suspension.
[0321] A silicone resin named Dowsil 2405 (dimethylsiloxane and methyl and n-octyl silsesquioxanes, methoxy terminated, available from DOW) was added to the suspension formulation based on the alumina in suspension. The amount of binder used was based on the actual mass of the area produced by the primary particle size used, with a ratio of 20:3 for 150 nm, designated as "high binder loading" according to one or more embodiments.
[0322] After mechanically stirring the alumina, ethanol and binder mixture to obtain a uniform suspension, a multi-step aerosol deposition process was performed to deposit the desired inorganic layer on the honeycomb filter walls. The aerosol deposition process was performed as follows: A t-chamber was used with a single nozzle. Heating bands were used around the chamber body in the upper cone section and deposition section.
[0323] During the atomization step, aerosol droplets were generated using a two-phase fluid nozzle (PF 1250+PA 64, Spraying systems Co.). The atomization gas was supplied by a nitrogen cylinder and controlled at 5 Nm by a gas mass flow controller. 3 The mixed suspension was delivered by an injector pump, and the liquid injection rate was fixed at 10 ml / min.
[0324] In the drying step, the airflow provided by the blower fan was sucked into the system through the top inlet and heated by both the cone section at the inlet and the heating bands wrapped around the body of the deposition chamber. The temperatures of the cone section and the deposition body were set at 350°C and 120°C, respectively. The atomized droplets were dried in the hot airflow to generate secondary agglomerate particles in front of the inlet of the honeycomb filter. In the deposition step, the secondary agglomerates were transported by the flow and deposited under the wall of the honeycomb filter to form a layer.
[0325] The honeycomb filter bodies tested had the following characteristics: 4.055 inch (13.208 cm) diameter, 5.47 inch (13.9 cm) length, 200 cells per square inch (CPSI) (approximately 31.0 cells / cm 2 ), a wall thickness of 8 mils (203 μm), and an average pore size of 13.5 μm. The average honeycomb filter body porosity was 55%. TIFF0007660500000014.tif70114 Example 16 Referring to Figures 43A-B and Table 14, it can be seen that the d50 of the agglomerates shifted towards larger size agglomerates (from 1.47 μm to 1.89 μm) as the binder content increased. When the suspension was deposited on the surface of the porous walls of the honeycomb body or inside the pores, the agglomerates tended to form chain-like structures. The addition of more binder affected the characteristics of the dried agglomerates produced by the process as well as the nature and strength of the interparticle interactions.
[0326] [Table 14]
[0327] Example 17 Reference is now made to Figure 44, which is a graph of smoke filtration efficiency versus pressure drop for wall-flow filters having alumina deposited thereon at different binder loadings, and a trend is observed as the binder loading is increased. As the binder level in the suspension increases, there is a tendency for the filtration efficiency versus pressure drop to plateau. This makes it more difficult to increase the filtration efficiency compared to low binder loading formulations.
[0328] A comparison of the characteristics of suspensions with 5% and 15% binder levels in terms of viscosity versus shear rate and surface tension versus temperature showed that increasing the binder amount had negligible effect on these suspension properties. Therefore, increasing the binder amount would not be expected to have a detrimental effect on the aerosol deposition process.
[0329] Example 18 The effect of water testing on inorganic layer structure SEM images of the sample containing 5% binder loading were taken before and after the water absorption test (50 g). Figure 45A and Figure 45B are top-view images of the honeycomb porous channel walls at 50% depth. Figure 45A shows the inorganic material structure before contact with water, in which the inorganic material appears uniformly distributed around the pores. After contact with water, the inorganic material showed a more exposed surface, suggesting that the agglomerates had moved from their original positions, as shown in Figure 45B.
[0330] Figures 46A and 46B show the inorganic material morphology before and after the basic water spray test (70 g) for the sample with 15 wt% binder. The 15 wt% binder resulted in improved inorganic material integrity to water, as indicated by a reduction in exposed open porosity. The inorganic material structure remained relatively intact.
[0331] The performance of the honeycomb filter body containing the aerosol-deposited inorganic material after water absorption test (50 g) was evaluated based on the clean filtration efficiency test at different soot loading levels, as shown in Figure 47. Both the original binder (5 wt%) part and the high binder loading (15 wt%) part showed similar starting filtration efficiency. As shown in Figure 48, the article containing 15 wt% binder showed better water resistance with FE drop of within 1% at 0 g / L soot loading, while the 5 wt% binder part suffered a drop in FE of more than 10%.
[0332] A basic water spray test was also conducted comparing 5 wt% and 15 wt% binders. The smoke FE reduction is shown in Figures 49 and 50. For the article made with the 5 wt% binder, the FE reduced from 95.4% as received at 0 g / L soot loading to 87% final with the addition of 15 g / L water loading, resulting in an approximately 10% FE reduction. For the article with the 15 wt% binder, the FE reduced from 91.7% as received at 0 g / L soot loading to 90% final with the addition of the same water loading, resulting in only a 2% FE reduction. A comparison of the FE reduction after the basic spray test with the two formulations is shown in Figure 51.
[0333] Test - Dispersant Example 19. According to the method described above.
[0334] Example 19 Dispersant The effect of different dispersants was analyzed by testing various slurries for aerosol deposition.
[0335] The underlying wall-flow filter had the following characteristics: 5.2 inch (13.208 cm) diameter, 5.07 inch (12.7 cm) length, 200 cells per square inch (CPSI) (approximately 31.0 cells / cm 2 ), a wall thickness of 8 mils (203 μm), and an average pore size of 13.5 μm.
[0336] The following alumina sources were tested: AL-022719-3-4400, AL-022719-1.5-4400-1.5-TEA, AL-022719-1.5-4400-1.5-TIPA, AL-022719-3.0 M600, as received DK-11-15-190228-01. TEA is triethanolamine. TIPA is triisopropanolamine. M600 is Jeffamine 600 (molecular weight) monoamine. References to "1.5" refer to 1.5% addition to the slurry and references to "3.0" refer to 3.0% addition to the slurry. Table 15 outlines the equipment and operating parameters.
[0337] [Table 15]
[0338] References to the "heat transmitter" are to the temperature of the preheated carrier gas entering the duct. The temperature values in Table 15 shown were based on measurements and were not set points to obtain these temperatures.
[0339] The slurry was sprayed according to Table 15. Filtration articles were produced by depositing alumina into an underlying wall-flow filter. Table 16 lists the deposition time (sec), loading (g / L), smoke filtration efficiency, material utilization (MU), pressure drop (Pa), and efficiency (smoke FE divided by loading).
[0340] [Table 16]
[0341] The final smoke FE was targeted to be approximately 85% for all conditions. During the experiments, it was found that the loading to achieve approximately 85% FE varied depending on the slurry composition.
[0342] FIG. 52 is a graph of smoke FE versus pressure drop, showing the change in pressure drop tradeoff depending on the slurry composition.
[0343] FIG. 53 is a graph of loading (g / L) versus pressure drop and also shows the variation in pressure drop tradeoff depending on the slurry composition.
[0344] FIG. 54 is a graph of efficiency versus deposition time (seconds) and again shows the change in pressure drop tradeoff depending on the slurry composition.
[0345] Table 17 shows the results of the water absorption test.
[0346] [Table 17]
[0347] In Table 17, "FE decrease @ 0 g / L [%]" indicates the change in FE before and after the water test.
[0348] The addition of organic dispersants affects the texture and morphology of the agglomerates and agglomerate aggregates as the organic dispersants are deposited into the monolith, thus affecting the FE and dP.
[0349] 55A-C and 56A-C show SEM images of siloxane-alumina agglomerates spray dried using PEG-PPG-PEG dispersion, where PEG is polyethylene glycol and PPG is polypropylene glycol. 55A-A are at 1K magnification, 55B-B are at 10K magnification, and 55C-C are at 25K magnification. Agglomerates prepared with 3 wt% copolymer in the slurry appear to be finer than agglomerates prepared with 1 wt% copolymer in the slurry. Thus, a polyethylene-polypropylene glycol triblock copolymer (4400 g / mol) can improve the fineness and uniformity of the siloxane-alumina agglomerates. Filters containing agglomerates prepared using such copolymers were shown to lose less than 5% of the baseline FE after various durability tests.
[0350] Figures 57-60 show SEM images of cross-sections of unmilled A1000SGD agglomerates using various dispersants. Varying the organic dispersant changes the resulting texture of the agglomerates. Figure 57 shows a PEG-PPG-PEG triblock copolymer (4400) dispersion at 1% by weight in the slurry. Figure 58 shows a PEG-PPG-PEG triblock copolymer (4400) dispersion at 3% by weight in the slurry. Figure 59 shows a polyoxypropylene diamine (D230) dispersion at 3% by weight in the slurry. Figure 60 shows a polyethylene glycol (PEG-400) dispersion at 3% by weight in the slurry. The dispersant appears to affect the morphology of the agglomerates.
[0351] Figures 61A-61B, 62A-62B, and 63A-63B show SEM images of siloxane-alumina agglomerates spray dried with various dispersants. Figures 61A-61B show siloxane-alumina agglomerates spray dried with a combination of PEG-PPG-PEG dispersion (1.5% by weight in the slurry) and TEA (1.5% by weight in the slurry) at two different magnifications. Figures 62A-62B show PEG-PPG-PEG triblock copolymer (4400) dispersion at 3% by weight in the slurry at two different magnifications. Figures 63A-63B show PEG-PPG-PEG triblock copolymer (4400) dispersion at 1% by weight in the slurry at two different magnifications. Figures 61A-61B, 62A-62B, and 63A-63B show the effect of dispersant on the agglomerate clusters. When triethanolamine (TEA) is added to the 4400 g / mol triblock copolymer, clusters of small agglomerates are produced, in contrast to the finer, more uniform, more discrete agglomerates with only 3% triblock copolymer, and the less fine and less uniform agglomerates with 1% triblock copolymer. Without wishing to be bound by theory, it is believed that the adhesive and non-adhesive dispersants promote uniformity of the agglomerate composition, affecting the structure of the agglomerates and providing the necessary FE / dP durability.
[0352] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, it is intended that the present specification cover modifications and variations of the various embodiments described herein, provided that such modifications and variations are within the scope of the appended claims and their equivalents.
[0353] Preferred embodiments of the present invention will be described below in detail.
[0354] EMBODIMENT 1 1. A filtration article comprising: A honeycomb filter body; the inorganic deposit is disposed in the honeycomb filter body in an amount of 20 g or less per liter of the honeycomb filter body; A clean filtration efficiency of 70% or more before exposure to the water resistance test as measured by the clean filtration efficiency test. having the clean filtration efficiency of the filtration article after exposure to the water resistance test is 80% or greater than the clean filtration efficiency of the filtration article before the water resistance test; The water resistance test is selected from the group consisting of a water absorption test, a water immersion test, or a water spray test; Filtration articles.
[0355] EMBODIMENT 2 2. The filtration article of embodiment 1, wherein the clean filtration efficiency of the filtration article prior to exposure to the water absorption test, or the water immersion test, or the water spray test is 85% or greater, or 90% or greater, or 95% or greater.
[0356] EMBODIMENT 3 3. The filtration article of embodiment 1 or 2, wherein the clean filtration efficiency of the filtration article after exposure to the water resistance test is 50% or more, or 60% or more, or 70% or more, or 80% or more, or 90% or more, or 95% or more.
[0357] EMBODIMENT 4 A filtration article according to any one of embodiments 1 to 3, wherein the inorganic deposits disposed within the honeycomb filter body are supported in an amount of 15 g or less per liter of the honeycomb filter body, or 10 g or less per liter of the honeycomb filter body, or 7 g or less per liter of the honeycomb filter body, or 5 g or less per liter of the honeycomb filter body.
[0358] EMBODIMENT 5 The filtration article according to embodiment 4, wherein the inorganic deposit disposed within the honeycomb filter body has a loading of 1 g or more of the inorganic deposit per liter of the honeycomb filter body.
[0359] EMBODIMENT 6 6. The filtration article of any one of the preceding claims, wherein the inorganic deposit does not include a precious metal.
[0360] EMBODIMENT 7 7. The filtration article of any one of the preceding embodiments, wherein the inorganic deposit is bonded to the honeycomb filter body.
[0361] EMBODIMENT 8 The filtration article of any one of the preceding embodiments, wherein at least some of the inorganic deposits are bonded to one another.
[0362] EMBODIMENT 9 9. The filtration article of any one of the preceding embodiments, wherein at least some of the inorganic deposits are disposed in islands.
[0363] EMBODIMENT 10 10. The filtration article of any one of the preceding embodiments, wherein the honeycomb filter body comprises a plurality of porous ceramic walls.
[0364] EMBODIMENT 11 11. The filtration article of embodiment 10, wherein at least some of the inorganic deposits are bonded to the porous ceramic wall.
[0365] EMBODIMENT 12 12. The filtration article of claim 10 or 11, wherein a portion of a surface of the porous ceramic wall of the inlet channel of the article is free of inorganic deposits.
[0366] EMBODIMENT 13 13. The filtration article of embodiment 12, wherein 5% or more of the surface area of the surface of the porous ceramic walls of the inlet channels of the article is free of inorganic deposits.
[0367] EMBODIMENT 14 14. The filtration article of any one of claims 10 to 13, wherein the porous ceramic wall has a porosity of 40% or more and 70% or less, or the porosity of the porous ceramic wall is 45% or more and 65% or less, or the porosity of the porous ceramic wall is 50% or more and 60% or less, or the porosity of the porous ceramic wall is 45% or more and 50% or less.
[0368] EMBODIMENT 15 1. A filtration article comprising: a honeycomb filter body comprising a plurality of porous walls comprised of a first ceramic composition, the honeycomb filter body exhibiting a honeycomb filter body filtration efficiency as measured by a Clean Filtration Efficiency Test; the inorganic deposit comprising a second ceramic composition having a loading of 20 g or less of the inorganic deposit per liter of the honeycomb filter body; Clean filtration efficiency as measured by the Clean Filtration Efficiency Test having The clean filtration efficiency is 110% or more of the honeycomb filter body filtration efficiency, the clean filtration efficiency of the filtration article after exposure to a water resistance test is 90% or greater than the clean filtration efficiency of the filtration article before the water resistance test; The water resistance test is selected from the group consisting of a water absorption test, a water immersion test, or a water spray test; Filtration articles.
[0369] EMBODIMENT 16 The filtration article of embodiment 15, wherein the clean filtration efficiency of the filtration article after exposure to the water absorption test, or the water immersion test, or the water spray test is 50% or more, or 60% or more, or 70% or more, or 80% or more, or 90% or more, or 95% or more.
[0370] EMBODIMENT 17 The filtration article of embodiment 15 or 16, wherein the clean filtration efficiency of the filtration article prior to exposure to the water absorption test, or the water immersion test, or the water spray test is 70% or more, or 75% or more, or 80% or more, or 85% or more, or 90% or more, or 95% or more.
[0371] EMBODIMENT 18 A filtration article according to any one of embodiments 15 to 17, wherein the inorganic deposits disposed within the honeycomb filter body are loaded with 15 g or less of the inorganic deposits per liter of the honeycomb filter body, or 10 g or less of the inorganic deposits per liter of the honeycomb filter body, or 7 g or less of the inorganic deposits per liter of the honeycomb filter body, or 5 g or less of the inorganic deposits per liter of the honeycomb filter body.
[0372] EMBODIMENT 19 19. The filtration article of embodiment 18, wherein the inorganic deposit disposed within the honeycomb filter body has a loading of 1 g or more of the inorganic deposit per liter of the honeycomb filter body.
[0373] EMBODIMENT 20 20. The filtration article of any one of embodiments 15 to 19, wherein the inorganic deposit is disposed on, in, or both on and in at least a portion of the wall.
[0374] EMBODIMENT 21 21. The filtration article of any one of embodiments 15 to 20, wherein at least some of the inorganic deposits are bonded to other inorganic deposits.
[0375] EMBODIMENT 22 22. The filtration article of any one of embodiments 15 to 21, wherein the inorganic deposit consists of alumina nanoparticles.
[0376] EMBODIMENT 23 23. The filtration article of any one of embodiments 15 to 22, wherein at least some of the inorganic deposits are attached to the wall.
[0377] EMBODIMENT 24 24. The filtration article of any one of embodiments 15 to 23, wherein the inorganic deposit consists of agglomerates of alumina nanoparticles.
[0378] EMBODIMENT 25 25. The filtration article of any one of embodiments 15 to 24, wherein the inorganic deposits consist of spherical agglomerates of alumina nanoparticles.
[0379] EMBODIMENT 26 26. The filtration article of any one of embodiments 15 to 25, wherein the inorganic deposits consist of aggregates of spherical agglomerates of alumina nanoparticles.
[0380] EMBODIMENT 27 27. The filtration article of embodiment 26, wherein the aggregates form a porous inorganic network disposed on at least some portions of the wall.
[0381] EMBODIMENT 28 28. The filtration article of any one of embodiments 15 to 27, wherein at least some of the inorganic deposits are present in discrete regions on or in the wall.
[0382] EMBODIMENT 29 29. The filtration article of any one of embodiments 15 to 28, wherein portions of the wall are free of inorganic deposits.
[0383] EMBODIMENT 30 16. The filtration article of embodiment 15, wherein at least a portion of the inorganic deposits form a porous inorganic network across portions of the wall.
[0384] EMBODIMENT 31 31. The filtration article of embodiment 30, wherein the porous inorganic network comprises aggregates of spherical agglomerates of refractory metal oxide nanoparticles.
[0385] EMBODIMENT 32 32. The filtration article of embodiment 31, wherein at least a portion of the refractory metal oxide nanoparticles are bound by silicon or a silicon-containing compound.
[0386] EMBODIMENT 33 33. The filtration article of any one of claims 15 to 32, wherein the porous walls of the honeycomb filter body intersect, the walls having surfaces defining a plurality of channels extending longitudinally from an inlet end to an outlet end, the plurality of channels comprising inlet channels open at the inlet end and sealed at a location spaced longitudinally from the inlet end, and outlet channels open at the outlet end and sealed at a location spaced longitudinally from the outlet end.
[0387] EMBODIMENT 34 34. The filtration article of any one of embodiments 15 to 33, wherein the inorganic deposits are unevenly distributed in the longitudinal direction.
[0388] EMBODIMENT 35 35. The filtration article of any one of claims 15 to 34, wherein the density of the inorganic deposits in the area proximate the outlet end is greater than the density of the inorganic deposits in the area proximate the inlet end.
[0389] EMBODIMENT 36 36. The filtration article of any one of embodiments 15 to 35, wherein the first composition is selected from the group consisting of ceramic oxides, ceramic carbides, ceramic nitrides, and combinations thereof.
[0390] EMBODIMENT 37 37. The filtration article of any one of embodiments 15 to 36, wherein the second composition is selected from the group consisting of ceramic oxides, ceramic carbides, ceramic nitrides, and combinations thereof.
[0391] EMBODIMENT 38 38. The filtration article of any one of claims 15 to 37, wherein the first composition is selected from the group consisting of cordierite, aluminum titanate, silicon carbide, mullite, spinel, silica, zeolite, zirconia, silicon nitride, zirconium phosphate, alumina, and combinations thereof.
[0392] EMBODIMENT 39 39. The filtration article of any one of claims 15 to 38, wherein the second composition is selected from the group consisting of cordierite, aluminum titanate, silicon carbide, mullite, spinel, silica, zeolite, zirconia, silicon nitride, zirconium phosphate, alumina, and combinations thereof.
[0393] EMBODIMENT 40 40. The filtration article of any one of embodiments 15 to 39, wherein the first composition is cordierite.
[0394] EMBODIMENT 41 41. The filtration article of any one of embodiments 15 to 40, wherein the second composition is alumina.
[0395] EMBODIMENT 42 42. The filtration article of any one of claims 15 to 41, wherein the first composition is cordierite and the second composition is alumina.
[0396] EMBODIMENT 43 43. The filtration article of any one of embodiments 15 to 42, wherein the inorganic deposit comprises a silicon-containing compound.
[0397] EMBODIMENT 44 44. The filtration article of any one of embodiments 15 to 43, wherein the inorganic deposit comprises silica.
[0398] EMBODIMENT 45 45. The filtration article of embodiment 44, wherein at least some of the inorganic deposits are bonded to the porous ceramic wall.
[0399] EMBODIMENT 46 46. The filtration article of any one of embodiments 15 to 45, wherein a portion of a surface of the porous walls of the inlet channels of the article is free of inorganic deposits.
[0400] EMBODIMENT 47 47. The filtration article of embodiment 46, wherein 5% or more of the surface area of the surfaces of the porous walls of the inlet channels of the article is free of inorganic deposits.
[0401] EMBODIMENT 48 48. The filtration article of any one of claims 15 to 47, wherein the porous wall has a porosity of 40% or more and 70% or less, or the porosity of the porous ceramic wall is 45% or more and 65% or less, or the porosity of the porous ceramic wall is 50% or more and 60% or less, or the porosity of the porous ceramic wall is 45% or more and 50% or less.
[0402] EMBODIMENT 49 1. A filtration article comprising: a honeycomb filter body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending longitudinally from an inlet end to an outlet end, the plurality of channels including inlet channels open at the inlet end and sealed at a location spaced longitudinally from the inlet end, and outlet channels open at the outlet end and sealed at a location spaced longitudinally from the outlet end; an inorganic deposit disposed on, or within, or both on and within at least some of said walls; a silicon-containing precursor binder; having the inorganic deposits are bound to each other, to the wall, or both by the silicon-containing precursor binder; Filtration articles.
[0403] EMBODIMENT 50 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is a viscoelastic solid.
[0404] EMBODIMENT 51 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is a silicone resin.
[0405] EMBODIMENT 52 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is a siloxane.
[0406] EMBODIMENT 53 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is an alkali siloxane.
[0407] EMBODIMENT 54 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is an alkoxysiloxane.
[0408] EMBODIMENT 55 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is a silicate.
[0409] EMBODIMENT 56 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is an alkali silicate.
[0410] EMBODIMENT 57 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is sodium silicate.
[0411] EMBODIMENT 58 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder comprises an inorganic component and an organic component.
[0412] EMBODIMENT 59 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder is converted to silica upon the application of heat.
[0413] EMBODIMENT 60 50. The filtration article of embodiment 49, wherein the silicon-containing precursor binder comprises an inorganic component and an organic component, and upon application of heat, the organic component is driven off and the inorganic component is converted to silica.
[0414] EMBODIMENT 61 1. A filtration article comprising: a honeycomb filter body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending longitudinally from an inlet end to an outlet end, the plurality of channels including inlet channels open at the inlet end and sealed at a location spaced longitudinally from the inlet end, and outlet channels open at the outlet end and sealed at a location spaced longitudinally from the outlet end; an inorganic deposit disposed on, or within, or both on and within at least some of said walls; having the inorganic deposits are bonded to each other, to the wall, or both; at least a portion of the inorganic deposits form a porous inorganic network across portions of the wall; The clean filtration efficiency of the filtration article is 70% or greater as measured by the Clean Filtration Efficiency Test. Filtration articles.
[0415] EMBODIMENT 62 62. The filtration article of embodiment 61, wherein the filtration article has a resistance to moisture such that the clean filtration efficiency of the article does not change by more than 5% after the article is exposed to a water absorption test, a water immersion test, a water spray test, or a combination thereof.
[0416] EMBODIMENT 63 62. The filtration article of embodiment 61, wherein the clean filtration efficiency of the article does not change by more than 5% after exposure to a high gas flow test, a gas backflow test, a vibration test, a high temperature test, or a combination thereof.
[0417] EMBODIMENT 64 A filtration article described in any one of embodiments 61 to 63, wherein the inorganic deposits disposed within the honeycomb filter body have a loading amount of 15 g or less of the inorganic deposits per liter of the honeycomb filter body, or 10 g or less of the inorganic deposits per liter of the honeycomb filter body, 7 g or less of the inorganic deposits per liter of the honeycomb filter body, or 5 g or less of the inorganic deposits per liter of the honeycomb filter body.
[0418] EMBODIMENT 65 65. The filtration article of embodiment 64, wherein the inorganic deposit disposed within the honeycomb filter body has a loading of at least 1 g of the inorganic deposit per liter of the honeycomb filter body.
[0419] EMBODIMENT 66 66. The filtration article of any one of embodiments 61 to 65, wherein the inorganic deposit has a porosity of 70% or more, or 80% or more, or 90% or more, or 95% or more.
[0420] EMBODIMENT 67 62. The filtration article of embodiment 61, wherein the inorganic deposit comprises refractory nanoparticles.
[0421] EMBODIMENT 68 62. The filtration article of embodiment 61, wherein at least some of the inorganic deposits are present in discrete regions on or in the wall.
[0422] EMBODIMENT 69 62. The filtration article of embodiment 61, wherein at least some of the inorganic deposits form a porous inorganic interlaced microstructure across portions of the surfaces of some of the walls.
[0423] EMBODIMENT 70 62. The filtration article of embodiment 61, wherein at least some of said surfaces of some of said walls are free of inorganic deposits.
[0424] EMBODIMENT 71 62. The filtration article of embodiment 61, wherein the inorganic deposit comprises agglomerates of refractory nanoparticles.
[0425] EMBODIMENT 72 72. The filtration article of embodiment 71, wherein the agglomerates are spherical in shape.
[0426] EMBODIMENT 73 62. The filtration article of embodiment 61, wherein said inorganic deposits consist of individual agglomerates, clusters of agglomerates, or both.
[0427] EMBODIMENT 74 The filtration article of embodiment 73, wherein the clusters are elongated or blocky in shape.
[0428] EMBODIMENT 75 62. The filtration article of embodiment 61, wherein the inorganic deposits are non-uniformly distributed along the length.
[0429] EMBODIMENT 76 62. The filtration article of embodiment 61, wherein the accumulation of inorganic deposits is greater away from the open portions of the channels.
[0430] EMBODIMENT 77 62. The filtration article of embodiment 61, wherein the inorganic deposit further comprises an inorganic binder that binds the refractory nanoparticles to one another, or to the wall, or to bind the refractory nanoparticles to one another and to the wall.
[0431] EMBODIMENT 78 78. The filtration article of embodiment 77, wherein the inorganic binder comprises one or more components having a melting point above 1000° C.
[0432] EMBODIMENT 79 78. The filtration article of embodiment 77, wherein the inorganic binder comprises one or more components that are stable at temperatures of 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, or 1300°C or greater.
[0433] Embodiment 80 78. The filtration article of embodiment 77, wherein the inorganic binder comprises a silicon-containing compound.
[0434] Embodiment 81 78. The filtration article of embodiment 77, wherein the inorganic binder comprises silica.
[0435] EMBODIMENT 82 1. A filtration article comprising: a honeycomb body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel sealed at a location spaced from the inlet end and an outlet channel sealed at a location spaced from the outlet end; an inorganic deposit disposed on, or within, or both on and within at least some of the walls defining the inlet channel; having The filtration article has a clean filtration efficiency of 70% or greater as measured by the Clean Filtration Efficiency Test; the filtration article is moisture resistant such that the clean filtration efficiency of the article does not change by more than 5% after exposure to a water absorption test, a water immersion test, a water spray test, or a combination thereof; Filtration articles.
[0436] EMBODIMENT 83 1. A filtration article comprising: a honeycomb body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel sealed at a location spaced from the inlet end and an outlet channel sealed at a location spaced from the outlet end; an inorganic deposit disposed on, or within, or both on and within at least some of the walls defining the inlet channel; having the inorganic deposit comprises refractory inorganic nanoparticles bound by a high temperature binder comprising one or more inorganic components; The filtration article has a clean filtration efficiency of 70% or greater as measured by the Clean Filtration Efficiency Test; the filtration article is moisture resistant such that the clean filtration efficiency of the article does not change by more than 5% after exposure to a water absorption test, a water immersion test, a water spray test, or a combination thereof; Filtration articles.
[0437] EMBODIMENT 84 84. The filtration article of embodiment 83, wherein at least a portion of the inorganic deposits form a porous inorganic network across portions of the wall.
[0438] EMBODIMENT 85 85. The filtration article of embodiment 83 or 84, wherein the inorganic deposit consists of refractory metal oxide nanoparticles.
[0439] EMBODIMENT 86 84. The filtration article of embodiment 83, wherein said inorganic deposits consist of nanoparticles present in the form of agglomerates.
[0440] EMBODIMENT 87 84. The filtration article of embodiment 83, wherein the inorganic deposits consist of aggregates of spherical agglomerates of nanoparticles.
[0441] EMBODIMENT 88 88. The filtration article of embodiment 87, wherein the nanoparticles comprise alumina.
[0442] EMBODIMENT 89 84. The filtration article of embodiment 83, wherein the high temperature binder comprises at least one component that is stable at temperatures of 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, or 1300°C or greater.
[0443] EMBODIMENT 90 84. The filtration article of embodiment 83, wherein the high temperature binder is a silicon-containing binder.
[0444] EMBODIMENT 91 84. The filtration article of embodiment 83, wherein the high temperature binder is a silicone resin.
[0445] EMBODIMENT 92 84. The filtration article of embodiment 83, wherein the high temperature binder is a siloxane.
[0446] EMBODIMENT 93 84. The filtration article of embodiment 83, wherein the high temperature binder is an alkoxysiloxane.
[0447] EMBODIMENT 94 84. The filtration article of embodiment 83, wherein the high temperature binder is a silicate.
[0448] EMBODIMENT 95 84. The filtration article of embodiment 83, wherein the high temperature binder is an alkali silicate.
[0449] EMBODIMENT 96 84. The filtration article of embodiment 83, wherein the high temperature binder is sodium silicate.
[0450] EMBODIMENT 97 1. A filtration article comprising: a honeycomb body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel sealed at a location spaced from the inlet end and an outlet channel sealed at a location spaced from the outlet end; an inorganic material disposed on, or within, or both on and within at least some of the walls defining the inlet channel; having The filtration article has a clean filtration efficiency of 70% or greater as measured by the Clean Filtration Efficiency Test; the filtration article is moisture resistant such that the clean filtration efficiency of the article does not change by more than 5% after exposure to a water absorption test, a water immersion test, a water spray test, or a combination thereof; Filtration articles.
[0451] EMBODIMENT 98 1. A filtration article comprising: a honeycomb body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel sealed at a location spaced from the inlet end and an outlet channel sealed at a location spaced from the outlet end; a porous inorganic network of refractory metal oxide nanoparticles disposed on, or within, or both on and within at least some of the walls defining the inlet channels; having the refractory metal oxide nanoparticles are bound by a high temperature binder comprising one or more inorganic components; The filtration article has a clean filtration efficiency of 70% or greater as measured by the Clean Filtration Efficiency Test; the filtration article is moisture resistant such that the clean filtration efficiency of the article does not change by more than 5% after exposure to a water absorption test, a water immersion test, a water spray test, or a combination thereof; Filtration articles.
[0452] EMBODIMENT 99 99. The filtration article of embodiment 98, wherein the high temperature binder is provided by a silicon-containing binder precursor.
[0453] EMBODIMENT 100 100. The filtration article of embodiment 99, wherein the high temperature binder comprises at least one component that is stable at temperatures of 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, or 1300°C or greater.
[0454] EMBODIMENT 101 99. The filtration article of embodiment 98, wherein the high temperature binder is a silicon-containing binder.
[0455] EMBODIMENT 102 100. The filtration article of embodiment 99, wherein the silicon-containing binder binds some of the refractory metal oxide nanoparticles to one another.
[0456] EMBODIMENT 103 100. The filtration article of embodiment 99, wherein the silicon-containing binder binds some of the refractory metal oxide nanoparticles to the porous walls of the honeycomb body.
[0457] EMBODIMENT 104 100. The filtration article of embodiment 99, wherein the silicon-containing binder binds the refractory metal oxide nanoparticles to each other and to the porous walls of the honeycomb body.
[0458] EMBODIMENT 105 100. The filtration article of embodiment 99, wherein the silicon-containing binder is one or more of the group consisting of silica, silicone resin, sodium silicate, colloidal silica, and combinations thereof.
[0459] EMBODIMENT 106 100. The filtration article of embodiment 99, wherein the silicon-containing binder precursor is a silicone resin.
[0460] EMBODIMENT 107 100. The filtration article of embodiment 99, wherein the silicon-containing binder precursor is a siloxane.
[0461] EMBODIMENT 108 100. The filtration article of embodiment 99, wherein the silicon-containing binder precursor is an alkoxysiloxane.
[0462] EMBODIMENT 109 100. The filtration article of embodiment 99, wherein the silicon-containing binder precursor is a silicate.
[0463] Embodiment 110 100. The filtration article of embodiment 99, wherein the silicon-containing binder precursor is an alkali silicate.
[0464] EMBODIMENT 111 100. The filtration article of embodiment 99, wherein the silicon-containing binder precursor is sodium silicate.
[0465] EMBODIMENT 112 1. A filtration article comprising: A honeycomb filter body having a porous wall having pores; an inorganic deposit including inorganic material nanoparticles and a binder disposed within the honeycomb filter body; having the inorganic deposit comprises a network of cohesive agglomerates of the inorganic material nanoparticles and the binder, the binder comprising an alcohol-soluble binder; Filtration articles.
[0466] EMBODIMENT 113 113. The filtration article of embodiment 112, wherein the agglomerates are comprised of nanoparticles of an inorganic material, and the network of agglomerates comprises aggregates of the agglomerates.
[0467] EMBODIMENT 114 The filtration article of embodiment 113, wherein said network of agglomerates comprises clusters or chains of said aggregates.
[0468] EMBODIMENT 115 115. The filtration article of embodiment 114, wherein at least a portion of the clusters or chains are disposed within the pores in or below the surface of the porous wall, and at least a portion of the clusters or chains are disposed above the surface of the porous wall.
[0469] EMBODIMENT 116 116. The filtration article of embodiment 114 or 115, wherein some of the clusters are porous clusters comprising exposed agglomerates of agglomerates.
[0470] EMBODIMENT 117 117. The filtration article of embodiment 116, wherein the porous cluster comprises one or more chains of two or more agglomerates, each chain extending in an outward direction from the porous wall.
[0471] EMBODIMENT 118 117. The filtration article of embodiment 116, wherein said porous cluster comprises a plurality of said outwardly extending chains that collectively provide a morphology resembling a member of the group consisting of fingers, tufts, and sponges.
[0472] EMBODIMENT 119 119. The filtration article of any one of embodiments 112 to 118, wherein the inorganic material comprises one or more of ceramic particles, metal oxide particles, and refractory metal oxide particles.
[0473] Embodiment 120 120. The filtration article of any one of embodiments 112 to 119, wherein the inorganic material comprises alumina.
[0474] EMBODIMENT 121 121. The filtration article of any one of embodiments 112-120, wherein the inorganic material is present on the honeycomb filter body at a loading in the range of 1-20 g / L or 1-10 g / L.
[0475] EMBODIMENT 122 122. The filtration article of any one of embodiments 112 to 121, wherein the inorganic material has a porosity of greater than 80% and less than 95%.
[0476] EMBODIMENT 123 123. The filtration article of any one of embodiments 112 to 122, wherein the alcohol-soluble binder comprises a silicon-containing binder.
[0477] EMBODIMENT 124 124. The filtration article of any one of embodiments 112 to 123, wherein the binder comprises an alkoxysiloxane.
[0478] EMBODIMENT 125 125. The filtration article of any one of embodiments 112-124, wherein the binder is present on the honeycomb filter body in an amount in the range of 5% to about 30% by weight of the inorganic material.
[0479] EMBODIMENT 126 1. A filtration article comprising: A honeycomb filter body having a porous wall having pores; an aggregate of agglomerates of inorganic nanoparticles and a silicon-containing binder disposed within the honeycomb filter body; having The aggregates are present in an amount of 0.1 to 20 g (g / L) per liter unit volume of the honeycomb filter body. Filtration articles.
[0480] EMBODIMENT 127 127. The filtration article of embodiment 126, wherein at least a portion of the aggregates are disposed within the pores on an outer surface of the porous wall or below the surface of the porous wall.
[0481] EMBODIMENT 128 128. The filtration article of embodiment 126 or 127, wherein the inorganic material comprises alumina.
[0482] EMBODIMENT 129 129. The filtration article of any one of embodiments 126 to 128, wherein the binder is alcohol-soluble or water-soluble.
[0483] Embodiment 130 130. The filtration article of any one of embodiments 126 to 129, wherein the binder comprises an alkoxysiloxane.
[0484] EMBODIMENT 131 130. The filtration article of any one of embodiments 126 to 129, wherein the binder comprises sodium silicate.
[0485] EMBODIMENT 132 132. The filtration article of any one of embodiments 126-131, wherein the binder is present on the honeycomb filter body in an amount in the range of 5% to about 30% by weight of the inorganic material.
[0486] EMBODIMENT 133 133. The filtration article of any one of embodiments 126 to 132, wherein the inorganic deposit does not include rare earth oxides, platinum group metals, and molecular sieves.
Claims
1. 1. A filtration article comprising: a honeycomb body comprising a plurality of intersecting porous walls having surfaces defining a plurality of channels extending from an inlet end to an outlet end, the plurality of channels including an inlet channel sealed at a location spaced from the inlet end and an outlet channel sealed at a location spaced from the outlet end; a porous inorganic network of refractory metal oxide nanoparticles disposed on at least some of said plurality of intersecting porous walls defining said inlet channel, or disposed within at least some of said plurality of intersecting porous walls, or disposed both on and within at least some of said plurality of intersecting porous walls; having the refractory metal oxide nanoparticles are bound by a high temperature binder comprising one or more inorganic components; the filtration article has a clean filtration efficiency of 70% or greater as measured by the Clean Filtration Efficiency Test; the filtration article is moisture resistant such that the clean filtration efficiency of the filtration article does not change by more than 5% after exposure to a water absorption test, a water immersion test, a water spray test, or a combination thereof; Filtration articles.
2. The filtration article of claim 1 , wherein the high temperature binder is a silicon-containing binder.
3. The filtration article of claim 2 , wherein the silicon-containing binder binds some of the refractory metal oxide nanoparticles together.
4. The filtration article of claim 2 , wherein the silicon-containing binder bonds some of the refractory metal oxide nanoparticles to the plurality of intersecting porous walls of the honeycomb body.
5. The filtration article of claim 2 , wherein the silicon-containing binder binds the refractory metal oxide nanoparticles to each other and to the plurality of intersecting porous walls of the honeycomb body.
Citation Information
Patent Citations
Method for manufacturing honeycomb structure
JP2012075989A
MULTI-CELL CERAMIC PRODUCT AND PRODUCTION METHOD THEREOF
JP2016520498A
Porous ceramic filter and method for producing the same
JP2018533471A
Honeycomb structure and exhaust gas purifier
WO2007097056A1
Honeycomb filter
WO2008136232A1